Electron pump-shuttle cathode enables coupled directed-electron flows for resource-oriented treatment of radioactive wastewater - Xijun Fu; Shuai Gao; Haodong Ji; Yanbiao Liu; Sujie Yang; Binsheng He; Ping Cao; Qingyan Zhang; Le Li; Yifeng Hu; Qingyi Zeng (Water Research, 2026)

Magnet-absorbed detrital magnetite from the western Qaidam Basin: Implications to Mars sample return missions - Qi-Tao Hu; Wen-Ping Liu; Qi-Zhi Yao; Shao-Bing Zhang; Wan-Cai Li; Sheng-Quan Fu; Yi-Liang Li; Gen-Tao Zhou (Icarus, 2026)

Piperlongumine inhibits the proliferation and migration of non-small cell lung cancer cells through the EGFR/FAK/STAT3 pathway - Qianwen Huang; Wen Chen; Xin Xu; Jiaxin Hua; Lehui Li; Ping Hu; Wei Zhang; Longhua Sun (Molecular Biology Reports, 2026)

Distinct soil microbial community composition and structure: evidence from soil inside and outside the cattle farm - Qi Ding; Jiayi Li; Fengling Xue; Wenjun Cui; Shiguang Hu; Lingfeng Yu; Wanyue Huang; Lin Li; Ping Cheng (Brazilian Journal of Microbiology, 2026)

Genome-wide identification and functional validation of asparagine synthetase genes (NtASNs) in Nicotiana tabacum - Yan-Qun Zhang; Xin-Yao Huang; Wu-Xia Xi; Pei-Song Yang; Jia-Rong Wu; Jian-Cheng Wu; Shao-Ming Zhao; Hang Li; Rong Zhang; Shi-Ping Zhou; Wei-Guang Wang; Qiu-Fen Hu; et al. (Plant Science, 2026)

Columnar optical properties of locally emitted light-absorbing carbonaceous aerosols - Kang Hu; Hong Liao; Dantong Liu; Jianbing Jin; Siyuan Li; Yangzhou Wu; Yuxing Gao; Xiaotong Jiang; Shitong Zhao; Ping Tian; Fei Wang; Na Kang; et al. (Journal of Environmental Sciences, 2026)

Historical and future changes in Tibetan Plateau aridity and their scenario-dependent climatic controls - Libin Huang; Ping Li; Jiajia Zhang; Yanjin Mao; Xianchun Chen; Xiaoyu Hu; Xiaorui Niu (Climate Dynamics, 2026)

Two-stage illumination with various lights regulate microalgal metabolism for enhanced pollutant removal and eicosapentaenoic acid (EPA) production from high-salinity food-processing wastewater - Hao Hu; Si Wu; Wei-Di Song; Zheng-Hao Li; Yan-Yun Hu; Guo-Ping Sheng (Water Research, 2026)

Aspergthones A and B, hybrids of dehydrosterigmatocystin with phenolic derivatives, isolated from the endophytic fungus Aspergillus versicolor VDL117 - Shan Hu; Mei Yang; Zhi-Yu Zhang; Yun-Xian Li; Xiao-Qin Yang; Wei-Hua Wang; Ying-Jun Zhang; Ping Zhao; Guo-Lei Zhu (Phytochemistry Letters, 2026)

Scleroglucan from Agroathelia rolfsii ameliorates glucolipid metabolic dysfunction in high-fat diet-fed mice and is associated with gut microbiota and metabolite changes - Dafang Yin; Kairui Tong; Min Zhou; Ping Yu; Mengfan Lyu; Mine Yang; Yanlong Wen; Lianghua Wen; Yang Li; Yadong Zhong; Jielun Hu (Food Research International, 2026)

Integrated analysis of lipid remodeling and volatile evolution during refining of Antarctic krill oil - Xinya Huang; Meiyu Zheng; Jin Zhang; Jinglun Zhou; Qingyang Zhang; Zhengting Zhu; Ping Kong; Shu Wang; Bin Li; Zhigang Hu; Kangyu Zhao; Dongping He; et al. (Food Chemistry, 2026)

Erosion and entrainment in dry granular flows: Insights from large-scale experiments - Shi-lin Zhang; Yang Gao; Yue-ping Yin; Lonneke Roelofs; Wen-pei Wang; Xie-wen Hu; Bin Li (Engineering Geology, 2026)

Hierarchical core–shell nanoplatforms based on sacrificial template-directed ZnO2@ZIF-8 for spatiotemporally controlled and self-augmented chemodynamic–photothermal antibacterial therapy - Yi-Fei Hui; Duan-Ping Hu; Yi Zhao; Shulin Li; Zhi-Feng Cai; Lin-Yi Li; Yuming Xie; Yong-Nian Zeng; Zu-Jin Lin; Fa-Qiang Tang (Chemical Engineering Journal, 2026)

Interfacial engineering of biochar/SnO2 heterojunctions for enhanced charge transfer and gas-sensing performance - Ping Hu; Jun Sun; Jialin Li; Aolin Li; Haiming Duan; Zhaofeng Wu (Chemical Engineering Journal, 2026)

Mercury pollution remediation in paddy fields with biochar amendment - Yanxin Hu; Chuan Wang; Junyao Yan; Ruolan Li; Rasheed Mohammed Abdul; Yan An; Jinjuan Li; Ping Li (Applied Geochemistry, 2026)

Mapping the True 3D Architecture: Quantitative Morphological Diversity of Human Hepatic Functional Unit Revealed by Fluorescence Micro-optical Section Tomography - Na Chen; Hongjun Liu; Xiaofeng Mei; Silin Liu; Hongjia Hu; Yunxi Lv; Qi Li; Wei Feng; Yifang Ping; Lu Zheng; Shiwu Dong; Yi Wu (Tissue and Cell, 2026)

Balancing color and order: Configuration-dependent effects of dominant color composition and spatial structure on scenic quality in urban forest landscapes - Zuoyou Hu; Ping Li; Zhongyi Li; Jiheng Li; Xianwen Li; Bingqian Ma; Chengyang Xu; Richard J. Hauer (Journal of Environmental Management, 2026)

Inside-out conversion of open pores into closed nanopores enables high-plateau hard carbon anodes for sodium-ion batteries - Zhuo Xiong; Rui Li; Ping Liu; Shuang Lin; Chaoshu Zhao; Wenyuan Fu; Jiale Shen; Lili Xiao; Xuedan Chen; Jianping Long; Xianguang Zeng; Anjun Hu; et al. (Chemical Engineering Journal, 2026)

A divalent nanoparticle vaccine confers robust protective immunity against serotype O FMDV and SVA in pigs - Nan Cao; Yamei Li; Xinghua Chen; Hehai Li; Linxing Tian; Zihui Hu; Yin Bo; Feifei Diao; Huanchun Chen; Xiangmin Li; Ping Qian (Veterinary Microbiology, 2026)

Divergent responses of ecosystem water use efficiency to environmental drivers in arid versus humid regions - Hailing Li; Maohong Wei; Hongling Yang; Ya Hu; Shaokun Wang; Ping Yue; Xujun Ma; Fangwei Hao; Rong Ma; Xiaoan Zuo (Journal of Environmental Management, 2026)

PFASs contamination in groundwater of a chemical industrial park and its implications for adjacent surface water: Spatial distribution, source characteristics, and ecological risk - Qi Ping; Zhihao Zhang; Jiqing Li; Wenxi Zhang; Tianqi Wang; Jianlei Chen; Shuya Hu (Journal of Contaminant Hydrology, 2026)

Effect of depth-direction SVF gradient on particle deposition performance in fibrous media - Ankang Zhou; Shihang Li; Jiahua Chai; Kunkun Tu; Hao Jin; Wenjie Liang; Shuda Hu; Fan Geng; Qiang Zhang; Wuping Peng; Ping Li (Journal of Aerosol Science, 2026)

Deep mantle reservoirs of recycled surface carbonates revealed by Mg-Sr-Nd-Pb isotopes in continental basalts - Yan-Qing Li; Chang-Qian Ma; Xiao-Ping Xia; Bin Liu; Ji-Ping Yu; Xiang-Yun Hu (Geochimica et Cosmochimica Acta, 2026)

Effects of dietary rosemary extract on meat quality, antioxidant capacity, fatty acid and amino acid compositions, and proteomic profile of duck breast muscle - Yang Liu; Xuan Huang; Chuang Li; Ping Deng; Xu Zhang; Yan Hu; Qiuzhong Dai (Food Chemistry, 2026)

Minutes-long soft X-ray prompt emission from a compact object merger - An Li; Chen-Wei Wang; Niccolò Passaleva; Jie An; Bin-Bin Zhang; Eleonora Troja; Yi-Han Iris Yin; Yuan Liu; Shao-Lin Xiong; Li-Ping Xin; Yi-Xuan Shao; Jun Yang; et al. (Science Bulletin, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Dimefluthrin-induced multigenerational endocrine toxicity in zebrafish (Danio rerio) offspring via parental exposure - Wei-Guo Wang; Rui-Rui Li; Ming-Jun Yang; Jing-Ying Hu; Wen-Ping Xu; Li-Ming Tao; Yang Zhang (Pesticide Biochemistry and Physiology, 2026)

A peroxisomal metabolic route from benzoyl-CoA to benzyl alcohol for phenylalanine-derived salicylic acid biosynthesis in rice - Yukang Wang; Shuyan Song; Wenxuan Zhang; Qianwen Deng; Yang Lai; Zhixue Huo; Shanshan Li; Qi Zhang; Yuchen Ping; Jiarong Chen; Zeng Tao; Yanlei Feng; et al. (Molecular Plant, 2026)

Comprehensive life-cycle assessment of a hybrid renewable energy system–powered decentralized sewage treatment system in cold and rural Inner Mongolia - Shangbin Ma; Ping Miao; Shugang Guo; Yaoting Hu; Hongli Ma; Pengyu Li; Pengfei Cao; Dawen Gao; Jing Luo; Jianguo Liu; Tianlong Zheng (Journal of Water Process Engineering, 2026)

Changes in perceptions of cultural ecosystem services in urban coastal park during different phases of COVID-19: Integrating the prompt engineering and aspect-based sentiment analysis with a large language model - Zirui Zhao; Ping Li; Bin Chen; Weiwei Yu; Wenjia Hu; Zhiyuan Ma; Jianji Liao (Journal of Cleaner Production, 2026)

Study on the generation of combustion pollutants and the transformation mechanism of N during NH3/CH4 combustion under MILD conditions - Huichun Wang; Ping Chen; Yongtao Li; Mingyan Gu; Kun Luo; Xun Hu (Fuel, 2026)

ERBB2 as a Prognostic Biomarker in Prostate Cancer: Integration of Single-Cell Transcriptomics, Deep Learning, and Immunohistochemical Validation - Chen Wang; Li-Jing Zhu; Wei-Bo Mao; Ting Chen; Teng-Fei Gu; Sheng-Ping Hu; Yong-Tao Pan; Guo-Lin Yan; Yun-Peng Dong; Jie Li (Biochemical Genetics, 2026)

Reliability-adaptive graph-cut phase unwrapping for InSAR geohazard deformation monitoring - Huadong Hu; Ping Zhang; Zhen Li; Jiangyuan Zeng; Haiwei Qiao; Yanan Bai; Siqing Xu; Hui Yuan (International Journal of Remote Sensing, 2026)

Exploring contributions and responses of microbial quantity and diversity to coastal seasonal hypoxia - Guihao Li; Jiarong Hu; Pengfei Zheng; Ping Zhu; Yaping Wang; Songbao Zou; Xiaoli Zhang; Eleni Gentekaki; Song Sun; Aolin Zhu; Jun Gong (Marine Pollution Bulletin, 2026)

Pancancer pro-angiogenic atlas unravels tumor-educated pericyte-augmented anti-angiogenic resistance - Yongqiang Zheng; Hui Sun; Zhe Fu; Haojie Chen; Guangyao Cai; Xin Huang; Yi-Qian Pan; Kai Yu; Ping Chen; Zhuoran Liang; Junteng Li; Jiamin Hu; et al. (Science Bulletin, 2026)

Ion trapping as an intrinsic physicochemical barrier limiting plant translocation and phytotoxicity of ionizable contaminants - Zhi-Yu Lu; Jia-Heng Zhao; Li Yuan; Yan-Yun Hu; Yi Hu; Cheng-Yuan Liu; Yang Pan; Chun-Chun Lv; Ke-Ke Qi; Wei Zhi; Guo-Ping Sheng (Journal of Environmental Sciences, 2026)

Synergistic effects of sequential ultrasound and autoclaving treatments on the structure, functionality, and digestibility of chestnut starch varieties - Yuan-Yuan Zhang; Can Xu; Ming-Xue Tu; Yin-Ping Zhang; Cong-Hu Li; Liang-Liang Zhu; Ting Hu (Food Chemistry, 2026)

Defensive remodeling of gut microbiota under microplastic stress and its pathogenic mechanism - Penghua Jian; Feng Zhang; Zhihao Chen; Xuan Zhou; Yan Xiong; Qiang Hu; Yingyu Wang; Dan Li; Jiai Yan; Ju Yang; Hong Cao; Ping Wu; et al. (Chemico-Biological Interactions, 2026)

GPD1-mediated neuronal lipotoxicity drives aconitine-induced mitochondrial collapse and lethality - Chen Jiang; Wen Hu; Sangyang Deng; Yongjie Huang; Linbo Wang; Zhenyu Yang; Yufei Li; Ping Li; Haiying Wu (Chemico-Biological Interactions, 2026)

Independent and joint effects of ambient temperature and relative humidity on fetal distress: effect modification by air pollutants - Hua Xiao; Yi Wang; Zongli Qi; Ziwei Ye; Liping Li; Li Mao; Peng Hu; Yuefei Li; Haoyun Zhang; Yao Cheng; Hao Wang; Ping Chen; et al. (International Journal of Biometeorology, 2026)

Groundwater-surface water interactions and material fluxes in a typical watershed, Ordos Plateau, NW China: insight from hydrochemistry, stable isotopes and 222Rn mass balance model - Wei Bao; Yixuan Wang; Ao Gao; Jiping Yao; Shen Qu; Jiajun Li; Dong Qian; Le Qiao; Lijuan Hu; Hongli Ma; Ping Miao; Haixia Wu; et al. (Environmental Geochemistry and Health, 2026)

Potential targets of baicalein in macrophages revealed by bulk and single cell RNA sequencing analysis - Ping Li; Jianran Hu; Yan Zhang; Xia Bai (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Mycorrhizal-association type mediates soil priming effect and its response to nitrogen addition in subtropical plantations - Wei Zhang; Xiao-Hong Wang; Liming Yin; Maokui Lyu; Lin-Qiao Jia; Li-Li Wang; Ai-Ping Liu; Xiao-Die Hu; Xiaodong Yao; Guang-Shui Chen (Pedobiologia, 2026)

Sediment physicochemical and dissolved organic matter control microbial responses and nitrous oxide emissions across a coastal wetland transition from invasion to reclamation - Shengwei Cao; Yaci Liu; Ping Yang; Xiujian Hu; Yan Dong; Xiangyu Guan; Ping Yin; Yasong Li (Journal of Environmental Management, 2026)

Paleoseismic activity revealed from soft sediment deformation structures in the Eastern Himalayan Syntaxis since the Last Glacial Maximum - Huiying Wang; Ping Wang; Gang Hu; Zinan Zou; Wenqiao Li; Chao Xie (Journal of Asian Earth Sciences, 2026)

Structural characterization and antitumor activity via immune modulation of an α-glucan from Grifola frondosa - Hui-Xiang Tian; Qin-Zhao Ruan; Yi-Zhen Xie; Wei Chen; Chun Xiao; Wei Zhong; Yuan-Chao Liu; Shao-Dan Chen; Tian-Qiao Yong; Hui-Ping Hu; Xiang-Min Li; Qing-Ping Wu (Carbohydrate Polymers, 2026)

Delayed response of river sediment to drainage reorganization in the arid and semi-arid regions - Menghao Li; Zhenbo Hu; Ping Wang; Qinhong Mo; Baotian Pan; Eduardo Garzanti (CATENA, 2026)

Corrigendum to “Hellebrigenin induces cell cycle arrest and apoptosis in human hepatocellular carcinoma HepG2 cells through inhibition of Akt” [Chemico. Biol. Interact. 219 (2014) 184-194] - Li-Juan Deng; Li-Ping Hu; Qun-Long Peng; Xiao-Lin Yang; Liang-Liang Bai; Anita Yiu; Yong Li; Hai-Yan Tian; Wen-Cai Ye; Dong-Mei Zhang (Chemico-Biological Interactions, 2026)

High-quality genome of guar (Cyamopsis tetragonoloba) provides the new insights into the biosynthesis and origination of galactomannans in Fabaceae family - Yuanhao Ding; Xinglong Zhao; Hui Yao; Shicai Huang; Xuyao Wang; Yayu Chen; Ping Li; Chengzhi Xie; Jiaquan Huang; Zhuang Yang; Haiyan Hu (Plant Cell Reports, 2026)

Characterization and source apportionment of halogenated organic pollutants in sediments from the Daya Bay, South China Sea - Ren-Jie Shang; Jian-Fang Hu; Ming-Yang Liu; Yao Xiao; Yi-Ting Zeng; Li-Tian Huang; Ping-An Peng (Marine Pollution Bulletin, 2026)

Impact of macroalgae farming on the carbonate system and biogenic sulfur dynamics in Sansha Bay, China - Ping Wang; Zheng-Xin Hu; Yu Xin; Bing-Han Li; Lu Han; Shu-Hang Dong; Chun-Ying Liu; Tao Liu; Jing-Wen Hu; Jiang-Chen Gong; Gui-Peng Yang (Marine Pollution Bulletin, 2026)

Digital disaster prevention for ocean engineering: Current progress and future directions - Zhen-Zhong Hu; Yilin Li; Fu-Ping Gao; Jian-Min Zhang (Ocean Engineering, 2026)

Structural dynamics of chloroplast genome in Paphiopedilum (Orchidaceae): in response to natural hybridization - Xue-Ying Wei; Ai-Qun Hu; Jin Zhou; Jiang-Ping Shu; Wei-Yue Sun; Li-Qiang Li; Jian-Wen Shao; Hui Wang; Yue-Hong Yan (Molecular Phylogenetics and Evolution, 2026)

Nitrate-mediated anaerobic microorganism-sponge iron system promoting simultaneous nitrogen and phosphate removal from piggery tail water - Qin Liao; Cong Jin; Ping Li; Jinhua Wu; Chiqian Zhang; Zhiqiang Hu (Journal of Environmental Sciences, 2026)

Oil phase-driven nanoemulsions improve CoQ10 stability, in vitro bioaccessibility and ex vivo intestinal uptake - Xia Jin; Peng Wu; Ni Wang; Ping Zhang; Cheng Li; Zejun Hu; Wenhao Zhao; Xiao Dong Chen (Food Research International, 2026)

Synergistic effects of dual enzymatic hydrolysis and heat-moisture treatment on starch digestibility and structure in multi-grain flour - Xinrui Ren; Pai Peng; Qianying Ma; Xiaolong Wang; Ping Li; Xinzhong Hu (Food Research International, 2026)

Parental DEHP exposure induces sex-specific reproductive toxicity in zebrafish and behavioral deficits in unexposed offspring - Yanan Sun; Yuqing Fan; Yao Dang; Ping Ding; Xin Li; Gang Li; Haojie Luo; Jianliang Zhao; Guocheng Hu (Environmental Pollution, 2026)

Distribution, source, and pollution risk assessment of heavy metals in the coastal sediments of the northern South China sea - Wen Yu; Yuqing Fan; Qinghua Chen; Jing Yang; Xin Li; Wei Huang; Kun Yue; Liuyi Zhang; Ping Ding; Guocheng Hu; Yunjiang Yu (Environmental Pollution, 2026)

A glucose-triggered self-reinforcing hydrogel based on carboxymethyl chitosan/oxidized hyaluronic acid/borax for delivering nano-selenium and dynamic diabetic wound management - Wei-Xiong Li; Shanshan Li; Hao Cheng; Yu Chen; Han-Jian Hu; Shipeng Tang; Jian Sun; Xiao-Ping Liao; Gang-Biao Jiang; Hongyan Zhang (Carbohydrate Polymers, 2026)

Investigation of post-rainfall dynamic behavior of anti-dip layered rock slope through shaking table tests - Ping Hu; DeGou Cai; XianQing Xu; HongYe Yan; JunKai Yao; TaiFeng Li (Bulletin of Earthquake Engineering, 2026)

Shrub Encroachment Constrains Precipitation‐Driven Shifts in Herbaceous Biomass‐Diversity Relationships - Hailing Li; Xiaoan Zuo; Fons van der Plas; Ya Hu; Fangwei Hao; Hongling Yang; Xiangyun Li; Ping Yue; Shaokun Wang; Zhaobin Song; Rentao Liu; Jiansheng Ye; et al. (Global Change Biology, 2026)
The relationship between herbaceous above ground biomass and species richness typically exhibits a unimodal pattern, shifting from positive under low‐precipitation conditions to negative under high‐precipitation conditions. While shrub encroachment generally reduces both herbaceous aboveground biomass and diversity, how shrubs mediate the herbaceous biomass‐richness relationship under altered precipitation regimes remains unclear. By synthesizing data from globally distributed precipitation manipulation experiments, we reveal contrasting herbaceous biomass‐diversity responses in grasslands and shrublands. In grasslands, reduced precipitation shifts the peak of the unimodal herbaceous biomass‐richness curve toward lower biomass, whereas increased precipitation shifts it toward greater biomass. In contrast, the peak of the unimodal relationship in shrub‐dominated systems shows no significant shifts across precipitation extremes. These global patterns are supported by a 5‐year field experiment in a desert steppe in Northern China, which further shows that precipitation change strongly affects species richness through soil water availability in grasslands, while exerting weaker effects through modifications of the fast‐slow leaf economics spectrum in shrublands. These findings demonstrate that shrub encroachment can constrain precipitation‐induced changes in herbaceous biomass‐diversity relationships, providing important insights into how woody plant expansion interacts with climate change to influence ecosystem structure and function.

Flucarbazone-sodium resistance detection in Japanese brome (Bromus japonicus Thunb. ex Murr.) and candidate herbicides for its chemical control in the wheat fields of the North China Plain - Hengzhi Wang; Yunxia Duan; Cheng Yang; Yi Li; Mengmeng Hu; Xinyu Sun; Ping Yu; Tao Jin; Jinxin Wang; Weitang Liu (Crop Protection, 2026)

The crucial role of ground ice in slowing permafrost degradation - Guojie Hu; Zhe Sun; Lin Zhao; Deliang Chen; Defu Zou; Chien-Lu Ping; Wenxin Zhang; Yao Xiao; Guangyue Liu; Ren Li; Xiaodong Wu; Yifan Wu; et al. (Science Bulletin, 2026)

Retrieval of snow depth using synthetic aperture radar: past, current, and future - Zhen Li; Haiwei Qiao; Ping Zhang; Yanan Bai; Huadong Hu (Journal of Hydrology, 2026)

Sediment transport mechanisms in sediment-starved subaqueous deltas: insights from storm-induced gravity flows - Chunye Hu; Fan Zhang; Jin Li; Xiaolei Liu; Fei Xing; Renzhi Li; Hao Wu; Heyu Yu; Ya Ping Wang (Journal of Hydrology, 2026)

Partitioned N-TiO2–N-TiO2@SWCNT/PET composite fabric for industrial wastewater habitat reconstruction and potential cross-niche carbon sequestration - Jian Qiu; Yang Hu; Ying Chen; Shilong Li; Yudong Yuan; Bin Chen; Ping Shi; Jianfa Zhao; Wenheng Jing; Wei Zhou; Yuan Bai; Lele Cui; et al. (Journal of Environmental Chemical Engineering, 2026)

Impacts of rainfall runoff on algal community in a humid region reservoir riverine zone - Cunli Li; Miao Yang; Aiju You; Guangwei Zhu; Ping Zhang; Qiaoxi Zheng; Mengyuan Zhu; Linxing Tu; Hongqing Zhang; Lei Fu; Bin Wang; Jinwen Hu; et al. (Journal of Environmental Chemical Engineering, 2026)

Persistent site-scale warming associated with solar photovoltaic installations - Chao Zhang; Wanjiao Li; Junjie Tang; Zhe Shi; Fanyu Suo; Shujie Zhang; Yulu Ke; Hongxing Hu; Ning Ai; Yong Gao; Ping Gong; Guo Yu Qiu (Journal of Environmental Management, 2026)

Fe-CN activated peracetic acid system achieving hydroxyl radical-dominated degradation of organic pollutants - Wei Ren; Xiao-Wen Huang; Dongmei Hou; Zhuoyuan Li; Jingenqi Li; Denglong Chen; Yuehong Ma; Chongli Wu; Qian-Qian Tang; Yi Hu; Long-Shuai Zhang; Jian-Ping Zou (Journal of Environmental Chemical Engineering, 2026)

Gamma-gliadins and some non-gluten proteins critically influence the rheological behavior of wheat dough subjected to thermal treatment - Ping Li; Pai Peng; Xiaoyang Zou; Xinrui Ren; Xinyu Zhang; Wen Zhao; Xinyu Kou; Yu Liu; Xinzhong Hu; Xiaolong Wang (Food Hydrocolloids, 2026)

Synergistic optimization of yield, quality, and nitrogen use efficiency in indica rice: Influence of nitrogen management and C-N metabolism linkages - Hongjin Li; Tao Li; Jianghui Yu; Tianyu Du; Ping Zhang; Jingjing Cui; Zheshu Xu; Ying Zhu; Fangfu Xu; Qun Hu; Guodong Liu; Guangyan Li; et al. (Field Crops Research, 2026)

Dynamic response of a gentle near-fault bedrock-overburden slope after rainfall based on shaking table tests - Ping Hu; DeGou Cai; Hao Wen; HongYe Yan; JunKai Yao; TaiFeng Li (Bulletin of Engineering Geology and the Environment, 2026)

DMSN@AuNPs-enhanced QCM immunosensor array for non-invasive and highly sensitive detection of Cyfra21-1 in saliva - Xiaojing Zhang; Hongyang Guo; Li Sin Wong; Hangming Xiong; Liubing Kong; Guangqing Ren; Yanjie Hu; Yong Zhou; Shuaike Zheng; Li Zhang; K. Jimmy Hsia; Hao Wan; et al. (Analytica Chimica Acta, 2026)

Flexible Ultrasound Patch for Noninvasive, Targeted Anti-Angiogenic Therapy of Unstable Carotid Plaques - Jie Hu; Mingke Jiao; Chenchen Tang; Ping Liang; Jingwei Tang; Li Wan; Jimei Chen; Rui Li (Annals of Biomedical Engineering, 2026)

General Biogeographic Rules and Lineage‐Specific History Shape the Assembly of Asian Tropical Megadiversity - Hao Wu; Bing‐Yue Zhu; Jing Yang; Qiang Zhang; Zhen‐Ping Shi; Yan‐Jing Shi; Xiao‐Chen Zhao; Pei‐Yi Yang; Ke‐Xin Fan; Guang‐Shun Li; Si‐Qi Hu; Yee Wen Low; et al. (Journal of Biogeography, 2026)
Aim Tropical Asia's extraordinary plant diversity is thought to be intrinsically linked to its dynamic geological history. However, quantifying the precise evolutionary processes that assembled this diversity across the archipelago remains challenging. A recently proposed biogeographic framework classifies the functional roles of different regions as “radiators,” “incubators,” “corridors” or “accumulators,” offering a useful framework to analyse this complexity. Here, we aim to provide a critical, independent test of this framework using the megadiverse tree genus Syzygium as a model system. Syzygium originated on the Sahul Shelf, contrasting with the Indochinese origin of rattan palms used in the original framework validation. Location Tropical Asia, Pacific Islands and Africa. Methods We analysed the complete chloroplast genome of 200 species of the genus Syzygium and performed phylogenetic analysis to estimate divergence times, ancestral region reconstruction, and estimated diversification and extinction rates. We then analysed the relationship between regional area and the dispersal of species and examined speciation and dispersal patterns in relation to the geographical environment. Results Our comprehensive chloroplast phylogenomic analysis indicates rapid diversification of Syzygium commencing ~12 million years ago, coinciding with shelf collision. Biogeographic reconstructions indicate that while the framework's general principles hold – continental shelf act as “radiators” and isolated islands as “incubators” – the specific geographic roles vary depend on lineage history . Main Conclusions Our study validates the radiator‐incubator model as a general feature of tropical Asian evolution but refines it by demonstrating that historical contingency is key to understanding the assembly of Earth's richest biota. Tropical Asian plant diversity reflects a unique geological history of continental shelf collision and dynamic island geography, offering insights into biodiversity evolution in other geologically active regions worldwide, highlighting the importance of maintaining large, connected natural areas and dispersal corridors for preserving the evolutionary processes that generate Earth's botanical richness.

New perspectives on key bioactive molecules of lactic acid bacteria: integrating targeted screening, key gene exploration and functional evaluation - Shi Hu; Qi Wang; Jinfeng Wu; Hangjia Zhang; Jiaqi Yin; Lina Ding; Ping Li; Hang Xiao; Qing Gu; Jiarun Han (Critical Reviews in Food Science and Nutrition, 2026)

Raccoon dog parvovirus NS1 protein antagonizes type I interferon signaling by promoting selective autophagic degradation of IRF3 - Wen-yu Cao; Rui-qi Wang; Jin-yang Zheng; Ping Ma; Bo Hu; Cheng-qi Zhang; Ya-jie Sun; Jia-jia Liu; Ding-rui Guo; Zi-han Zhao; Xin Cao; Xue Bai; et al. (Veterinary Microbiology, 2026)

The overlooked role of nitrate in mediating electron transfer and enhancing reactive species generation in TiO2 photocatalytic water remediation - Zheng Hu; Jin Wu; Lingzhi Shen; Zili Lin; Zihong Xu; Zhenjun Xiao; Zheng Fang; Daguang Li; Ping Chen; Wenying Lv; Guoguang Liu (Process Safety and Environmental Protection, 2026)

Understanding public perceptions of cultural ecosystem services in urban coastal wetland ecological restoration areas: A social media-based large language model approach - Zirui Zhao; Zhiyuan Ma; Bin Chen; Ping Li; Weiwei Yu; Wenjia Hu; Dian Zhang; Jianji Liao (Journal of Environmental Management, 2026)

An innovative triple-channel probing strategy for ultrasensitive detection of quercetin in food matrices based on carbon dots - Ping Li; Zhen-quan Yang; Lixia Xiao; Xuechao Xu; Tianzu Guan; Wenyuan Zhou; Xiaowei Tang; Xiaojuan Gong; Qin Hu (Food Chemistry, 2026)

A refined middle-late Mississippian chronostratigraphic framework established through biostratigraphy and chemostratigraphy in South China: Implications for redefining the base of the Serpukhovian Stage - Chao Liu; Pedro Cózar; Ismael Coronado; Yuansheng Du; Axel Munnecke; Xin Li; Xia Hu; Meng Li; Weiqing Liu; Ping Wang (Earth-Science Reviews, 2026)

Electronic structure reconstruction and interface anchoring for high-performance direct regeneration of spent LiFePO4 materials - Yuyun Li; Yuan Ping; Fanbin Hu; Changjiang Li; Jinhua Shi; Haigang Dong; Qingfeng Liu; Yingjie Zhang; Qi Meng; Peng Dong (Chemical Engineering Journal, 2026)

Microscopic mechanisms of dissolved organic matter sequestration and transformation at the mineral-water interfaces during the formation and transformation of Fe Mn (hydr)oxides - Kai Cui; Libin Wu; Zihao Wu; Yue Yang; Shiwen Hu; Xiaoyuan Zhang; Zilong Zeng; Ping Chen; Li Wang; Zecong Ding; Hao Yi (Chemical Engineering Journal, 2026)

Coupled effects of straw return practices on soil microbial functional potential and agricultural productivity in Semi-Arid Region - Rui-Zhi Liu; Xiao-Ya Zhao; Li-Jie Wang; Xing Zhang; Shu‑Ping Hu; Ju‑Lin Gao; Xiao‑Fang Yu; Qinggeer Borjigin (Plant and Soil, 2026)

Nitrogen-fixing bacteria and arbuscular mycorrhizal fungi alleviated nitrogen limitation in halophytes and reduced soil salinity in salt-aggregating and salt-secreting plants - Zehao Zhang; Tian Li; Rui Hu; Zhanyong Fu; Yao Zhang; Jinzhao Ma; Ping Wang; Jingkuan Sun (Plant and Soil, 2026)

The Impact of Delay Time on Blasting Mining Efficiency: Insights from Simulations and Field Experiments - Tao Hu; Xiang-long Li; Jian-guo Wang; Chun-ping Wu; Shu-feng Liang; Bao-qian Huan (Applied Geophysics, 2026)

Effect of Density Ratio and Surface Tension on Vortex–Interface Interactions: A Numerical Study - Xiaobin Yang; Yiding Hu; Zhihan Li; Chenghan Wu; Ping Wei; Weige Liang; Shiyan Sun (Journal of Marine Science and Engineering, 2026)
In two-phase flow, the interaction between multi-scale vortex structures and interfaces (bubbles or free surfaces) triggers a range of complex physical phenomena. This study employs numerical simulations to investigate the interaction between a horizontal vortex and the interface separating two layers of immiscible fluids with different densities (e.g., water and air). The vortex is initialized as an internal motion within the heavier phase. We focus specifically on the impact of the phase density ratio and surface tension. Numerical simulations reveal that when the density ratio is near unity, interface rupture occurs only at high Weber numbers (We), where low surface tension enables the rupture of sharp interface points. Conversely, at high surface tension (low We), these sharp points stretch into thin liquid films, significantly increasing the surface area without causing breakage. As the density ratio increases, interface rupture at sharp points accelerates, even under high surface tension, leading to faster dissipation of the initial vortex. In high-We scenarios, an increased density ratio promotes the faster formation and greater intensity of new vortex layers at the interface. However, increasing surface tension enhances the vorticity of these layers but simultaneously slows their generation rate. The findings highlight the critical interplay between surface tension and density differences in vortex–interface interactions, with surface tension stabilizing the interface and density differences driving more intense vortex shedding and deformation. These insights offer valuable guidance for understanding two-phase flow behavior and improving the design of systems involving multiphase fluids.

Coupled tectonic-climatic-oceanographic dynamics drove the evolution of foraminiferal diversity in South China during the Middle to Late Mississippian - Chao Liu; Junjun Qi; Pedro Cózar; Ismael Coronado; Fei Li; Weiqing Liu; Meng Li; Ping Wang; Xin Li; Xia Hu; Song Jin (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Origin and forming mechanism of coking substance in ester aviation lubricating oil - Teng Chen; Huashuai Gao; Ping Qi; Shizhao Yang; Xin Xu; Jun Ma; Li Guo; Jingpei Cao; Jianqiang Hu (Fuel, 2026)

Study on the influencing factors of coaxial DBD plasma assisted coal combustion characteristics - Ping Li; Zhendong Cao; Haibo Hu; Deshan Wang; Haoyuan Song (Fuel, 2026)

Defect passivation with Pb for high-performance Sb2S3 solar cells via vapor transport deposition - Gan Huang; Xin-Yi Cai; Hu Li; Jin-Rui Cai; Ying-Sen Xia; Zhi-Ping Huang; Li-Mei Lin; Fu-Bao Gong; Shui-Yuan Chen; Gui-Lin Chen (Chemical Engineering Journal, 2026)

Mesoporous catechin nanocarriers potentiate curcumin to treat osteoarthritis via synergistic antioxidant and macrophage repolarization - Xinyu Zhang; Junyan Li; Ye Zhu; Huilin Hu; Ping Gong; Hui Xu; Ningli Guo; Quanzhou Wu; Chao Lou; Minghao Chao; Zhang Chen; Minjiang Chen; et al. (Chemical Engineering Journal, 2026)

Discovery of FLF-15 as a novel selective inhibitor of ADAM17 to prevent hepatocellular carcinoma metastasis - Qing Li; Dao-ping Wang; Ting Zhong; Ai-ling Ling-hu; Jia-lin Chen; Fang Luo; Feng Zhang; Ming-zhi Su; Ying Yang; Yan-hua Fan (Molecular Diversity, 2026)

Exceptional methylmercury bioaccumulation in rice grain from karst region with high geological background - Langfei Wei; Shaochen Yang; Ruolan Li; Rasheed Mohammed Abdul; Yanxin Hu; Haiyu Yan; Baolin Wang; Haiyan Hu; Ping Li (Applied Geochemistry, 2026)

Dual-functional alginate/polycaprolactone composite dressing for co-delivery of silver nanoparticles and PDGF-B plasmid to promote diabetic wound regeneration - I-Tsu Chyuan; Ping-Jyun Li; Chia-Wen Tsao; Wei-Wen Hu (Journal of Pharmaceutical Investigation, 2026)

Undescribed dihydro- β -agarofuran sesquiterpenoids from the roots of Tripterygium wilfordii - Ya-Lin Hu; Jia-Li Huang; Chong Wang; Wen-Jie Chen; Jing-Yi Huang; Yi-Ping Xie (Natural Product Research, 2026)

Stevia rebaudiana Bertoni root polysaccharide ameliorate high-fat-diet-induced atherosclerosis in ApoE-knock out mice: potential role of inflammation regulation - Chunyan Liu; Guangdong Hu; Haoyu Zhang; Ping Wu; Fengge Wang; Ji Li; Guodong Wang; Taili Shao (Natural Product Research, 2026)

Polyprenylated xanthones with potential anti-inflammatory and anti-HIV effects from the stems and leaves of Cratoxylum cochinchinense (Lour.) Blume - Yong Zhang; You-Di Rao; Jing-Su Yu; Jia-Yi Hu; Wen-Hui Hu; Shu-Ri Li; Hui Yang; Yan-Ping Liu; Yan-Hui Fu (Natural Product Research, 2026)

Interspecific interactions increase soil aggregate stability through altered root traits in long-term legume/maize intercropping - Xiao-Yang Duan; Surigaoge Surigaoge; Yu-He Du; Dai-Han Fu; Hao Yang; Xin Yang; Huai-Yin Ma; Hu Zhou; Peter Christie; Dario Fornara; Wei-Ping Zhang; Long Li (Soil and Tillage Research, 2026)

A fluorescent probe based solid-state fluorophore for the detection of N2H4 and its application in environmental samples - Cong-Ping Cao; Qian Song; Chu-Yu-Hui Peng; Shuang-Xian Li; Guo-Jiang Mao; Juan Ouyang; Liufang Hu; Yongfei Li; Chun-Yan Li (Journal of Hazardous Materials, 2026)

Organ-level translocation and tissue-specific accumulation of micro- and nanoplastics in wild birds - Mengzhu Wang; Shirui Wang; Pinxi Zhou; Hongcheng Shan; Shangmingyu Zhang; Zhixiong Yang; Yibo Wang; Zhengrui Hu; Jiayu Zhang; Yi Wu; Xinyu Lu; Zhiqiang Li; et al. (Journal of Hazardous Materials, 2026)

Urbanization increases the impact of micropollutants on riverine planktonic food web - Bob Adyari; Lanping Zhang; Francisco J.A. Nascimento; Dandan Izabel-Shen; Yiqing Zhang; Meixian Cao; Jianjun Wang; Hongjun Li; Qian Sun; Chang-Ping Yu; Anyi Hu (Journal of Hazardous Materials, 2026)

Partial consistency of net primary productivity and water-carbon use efficiency in response to climate change among three plantations - Chongfan Guan; ShouJia Sun; Jinsong Zhang; Xiaochuang Hu; Zijing Li; Jinfeng Cai; Ping Meng (Ecological Modelling, 2026)

Mild magnetic hyperthermia-enhanced perfusion chemotherapy against bladder cancer - Han Jiang; Siqian Li; Hanyong Dong; Jing Wang; Ping Hu; Jianlin Shi (Chemical Engineering Journal, 2026)

Observation of out-of-plane ferroelectricity in ∼5 nm ultrathin SrBi2Ta2O9 films for memristors and synapses application - Li-Ping Tan; Xue-Feng Hu; A-Long Li; Wei-Wei Qing; Ming Zhou; De-Bao Yu; Guo-Peng Zhang; Qing-Qing Mu; Zi-Long Wang; Xiao-Liang Wang; Ya-Li Bi; Wei Zhang (Chemical Engineering Journal, 2026)

Ti3C2-Cl-Bi12O17Cl2/Bi12O17Cl2 Mott-Schottky heterojunction with mixed noncovalent/covalent type to boost ultra-sensitive photoelectrochemical sensing of ciprofloxacin - Chu-Chu Hu; Qi-E Zhang; Shao-Peng Shi; Guo-Qing Zhao; Yan-Sha Gao; Ping Liu; Xun-Kuan Ye; Yan Pan; Hui-Qing Lv; Li-Min Lu (Chemical Engineering Journal, 2026)

Deciphering mechanisms of stress-induced metabolic shifts in Corynebacterium glutamicum by transcriptomics and contextualised modelling - Xiaomeng Ni; Ning Gao; Wenjing Hu; Xuan Guo; Jiao Liu; Jiuzhou Chen; Ningyun Cai; Xiaojia Zhao; Jibin Sun; Yu Li; Yan Zhu; Ping Zheng (Bioresource Technology, 2026)

Mapping the spatial variability of hydrogen and oxygen isotopic compositions in Chinese lake water: Patterns and drivers - Hu Liu; Ping Zhang; Huanye Wang; Zhoufeng Wang; Zhonghui Liu; Meng Xing; Zheng Wang; Yixuan Li; Yunning Cao; Xiangzhong Li; Weiguo Liu (Science China Earth Sciences, 2026)

Retraction Note to: Downregulation of the Long Non-Coding RNA Meg3 Promotes Angiogenesis After Ischemic Brain Injury by Activating Notch Signaling - Juan Liu; Qing Li; Kun-shan Zhang; Bin Hu; Xin Niu; Shu-min Zhou; Si-guang Li; Yu-ping Luo; Yang Wang; Zhi-feng Deng (Molecular Neurobiology, 2026)

Association between low daily average temperature and epilepsy outpatient visits: a hospital-based study in Chongqing, China - Pei Jiang; Jing Yang; Yumeng Zhou; Jinchi Gu; Fengxia Liu; Chunlei Tan; Yao Cheng; Hao Wang; Li Mao; Peng Hu; Ping Chen; Ding Liu; et al. (International Journal of Biometeorology, 2026)

Tropical tree-mycorrhizal types show divergent phosphorus adaptive strategies after 12-year simulated acid rain - Yuanliu Hu; Ji Chen; Dafeng Hui; Ying-Ping Wang; Xiaolin Huang; Minghui Hu; Yiren Zhu; Yonghui Li; Jianling Li; Deqiang Zhang; Qi Deng (Soil Biology and Biochemistry, 2025)

Tree-mycorrhizal types differ in their biomass response to nitrogen addition - Guoyin Chen; Yuanliu Hu; Jianping Wu; Richard P. Phillips; Jianyang Xia; Ying-Ping Wang; Dafeng Hui; Jianling Li; Xianyu Yao; Qi Deng (Soil Biology and Biochemistry, 2025)

Recovery of V2O5 from spent catalysts for NH3 and humidity sensors - Yan Li; Ping Hu; Miaomiao Liu; Bo Ran; Yuqing Zhu; Junxi Cheng; Jun Sun; Zhaofeng Wu (Journal of Environmental Chemical Engineering, 2025)

The probiotic characteristics and antimicrobial mechanisms of Lactiplantibacillus plantarum ZFM55 - Shiying Wu; Jiayi Fan; Yi Xu; Yuenuo Luo; Luying Xie; Mingyang Hu; Yongqiang Chen; Fangtong Wei; Yuqing Lou; Ping Li; Qing Gu (Food Bioscience, 2025)

Design of Ni-MOF@biochar heterostructures via ligand-induced distortion for highly selective N2H4 sensing - Bo Ran; Ping Hu; Jun Sun; Jialu Fang; Yan Li; Qihua Sun; Zhizhong Zhang; Zhaofeng Wu; Haiming Duan (Chemical Engineering Journal, 2025)

A high safety composite separator for powerful battery with ultra-long lifespan over 14,000 cycles at 10C - Ke Fang; Yan-yan Chen; Jian-wei Ji; Tian-kun Gao; Mei-qi Hu; Lian-li Zou; Ying Liu; Li-ping Zhou; Ming-quan Liu; Mao-xiang Jing (Chemical Engineering Journal, 2025)

Natural compound rhein-based bimetallic nanosheets to induce ferroptosis and activate STING pathway for enhanced cancer immunotherapy - Chang Li; Tiancheng Xie; Xilong Mei; Yu Wen; Mi Huang; Hu Guo; Ping Lu; Xiaoxin Yang; Jun Liu (Chemical Engineering Journal, 2025)

Recent developments in polysaccharide-based conductive hydrogels: A review and perspective - Lijun Liu; Yanbo Wang; Xianwei Li; Ping Li; Yizhi Jin; Hongli Yu; Meixing Yan; Yuan Hu (Carbohydrate Polymers, 2025)

Skeletal and sedimentary structures in yardang caverns in the Mars analog, Qaidam Basin: origin and implication - Qi-Tao Hu; Wen-Ping Liu; Yu-Lu Xue; Qi-Zhi Yao; Sheng-Quan Fu; Yi-Liang Li; Gen-Tao Zhou (CATENA, 2025)

A new 2-arylbenzofuran derivative and other constituents from Smilax china L. and their chemotaxonomic significance - Li-Juan Hu; Xian-Sheng Ye; Kuan Lin; Jie Gao; De-Sen Yang; Guo-Ping Gan; Xi-Ji Shu; Wei Liu; You-Hua Yang (Biochemical Systematics and Ecology, 2025)

Lactiplantibacillus plantarum ZJ316 Alleviates Helicobacter pylori-Induced Intestinal Inflammation by Sustaining Intestinal Homeostasis - Shiying Wu; Fangtong Wei; Yongqiang Chen; Ziqi Chen; Yuenuo Luo; Jiayi Fan; Yang Xu; Mingyang Hu; Ping Li; Qing Gu (Probiotics and Antimicrobial Proteins, 2025)

Synergistic effects and mechanism of recombinant viral vector-mediated STAT1 overexpression and STAT3 silencing on glioma U251 apoptosis - Xin-Long Hu; Hong Li; Guo-Dong Zhang; Chao Lin; Ping Huang; Xiu-Feng Chen; Fang Wan; Chang-Wu Dou; Hai-Tao Ju (Molecular Biology Reports, 2025)

Prognostic and therapeutic implications related to glycosylation profiles of cancer-associated fibroblasts in colorectal cancer: insights from single-cell and bulk transcriptomics - Keji Chen; Huixia Huang; Zijuan Hu; Yifei Zhu; Yanxi Yao; Yaxian Wang; Jiayu Chen; Yuxue Li; Dawei Li; Ping Wei (Functional & Integrative Genomics, 2025)

Multigenerational toxic effects of Butylparaben and Hexylparaben on Moina macrocopa - Xue Lei Hu; Ming Chen; Jin Lan Peng; He Ping Huang; Sui Jun Cai; Jin Ling Liu; Yun Hui Li; Lu Wang (Ecotoxicology, 2025)

CPT1A facilitated ferroptosis by forming feedback loop with Nrf2 via PI3K/AKT pathway in colorectal cancer - Xiao-huan Li; Feng Lv; Si-qi Li; Hao-wei Deng; Li-ping Tang; Ke-zhi Li; Li-ye Xie; Bang-li Hu; Shu-fang Ning (Apoptosis, 2025)

Critical processes controlling the formation of visible gold in the giant Jiaodong gold province: Constraints from microtextural and geochemical analyses by SEM, TOF–SIMS, and LA-(MC)-ICP-MS - Hong Wang; Ting-Guang Lan; Lang-Ye Zhao; Hong-Rui Fan; Zhan-Ping Li; Huan-Long Hu; Zi-Qi Xu; Hong-Wei Peng; Lei Shu (Acta Geochimica, 2025)

Plastispheres as unique niches for promoting turnover of dissolved organic matter in aquatic environments - Yan-Jun Liu; Zheng-Hao Li; Yan-Yun Hu; Jia-Heng Zhao; Li Yuan; Guo-Ping Sheng (Water Research, 2025)

Overexpression of G protein-coupled receptors (GPCRs) contributing to lambda-cyhalothrin resistance in Cydia pomonella - Yu-Xi Liu; Chao Hu; Zi-Nan Xia; Yan Wang; Yu-Ting Li; Ping Gao; Yun-Tong Lv; Jia Li; Xue-Qing Yang (Pesticide Biochemistry and Physiology, 2025)

The pleiotropic odorant binding protein CaspOBP12 involved in perception of Ceutorhynchus asper for plant volatiles and pesticides - Xinghao Li; Fangjing Hu; Rufan Li; Danhao Peng; Ping Gao; Fuqiang Rao; Yonghong Li; Deguang Liu (Pesticide Biochemistry and Physiology, 2025)

Mixotrophic Chlorella pyrenoidosa biofilm with enhanced biomass production, microalgal activity, and nutrient removal from nutrient-rich wastewater - Xiongwei Wu; Cong Jin; Chiqian Zhang; Ping Li; Jim Junhui Huang; Jing Wu; Jinhua Wu; Zhiqiang Hu (Journal of Environmental Sciences, 2025)

Boosting 2,5-furandicarboxylic acid production from crude 5-hydroxymethylfurfural over MgMn-mixed spinel supported Ru catalysts - Yimeng Guo; Xiaoying Tian; Xixi Liu; Hang Lv; Ping Hu; Hui Li; Fengyi Lu; Changwei Hu; Liangfang Zhu (Fuel, 2025)

Androgen induces 3′UTR shortening of de novo lipogenesis genes by alternative polyadenylation in prostate cancer cells - Wei-Jie Sun; Fei Liang; Hui Zhao; Yun-Mei Wang; Zhong-Yin Zhou; Hui Xu; Hang Liu; Dong Tang; An-Long Xu; Yong-Gui Fu; Xi Li; Jun Ouyang; et al. (Science China Life Sciences, 2025)
Alternative polyadenylation (APA) is a pervasive mechanism that is emerging as a formidable player in post-transcriptional regulation. The transcriptional landscape can be altered via APA in response to various stimulating factors. Using the PacBio single-molecule long-read sequencing method, we present for the first time the 3′UTR landscape and reveal a global increase of APA events in prostate cancer (PCa) LNCaP cells in response to androgen dihydrotestosterone (DHT), a critical regulator of PCa progression. With evidence from differential gene expression analyses of Illumina RNA-sequencing data, we demonstrated that genes with DHT-induced changes in both expression and APA were enriched in lipid metabolism. These genes predominantly supported de novo fatty acid synthesis, such as FASN and ACSL3 . Furthermore, we showed that an isoform switch to the proximal poly(A) site of these genes depended on the androgen receptor, and the expression of cancer-associated genes was upregulated by the escape of miRNA-regulated repression machinery. To address the role of key gene shortening in PCa, we prepared 22RV1-FS cells missing the distal poly(A) signal of FASN in the AR + PCa cell line 22RV1 using CRISPR/Cas9 technology. As expected, the edited 22RV1-FS cells overexpressed FASN mRNA and protein and were inclined to cell proliferation in vitro and tumorigenesis in vivo . Interestingly, we found that FASN transcripts with a shortened 3′UTR were significantly increased in advanced PCa and castration-resistant prostate cancer compared with benign prostate hyperplasia, suggesting a possible association between usage of the proximal poly(A) site and disease progression. Therefore, our study highlights the importance of the APA mechanism in response to DHT stimulation in PCa cells and provides a novel regulatory mechanism through which DHT-induced APA causes altered expression of de novo lipogenesis genes, with a possible association with the progression of PCa.

Retraction Note: Fluoxetine is Neuroprotective in Early Brain Injury via its Anti-inflammatory and Anti-apoptotic Effects in a Rat Experimental Subarachnoid Hemorrhage Model - Hui-Min Hu; Bin Li; Xiao-Dong Wang; Yun-Shan Guo; Hua Hui; Hai-Ping Zhang; Biao Wang; Da-Geng Huang; Ding-Jun Hao (Neuroscience Bulletin, 2025)

The dietary supplementation with probiotic Bacillus cereus G1-11 improved the growth parameters, immune performances, intestinal histomorphology, and disease resistance of hybrid grouper (Epinephelus fuscoguttatus ♀ × Epinephelus lanceolatus ♂) - Ming-Qing Zhang; Zhong-Xuan Zhong; Qian-Ping Du; Wen Li; Ya-Ting Zhu; Guang-Ting Xie; Feng-Ying Yan; Jin-Lin Yang; Shui-Sheng Li; Hu Shu (Animal Feed Science and Technology, 2025)

CsAHL20 negatively regulates epi-catechins biosynthesis under drought stress in Camellia sinensis - Yu Chen; Mingyuan Luo; Ping Li; Qi Zhao; Luo Chao; Yujie Jiao; Shiyu Tian; Xingyu Tian; Shenyuan Ye; Zhenkedai Yuan; Yilan Hu; Yongqing Bai; et al. (Plant Science, 2025)

Analysis of atmospheric pollutant characteristics and regional transport in coastal area along the East China Sea - Yangzhou Wu; Dantong Liu; Honghui Xu; Meng Shan; Siyuan Li; Ping Tian; Kang Hu; Junfeng Wang (Journal of Environmental Sciences, 2025)

Lipid profiles and microstructure of alpine Holstein milk: Comparison with common Holstein milk - Xinying Hu; Qingyun Wang; Shuai Wang; Xinyi Cheng; Ping Qin; Jingwei Cui; Li Wang; Wei Wei; Xingguo Wang (International Dairy Journal, 2025)

Unraveling the absorption properties and driving mechanisms of atmospheric brown carbon in coastal air masses - Siyuan Li; Dantong Liu; Yangzhou Wu; Kang Hu; Shitong Zhao; Xiaotong Jiang; Ping Tian; Bin Xu (Environmental Pollution, 2025)

Cold crystallization-enabled permanent shape transformation in 4D-printed PLA/TPU composites for personalized wearable devices - Chuanru Zheng; Xi Li; Juan Tan; Anna Tan; Xiuchen Li; Hailiang Ni; Wenhao Yu; Yuefeng Bai; Ping Hu; Wei Min Huang; Hongmei Chen (Chemical Engineering Journal, 2025)

Targeted gene therapy for intracranial aneurysm using SOX17-CRISPRa - Dujie Xie; Yi Yuan; Panyao Long; Juan Huang; Mi Jiang; Yongzhong Tang; Yuanqiang Luo; Cancan Zhang; Ping Zheng; Liang Yang; Yiwei Chen; Xiaobo Li; et al. (Chemical Engineering Journal, 2025)

Bacterial outer membrane vesicles encapsulated cationic polymer with STING agonist as nanovaccines for enhanced immunotherapy - Xiao-Li Tian; Ping Chen; Yue Hu; Lan Zhang; Jin Li; Ji Zhang (Chemical Engineering Journal, 2025)

The role of evaporites in Kiruna-type iron oxide-apatite deposits in the Northern Norrbotten region, Sweden: Evidence from in situ halogen analyses of scapolite - Li-Ping Zeng; Carl Spandler; Ying-Ying Liu; Johannes Hammerli; Wang Liao; Hao Hu; Sanna Olsson; De-Xian Zhang; Tao He; Jian-Wei Li; Xin-Fu Zhao (Chemical Geology, 2025)

Lactiplantibacillus plantarum RS20D Alleviates Male Reproductive Toxicity Induced by Pubertal Exposure to Di-n-butyl Phthalate and Mono-n-butyl Phthalate - Yuan-ting Zhu; Xing-jie Wang; Shu-liang Liu; Jing-hui Lai; Jian-long Li; Qin Li; Kai-di Hu; Ai-ping Liu; Yong Yang; Li He; Shu-juan Chen; Xiao-lin Ao; et al. (Probiotics and Antimicrobial Proteins, 2025)

Revealing the occurrence characteristics, interaction mechanisms, and health risk of phthalates in agricultural soil of arid regions across Northwest China - Guo-dong Kang; Peng Lei; Lei-lei Lu; Ning Wang; Meng-jiao Li; Liang-liang Liu; Rui-yun Sun; Sheng-hu Zhang; Yan-hua Liu; Ping Wu (Environmental Monitoring and Assessment, 2025)

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

Links of abrupt climate events in the eastern Hexi Corridor to Atlantic meridional overturning circulation changes during the last glacial: Magnetoclimatological evidence of the Shagou loess record - Mei Sheng; Shiyu Yi; Xisheng Wang; Zongyao Li; Ping Sun; Yueyue Xin; Ke Hu; Zhenyu Yang (Global and Planetary Change, 2025)

A three-dimensional model of two-phase flow to a horizontal well in dual-porosity media - Jie Hu; Ping Tan; Chen Sheng Zhang; He Li; Shun Jie Sun (Computers and Geotechnics, 2025)

Internal encapsulation for enhancing perovskite solar cell stability based on moisture-triggered in situ polymerization - Jingwei Zhu; Jianting Huang; Ping Hu; Wei Yue; Mingdeng Wei; Ying Zhang; Yafeng Li (Chemical Engineering Journal, 2025)

Nanoparticles co-delivering double-stranded RNA and insecticide enhance control efficacy and overcome pest resistance - Chao Hu; Chang Yu; Jiaqing Li; Yuxi Liu; Qinghong Zeng; Hu Wan; Shun He; Yuting Li; Ping Gao; Yuntong Lv; Kunyan Zhu; Subba Reddy Palli; et al. (Chemical Engineering Journal, 2025)

Permeability and microstructure evolution of loess-paleosol sequence: analysis of prediction model based on deposition time - Zhiyan Zhao; Xiaokun Hou; Wei Shen; Mengmeng Zhang; Jianchao Chen; Ping Li; Tonglu Li; Xiangyang Hu (CATENA, 2025)

Genome-wide Identification of the MTP Gene Family in Cotton and Expression Analysis Under Multiple Metal Stresses - Yong Yang; Wenjie Lai; Ping Li; Shihan Zhou; Yutong Wu; Yuanhao Ding; Haiyan Hu (Plant Molecular Biology Reporter, 2025)

Mycorrhizal Network and Symbiotic N‐Fixer Jointly Enhance the Interplant Nitrogen Sharing - Yuxuan Gao; Yuntao Wu; Pengfei Chang; Ping Li; Shuijin Hu; Lingli Liu (Ecology Letters, 2025)
Symbioses with mycorrhizal fungi and nitrogen‐fixing bacteria (NFB) enhance nitrogen (N) acquisition in host plants and may promote N transfer to neighbouring plants through mycorrhizal networks (MN). Nevertheless, the extent and mechanisms of this transfer remain unclear. On the basis of a synthesis of 15 N labeling studies, we show that MN and NFB synergistically enhanced interplant N sharing. In the presence of MN, N transfer from N‐fixing donors to non‐N‐fixing receivers increased by an average of 9.7‐fold, accounting for 5.61% of the total N in receiver plants. Moreover, greater amounts of N were transferred from N‐fixing plants towards their phylogenetically distant plants. Source‐sink gradients driven by differences in N content between neighbouring plants further promoted N transfer. Together, our findings highlight the ecological significance of an expanded MN framework in explaining interplant N sharing and provide new insights into how symbiotic guild interactions promote species coexistence and biodiversity maintenance.

Discovery of indole-carbohydrazide hybrids as novel broad-spectrum fungicidal lead compound though membrane-targeting mechanism - Ying Wu; Li-Hui Shao; Xian-Qun Hu; Yu Long; Yuan-Yuan Wu; Pei-Bu Yu; Ai-Ping Yan; Long-Fei Li; Xiang Zhou; Song Yang (Molecular Diversity, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

A symbiotic bacterium regulates the detoxification metabolism of deltamethrin in Aedes albopictus - Si-jia Deng; Lei Tu; Lin Li; Ju-ping Hu; Ju-lin Li; Jian-xia Tang; Mei-chun Zhang; Guo-ding Zhu; Jun Cao (Pesticide Biochemistry and Physiology, 2025)

BarleyOmics: A comprehensive multi-omics database of barley - Junheng Zhao; Shanggeng Xie; Chenyang Zhang; Zengjie Hu; Xiangqian Lu; Nannan Zheng; Yujie Fu; Jie Yao; Ping Zhou; Danyin Huang; Zhizhong Zhang; Mengdi Li; et al. (Molecular Plant, 2025)

Highly selective conversion of NO to NO3—through radical modulation over UiO-66–67-NH2 S-scheme heterojunction - Ping Tan; Zhuo Wang; Zhen Mao; Riming Hu; Jiayuan Yu; Yuhan Li (Journal of Hazardous Materials, 2025)

How did the Hukou Waterfall of the Yellow River form? - Hao Liang; Ke Zhang; Jianguo Xiong; Zhongyun Li; Xiu Hu; Ying Xu; Ping Huang; Zhigang Li; Yipeng Zhang; Gege Hui; Kang Liu; Weitao Wang; et al. (Geomorphology, 2025)

Agronomic characteristics, objective quantitative, metabolome and transcriptome analysis reveal the influence of fertilization treatments on fresh leaf characteristics and finished tea quality - Liyue Yang; Xizhe Zhu; Ziming Yu; Bicheng Hu; Ping Liu; Fenglan Zhang; Ming Chen; Jinjin Wang; Youyi Huang; Haibo Yuan; Yeyun Li; Jinjie Hua (Food Chemistry, 2025)

Tracing anthropogenic imprints on polybrominated and polychlorinated dibenzo-p-dioxin/furans in soil: A comprehensive field study in an urban agglomeration of China - Ming-Yang Liu; Hui-Ru Li; Ping-An Peng; Ai-Min Song; Yang Li; Fei-Xiang Xie; Yong-Hong Zhang; Jian-Fang Hu (Environmental Research, 2025)

Complete genome analysis of a novel phenui-like virus in Morus alba - Hanze Zheng; Yangwei Gao; Xiaodi Hu; Zhongtian Xu; Jian-Ping Chen; Yiyuan Li (Archives of Virology, 2025)

Deep reinforcement learning algorithm incorporating problem characteristics for dynamic multi-objective permutation flow-shop scheduling problem - Yuan-Yuan Yang; Bin Qian; Rong Hu; Zuocheng Li; Zi-Qi Zhang; Huai-Ping Jin; Jian-Bo Yang (Swarm and Evolutionary Computation, 2025)

Environment disturbances influence bacterial diversity, structure and co-occurrence network in the Digitaria sanguinalis rhizosphere - Yiming Dai; Ye Cui; Qingchen Xiao; Meiling Ping; Yiming Zhang; Shiguang Hu; Hao Chen; Xiaoyu Li; Jin Chen (Physiological and Molecular Plant Pathology, 2025)

Arsenic mobilization by Bathyarchaeia in subsurface sediments at the Jianghan Plain, China - Zhou Jiang; Wenjie Fang; Yongguang Jiang; Yidan Hu; Yiran Dong; Ping Li; Liang Shi (Journal of Hazardous Materials, 2025)

Key aspects of karst development and tunnel construction countermeasures: a case study of the Ehan expressway - Fangtao Li; Zhiping Hu; Yonghui Zhang; Xuexu An; Huaming Li; Lejun Cai; Ping Huang (Bulletin of Engineering Geology and the Environment, 2025)

Statins could improve short-term prognosis in patients with traumatic brain injury: a propensity-matched cohort study - Ping Li; Qiang Liu; Zhuo Zhang; Hu Nie (Inflammopharmacology, 2025)

STING-activating pyroptotic nanoparticles for in situ pancreatic cancer vaccination and immunotherapy - Shiyi Shao; Xiaohong Chen; Yuxuan Chen; Meng Wang; Junmin Huang; Jianwei Wang; Xiazhen Yu; Xinya Li; Yao Zhang; Yuan Ping; Qida Hu; Tingbo Liang (Science Bulletin, 2025)

Corrigendum to “Trace-elements driven up-regulation of secreted proteases expression in the human-pathogenic fungus Trichophyton rubrum” [J. Trace Elem. Med. Biol. 87 (2025) 127580] - Oliver Blechert; Shanyu Lan; Shuzhen Xiong; Yuning Zou; Peicong Li; Jiewei Hu; Jiayuan Li; Ping Zhan (Journal of Trace Elements in Medicine and Biology, 2025)

Comparative mechanisms of PDS-activated antibiotic remediation in groundwater via controlled-release materials with different mesoporous catalysts - Ting Wang; Jing-le Chen; Rui Huang; Hua-li Chen; Cheng Hu; Gang Chen; Kou-ping Chen; Ji-chun Wu (Journal of Environmental Management, 2025)

Identification of volatile indicators for quality deterioration of Yu-Shiang Shredded pork after reheating based on HS-GC-IMS and intelligent sensory evaluation - Chunyuan Ping; Honglian Hu; Jicai Bi; Xiang Li; Yuwen Yi; Mingfeng Qiao (International Journal of Gastronomy and Food Science, 2025)

Ripening-stage variations in small metabolites across six banana cultivars: A metabolomic perspective - Huijun Gao; Ping Liu; Weidi He; Fangcheng Bi; Chunhua Hu; Guiming Deng; Tongxin Dou; Qiaosong Yang; Chunyu Li; Ganjun Yi; Ou Sheng; Tao Dong (Food Chemistry, 2025)

In vitro and in vivo antibacterial effects of indole-3-lactic acid against Salmonella enterica serovar Typhimurium - Qingqing Zhou; Yajun Yu; Zuorui Xie; Yingying Zhou; Yanan Li; Ping Li; Jiangning Hu; Qing Gu (Food Bioscience, 2025)

Terpene-conjugated curcumin analogs alleviated alcoholic liver injury in rats through mitigation of intestinal barrier abnormalities - Shuaihu Tao; Ruanping Song; Ziyu Wang; Wenjing Xie; Siyuan Xiao; Yangyang Liao; Xinjie Zhang; Qiongdan Hu; Xinxing Tang; Jingyuan Huang; Wan Liao; Hongtao Xiao; et al. (Food Bioscience, 2025)

Transgenerational thyroid hormone disruption in zebrafish induced by environmentally relevant concentrations of triclosan - Ping Ding; Jiayi Zhang; Xin Li; Pengcheng Ma; Guocheng Hu; Lijuan Zhang; Yunjiang Yu (Environmental Pollution, 2025)

Energy transfer strategy inspired by TADF molecules for efficient and UV-Robust perovskite solar cells - Ping Hu; Liujiang Zhang; Ruoxin Yang; Rongen Guo; Xingyu Gao; Mingdeng Wei; Yafeng Li (Chemical Engineering Journal, 2025)

Discovery of potent MD2 inhibitors by hierarchical virtual screening strategy and bioactivity evaluation - Lili Yang; Jialu Liu; Lei Di; Siming Tang; Ping Hu; Fang Wang; Zeng Li (Chemico-Biological Interactions, 2025)

Chromosome-level genome assembly of a high-yield Chinese soybean variety Mengdou1137 unlocks genetic potential of disease and lodging resistance - Rujian Sun; Bincheng Sun; Zihao Zheng; Qi Zhang; Xingguo Hu; Rongqi Guo; Lei Feng; Shen Chai; Jingshun Wang; Ping Qiu; Ping Yu; Ying Liu; et al. (Theoretical and Applied Genetics, 2025)

Olaparib reverses prostate cancer resistance to Rapamycin by promoting macrophage polarization towards the M1 phenotype - Kai Ye; Gang Shi; Jian Xu; Kunyan Qiao; Qinghai Dai; Zhixiao Huo; Yu Cao; Wei Liu; Yue Hu; Lihua Yan; Yu Zhu; Ping Li; et al. (Molecular and Cellular Biochemistry, 2025)

Health risk assessment of heavy metal emissions from on-road vehicles in a metropolitan area in southeastern China - Qi-Yu Miao; Zhe-Nan Wen; Shui-Ping Wu; Jun Hu; Li-Xiong He; Bing-Qi Jiang; Yi-Jing Liu (Journal of Atmospheric Chemistry, 2025)

Three-Dimensional Shallow P-wave Velocity Distribution in the Source Area of the 2021 MS6.0 Luxian Earthquake from Dense Array Seismic Imaging - Jian-xun Yang; Qi-yan Yang; Da-hu Li; Yong-ming Lu; Ping-ping Wu; Hui-li Guo; Ning-bo Jiang; Mi Gao; Heng Pan (Applied Geophysics, 2025)

Aged microplastics-induced growth inhibition via DNA damage, GH/IGF-1 and HPT axes disruption in zebrafish larvae - Qing Ge; Tong Zheng; Ping Ding; Zhenyuan Li; Xihua Lin; Xintong Li; Miao He; Guocheng Hu (Science of The Total Environment, 2025)

The transcription factor CsPAT1 from tea plant (Camellia sinensis) is involved in drought tolerance by modulating phenylpropanoid biosynthesis - Jing-Wen Li; Ping Zhou; Zhi-Hang Hu; Ai-Sheng Xiong; Xing-Hui Li; Xuan Chen; Jing Zhuang (Journal of Plant Physiology, 2025)

Aggregation behavior of photoaging nanoplastics in artificial sweat solutions - Yanlin Yang; Haoran Song; Yan Cao; Jiao Li; Jie Li; Xiangfen Cui; Xuewei Hu; Anjum Mahfuza; Ping Ning; Linfeng Zhang; Qun Zhao; Senlin Tian (Journal of Hazardous Materials, 2025)

Development of a shear strengthening conductive hydrogel for impact protection and distress signal emission - Juan Tan; Xi Li; Chuan Ru Zheng; Anna Tan; Xiu Chen Li; Hai Liang Ni; Wen Hao Yu; Yue Feng Bai; Ping Hu; Hong Mei Chen (Chemical Engineering Journal, 2025)

A Golden2-like transcription factor regulates Brassica napus seed vigor after artificial aging - Xiaoke Ping; Mei Yan; Jia Wang; Qianjun Ye; Taiyuan Zhang; Xiaojie Hu; Sheng Chen; Jiana Li; Liezhao Liu (Theoretical and Applied Genetics, 2025)

Unraveling Spatiotemporal Metabolic Perturbation of Amino Acids Associated with Ischemia–Reperfusion Injury by MALDI MS Imaging - Kening Li; Yingying Gong; Wenqiao Chang; Jieping Yan; Ying Hu; Zongfu Pan; Ping Huang (Molecular Neurobiology, 2025)

Deepened snow promotes temporal stability of semi‐arid grasslands via improving water acquisition‐and‐use strategies - Ping Li; Zhou Jia; Yuntao Wu; Pengfei Chang; Nairsag Jalaid; Lulu Guo; Shengnan Pan; Shaopeng Wang; Lin Jiang; Shuijin Hu; Lingli Liu (Ecology, 2025)
Precipitation fluctuations strongly influence biomass production and its stability of terrestrial ecosystems. However, our understanding of the extent to which plant communities adjust their water‐use strategies in response to non‐growing season precipitation variations remains limited. Our 5‐year snow manipulation experiment in a semi‐arid grassland, complemented with paired stable isotope measurements of δ 18 O and δ 13 C for all species within the community, demonstrated that the impact of snowmelt on plant physiological activities extended into the peak growing season. Deepened snow enhanced ecosystem water use efficiency (WUE), biomass production, and its temporal stability. We further examined whether the observed increase in biomass stability was associated with the functional diversity of plant water‐use strategies. Plant cellulose Δ 18 O cell analysis revealed that both community‐weighted mean and functional dispersion of stomatal conductance were positively associated with biomass production and its stability. The δ 13 C results further indicated that even with increased stomatal conductance, grasses were able to maintain their high intrinsic WUE by increasing photosynthesis more than transpiration. This resulted in higher biomass and greater dominance of high‐WUE functional groups under deepened snow. In addition, we also found that deepened snow increased root biomass, particularly in the 0‐ to 5‐cm and 20‐ to 40‐cm soil layers. This increase in root biomass enhanced the uptake of snowmelt from both surface and deep soil layers, further contributing to community stability. Overall, our study demonstrates that plant communities can optimize water acquisition and utilization, thereby enhancing the stability of biomass production through coordinated changes in plant physiology, species reordering, and root distribution under altered snow regimes.

Four new constituents from the fruits of Cyclocodon lancifolius (Roxburgh) Kurz - Meng-Jie Ma; Wei Wu; Bei Tian; Li-Ping Shen; Tong Wu; Chun-Yue Huang; Xu-Dong Mao; Xiao Hu (Natural Product Research, 2025)

ABA-INSENSITIVE 4 promotes nicotine biosynthesis under high light in Nicotiana attenuata - Bo Lei; Yan Mao; Huina Zhao; Jing Yu; Bing Wang; Ping Li; Xiangyang Hu (Plant Science, 2025)

Restoring turbid eutrophic shallow lakes to a clear-water state by combined biomanipulation and chemical treatment: A 4-hectare in-situ experiment in subtropical China - Bo Li; Deyuan Chen; Jichong Lu; Suxia Liu; Jiale Wu; Lei Gan; Xiaoqin Yang; Xiaolin He; Hu He; Jinlei Yu; Ping Zhong; Yali Tang; et al. (Journal of Environmental Management, 2025)

Revealing the adsorption kinetics of microplastics towards hydrophobic antibiotic: New insights into the microplastics aging behavior and aquatic environmental factors - Ping Wu; Guo-dong Kang; Xue-jian Li; Lei-lei Lu; Hao Zhou; Sheng-hu Zhang; Yuan-qing Bu; Hou-hu Zhang (Journal of Environmental Chemical Engineering, 2025)

Effect of γ-Aminobutyric acid and dietary monosodium glutamate supplementation on gut microbiota and short-chain fatty acid: Insights from an in vitro colonic fermentation model - Jiarun Han; Xilian Zhao; Qiuqiu Ye; Yueting Wang; Yutong Wu; Shi Hu; Ping Li; Qing Gu (Food Bioscience, 2025)

Generation characteristics of polybrominated and polychlorinated dibenzo-p-dioxins/furans (PBDD/Fs and PCDD/Fs) under varying incineration conditions of municipal solid waste - Ming-Yang Liu; Ai-Min Song; Hui-Ru Li; Sheng-Tao Ma; Ren-Jie Shang; Yao Xiao; Ping-An Peng; Jian-Fang Hu (Environmental Pollution, 2025)

A remotely triggered phase change hydrogel dressing for controlled release and promoting healing of infected wounds - Xiaolong Hu; Hongyan Zhang; Zuan-Tao Lin; Yu Chen; Hao Cheng; Bi-Huan Zhong; Yongli Li; Xiao-Ping Liao; Jian Sun; Mei X. Wu; Gang-Biao Jiang (Chemical Engineering Journal, 2025)

Designing multilayer interlocked architectures with vertical LDH nanosheets in ZIF-67 composite membranes for upgrading CO2 separation - Yan-Mei Zhang; Li-Hao Xu; Xiao-Xue Hu; Bing-Hong Chen; Xin-Ru Chen; Qian-Qian Li; Heng Mao; Zhi-Ping Zhao (Chemical Engineering Journal, 2025)

Developing the sensing mechanism of high-performance N2H4 sensors derived from waste cotton stalk using a one-step process - Ping Hu; Jun Sun; Bo Ran; Jialin Li; Jialu Fang; Qihua Sun; Ning Tian; Zhaofeng Wu; Haiming Duan (Chemical Engineering Journal, 2025)

Retraction notice to “Magnesite driven the complementary effects of core fungi by optimizing the physicochemical parameters in pig manure composting” [Bioresource Technol. 360 (2022) 127541] - Wen Liang; Minna Jiao; Endian Hu; Tao Liu; Xiuna Ren; Ping Wang; Mukesh Kumar Awasthi; Ronghua Li; Zengqiang Zhang (Bioresource Technology, 2025)

Morphological characteristics and distribution of antennal sensilla of Spodoptera litura (Lepidoptera: Noctuidae) using scanning electron microscopy - Yong-Ping Li; Hai-Yan Zhou; Hui Ye; Robert A. Haack; Yuan Yang; Qiu-Lian Hu; Ming-Min Jiang; Jun Cao (Zoomorphology, 2025)

Aberrance of GAP43/p-GAP43 Closely Associates with the Pathology of Neuron Loss in Prion-Infected Rodent Models - Xiao-Xi Jia; Cao Chen; Chao Hu; Yue-Zhang Wu; Zhi-Yue Chao; Jia-Feng Zeng; Ru-Han A.; Dong-Hua Zhou; Yuan Wang; Wei-Wei Zhang; Kang Xiao; Li-Ping Gao; et al. (Molecular Neurobiology, 2025)

Sus scrofa RNase L inhibits PRRSV replication by activation of type I IFN signaling pathway and apoptosis - Xiangju Wu; Xiaoyan Cong; Ping Jiang; Mingming Zhou; Ying Yu; Dandan Jiang; Yue Hu; Juntong Li; Jinxia Zhang; Ying Cao; Haowen Zhang; Yijun Du; et al. (Veterinary Microbiology, 2025)

Deciphering denitrification drivers in a high‑nitrogen estuary: Insights from stable isotope analysis and microbial molecular techniques - Shengwei Cao; Ping Yin; Chunlei Liu; Xiujian Hu; Yaci Liu; Yuewen Zhao; Xiangyu Guan; Yasong Li (Science of The Total Environment, 2025)

Impact of eight extruded starchy whole grains on glycemic regulation and fecal microbiota modulation - Fang Fang; Yu-Xin He; Hao-Qiang Wang; Yan-Li Zhang; Ya-dong Zhong; Xiao-Tian Hu; Shao-Ping Nie; Ming-Yong Xie; Jie-Lun Hu (Food Hydrocolloids, 2025)

Synergistic neurotoxicity of clothianidin and photoaged microplastics in zebrafish: Implications for neuroendocrine disruption - Ping Ding; Yajing Han; Yanan Sun; XiaoXia Chen; Qing Ge; Wei Huang; Lijuan Zhang; Adela Jing Li; Guocheng Hu; Yunjiang Yu (Environmental Pollution, 2025)

Enhanced production of recombinant calf chymosin in Kluyveromyces lactis via CRISPR-Cas9 engineering - Yanli Zheng; Shiqing Wang; Yuhui Deng; Ping Hu; Qingxin Xue; Jiaxin Li; Lei Lei; Zhuhua Chan; Jiangke Yang; Wenfang Peng (Bioresource Technology, 2025)

Effect of Particle Size, Sphericity, and Distribution on Seepage in Granular Porous Media - Bo-bo Xiong; Rui Kuang; Ping Zhang; Bin Tian; Hong-hu Gao; Qian Zheng; Yu-qin Li (Geotechnical and Geological Engineering, 2025)

Evaluation of Enrichment Approaches for the Study of the Viromes in Mollusk Species - Tongling Chen; Tiantian Wu; Yunyi Hu; Zifeng Zhu; Ji Wu; Datao Lin; Xi Sun; Zhongdao Wu; Yi-Ping Li (Food and Environmental Virology, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Identification of the Shuanglongtan tectonic mélange (ca. 1.7–1.5 Ga) in the southwestern Yangtze Block and it’s tectonic implications - Jun-Ping Liu; Zai-Bo Sun; Xiao-Hu He; Jiang-Tai Zhao; Shi-Jun He; Ling-Jing Bi; Wei-Ke Li (Precambrian Research, 2025)

2.08 Ga andesitic gneisses in the southwestern Yangtze Block: Unveiling new insights into its geological evolution - Jun-Ping Liu; Zai-Bo Sun; Wei-Ke Li; Hua-Li Luo; Shi-Jun He; Shao-Bin Hu; Jiang-Tai Zhao; Hai-bao Yan; Ming-Guo Zhai; Hai-Long He (Precambrian Research, 2025)

Trace-elements driven up-regulation of secreted proteases expression in the human-pathogenic fungus Trichophyton rubrum - Oliver Blechert; Shanyu Lan; Shuzhen Xiong; Yuning Zou; Peicong Li; Jiewei Hu; Jiayuan Li; Ping Zhan (Journal of Trace Elements in Medicine and Biology, 2025)

Characterizing Chinese saffron Origin, Age and grade using VNlR hyperspectral imaging and Machine learning - Jiahui Wu; Jing Nie; Hao Hu; Xinyue Xu; Chunlin Li; Hongkui Zhou; Peishi Feng; Hanyi Mei; Karyne M. Rogers; Ping Wang; Yuwei Yuan (Food Research International, 2025)

Metabolomics-based mechanistic insights into antioxidant enhancement in mango juice fermented by various lactic acid bacteria - Shuai Liu; Yu-Jia Peng; Wei-Wei He; Xiao-Xiao Song; Yu-Xin He; Xiao-Yi Hu; Shui-Gen Bian; Yu-Hao Li; Jun-Yi Yin; Shao-Ping Nie; Ming-Yong Xie (Food Chemistry, 2025)

Identification and characterization of GRAS genes in passion fruit (Passiflora edulis Sims) revealed their roles in development regulation and stress response - Xinkai Cai; Denglin Li; Chaojia Liu; Jiayi Chen; Xiuqing Wei; Sitong Hu; Lin Lu; Shengzhen Chen; Qinglong Yao; Shiyu Xie; Xiaowen Xu; Ruoyu Liu; et al. (Plant Cell Reports, 2025)

CXCL10 Enhances Acid-Sensing Ion Channel Currents in Rat Dorsal Root - Ting-Ting Liu; Chun-Yu Qiu; Xue-Mei Li; Wang-Ping Hu (Molecular Neurobiology, 2025)

Comparative evaluation of the biological characteristics of flower organs and fruits of the new Chinese blueberry cultivar Zhaixuan 4 - Lichao Hu; Xiaomin Wang; Xinyue Ping; Yaqiong Wu; Wenlong Wu; Lianfei Lyu; Weilin Li (Horticulture, Environment, and Biotechnology, 2025)

The effect of nitrogen input on methane uptake in a wet and a dry year from a temperate desert steppe - Ping Yue; Kaihui Li; Ya Hu; Jingjuan Qiao; Zhaobin Song; Shaokun Wang; Tom Misselbrook; Xiaoan Zuo (Agricultural and Forest Meteorology, 2025)

Molecular fractionation mediates genotoxicity evolution of hydrochar-derived dissolved organic matter at the iron oxyhydroxides-water interface - Yan-Jun Liu; He-Yun Yang; Shu-Xian Gao; Zheng-Hao Li; Yan-Yun Hu; Xing Zheng; Guo-Ping Sheng (Water Research, 2025)

Amino modifications exacerbate the developmental abnormalities of polystyrene microplastics via mitochondria-mediated apoptosis pathway in zebrafish larvae - Jiayi Zhang; Guocheng Hu; Hongzhi Guo; Wenhui Yang; Xintong Li; Yuyang Ni; Miao He; Ping Ding; Yunjiang Yu (Science of The Total Environment, 2025)

Developed metabolomics approach reveals the non-volatile color-contributing metabolites during Keemun congou black tea processing - Mingchun Wen; Wei Hu; Lu Li; Piaopiao Long; Zisheng Han; Jia-Ping Ke; Zhiyang Deng; Mengting Zhu; Liang Zhang (Food Chemistry, 2025)

Multifunctional role of surfactant in fabricating polyamide nanofiltration membranes for Li+/Mg2+ separation - Shang Fang; Kecheng Guan; Aiwen Zhang; Liheng Dai; Siyu Zhou; Wenming Fu; Mengyang Hu; Ping Xu; Pengfei Zhang; Zhan Li; Zhaohuan Mai; Hideto Matsuyama (Desalination, 2025)

Unveiling shape-dependent intrinsic activity of cadmium sulfide (CdS) for photocatalytic uranium(VI) reduction - Yihao Quan; Sen Lu; Qingliang Wang; Hongqiang Wang; Eming Hu; Xinnan Wang; Jiacheng Bao; Xin Sun; Kai Li; Ping Ning (Chemical Engineering Journal, 2025)

Study on high-efficiency vanadium removement using sulfate radical-based AOPs and its oxidation mechanism of landfilled metallurgical residues - Jun Wang; Haoyu Li; Chunhua Hu; Xinyi He; Shihong Tian; Xuejun Zhu; Xuehua Mao; Yijia Zhang; Ping Liu (Chemical Engineering Journal, 2025)

Relationship Between Whole Blood Iron Levels and Lipid Profile Parameters in the General Population: Findings from Routine Physical Examination Report - Rou-Jun Pan; Zhi Luo; Yu-Shun You; Jun-Dong Wang; Ya-Qi Chen; Rong-Rong Zhou; Shu-Zi-Qi Chen; Lin-Min Wang; Jun-Xiang Zhao; Hua-Qin Su; Cai-Li Wang; Li-Fen Zhang; et al. (Biological Trace Element Research, 2024)

Real-time remote corn growth monitoring system using plant wearable fiber Bragg grating sensor - Wei Zhang; Muhammad Awais; Syed Muhammad Zaigham Abbas Naqvi; Yani Xiong; Linze Li; Yiheng Zang; Shakeel Ahmed; Junfeng Wu; Hao Zhang; Mukhtar Iderawumi Abdulraheem; Vijaya Raghavan; Jianfeng Ping; et al. (Computers and Electronics in Agriculture, 2024)

Inter-annual and spatial variations of air-sea CO2 fluxes and acidification mechanism in the coastal waters of Qingdao, China during 2011–2019 - Zheng-Xin Hu; Tie Li; Tian-Tian Ge; Jing-Wen Hu; Ping-Wang; Chun-Ying Liu; Gui-Peng Yang (Marine Pollution Bulletin, 2024)

Solving the storage location assignment of large-scale automated warehouse based on dynamic vortex search algorithm - Haoran Li; Jingsen Liu; Ping Hu; Huan Zhou (Swarm and Evolutionary Computation, 2024)

Ecological risks caused by neonicotinoid pesticides in sediments: A case study of freshwater basins in China - Xiaoxia Chen; Pengchong Wen; Yanan Sun; Ping Ding; Haibo Chen; Hui Li; Xin Li; Limei Cai; Yunjiang Yu; Guocheng Hu (Science of The Total Environment, 2024)

Precipitation-induced biomass enhancement and differential allocation in Inner Mongolia's herbaceous and shrub communities - Xiangyun Li; Ya Hu; Zhaobin Song; Ping Cong; Huan Cheng; Xuebo Zheng; Wenjing Song; Ping Yue; Shaokun Wang; Xiaoan Zuo (Science of The Total Environment, 2024)

Structurally diverse ent-clerodanoids from the aerial parts of Isodon scoparius - Xue-Chun Jiang; Kun Hu; Xue Bai; Xing-Ren Li; Bing-Chao Yan; Su-Ping Chen; Xiao-Nian Li; Han-Dong Sun; Pema-Tenzin Puno (Phytochemistry, 2024)

Eco-friendly, stable, and high-performance biochar prepared by a twice-modification scheme: Saccharification of raw materials & thermal air oxidation of biochar - Yundong Liu; Bu Li; Wang Kai Tong; Han Tang; Zhaoli Ping; Wenjuan Wang; Min-tian Gao; Chaomeng Dai; Nan Liu; Jiajun Hu; Jixiang Li (Journal of Environmental Management, 2024)

Corrigendum to “An isolated salt-tolerant Tetragenococcus halophilus 2MH-3 improved the volatile flavor of low-salt fermented fish sauce by regulating the microbial community” [Food Res. Int. 196 (2024) 115052] - Jiarun Han; Shi Hu; Xin Zhao; Jialan Jiang; Qi Wang; Jinfeng Wu; Xilian Zhao; Ping Li; Qing Gu (Food Research International, 2024)

Unraveling anti-aging mystery of green tea in C. elegans: Chemical truth and multiple mechanisms - Jia-ping Ke; Jia-Yi Li; Zi Yang; Hao-Yue Wu; Jing-Ya Yu; Yi Yang; Chen-Hui Chen; Peng Zhou; Fang Hua; Wei Wang; Fenglin Hu; Gang-Xiu Chu; et al. (Food Chemistry, 2024)

Variations and driving factors for concentrations and carbon isotopes of dissolved CO2 in lake water across different Chinese lakes - Hu Liu; Jia Liu; Huanye Wang; Zhonghui Liu; Xiangzhong Li; Ping Zhang; Weiguo Liu; Shangbin Xiao (Environmental Research, 2024)

Polyethylenimine-assisted preparation of Zr-MOF/GO membranes for radionuclide separation - Chuang Li; Zhan Li; Kecheng Guan; Yu-Hsuan Chiao; Pengfei Zhang; Ping Xu; Ralph Rolly Gonzales; Mengyang Hu; Zhaohuan Mai; Tomohisa Yoshioka; Hideto Matsuyama (Desalination, 2024)

Multiple NADPH-cytochrome P450 reductases from Lycoris radiata involved in Amaryllidaceae alkaloids biosynthesis - Yuqing Wu; Yifeng Zhang; Haitong Fan; Jie Gao; Siyu Shen; Jifan Jia; Rong Liu; Ping Su; Yating Hu; Wei Gao; Dan Li (Plant Molecular Biology, 2024)

Accumulation of Prion Triggers the Enhanced Glycolysis via Activation of AMKP Pathway in Prion-Infected Rodent and Cell Models - Qin Fan; Kang Xiao; Ruhan A; Li-Ping Gao; Yue-Zhang Wu; Dong-Dong Chen; Chao Hu; Xiao-Xi Jia; Chu-Mou Liu; Xin Liu; Cao Chen; Qi Shi; et al. (Molecular Neurobiology, 2024)

Engineered bispecific antibodies with enhanced breadth and potency against SARS-CoV-2 variants and SARS-related coronaviruses - Fangfang Chang; Qian Wu; Yabin Hu; Zhendong Pan; Yong-Chen Liu; Yue-Zhou Li; Mihnea Bostina; Wenpei Liu; Ping Zhao; Xiaowang Qu; Yi-Ping Li (Medical Microbiology and Immunology, 2024)

Plant Functional Traits Modulate Effects of Drought on C:N:P Stoichiometry of Plant, Litter, and Soil Microbe in an Arid Grassland - Zhaobin Song; Xiaoan Zuo; Xueyong Zhao; Xiangyun Li; Ya Hu; Jingjuan Qiao; Ping Yue; Min Chen; Shaokun Wang; Jordi Sardans; Josep Peñuelas (Journal of Soil Science and Plant Nutrition, 2024)

Characterization and fine mapping of a white stripe leaf mutant in rice - Binhua Hu; Zhiyuan He; Xiaoli Xiang; Hui Li; Anping Du; Mingxia Wang; Yulu Bai; Lanying Wang; Cong Zhang; Ping Wang; Zhigang Pu (Genetic Resources and Crop Evolution, 2024)

The actionability of household food waste reduction - Xiaolei Li; Wuyang Hu; Jian Li; Ping Qing (Sustainable Production and Consumption, 2024)

Dynamic evolution of particulate and gaseous emissions for typical residential coal combustion - Siyuan Li; Dantong Liu; Xiaotong Jiang; Ping Tian; JiuJiang Sheng; Yangzhou Wu; Kang Hu; Kai Bi; Ruijie Li; Delong Zhao; Mengyu Huang; Shaofei Kong; et al. (Science of The Total Environment, 2024)

Pyrite functionalized Black Soldier Fly feces biochar for mine soil quality improvement and heavy metals immobilization - Chuang Li; Lei Zhao; Ping Chen; Shujing Ye; Hailan Yang; Yanling Gu; Shaobo Liu; Zhiming Yang; Xinjiang Hu; Xiaofei Tan (Process Safety and Environmental Protection, 2024)

Brominated flame retardants in surface sediment from Western Guangdong, South China: Occurrence, distribution and toxicity in Caenorhabditis elegans - Xiaoxia Chen; Ping Ding; Haibo Chen; Tingzhen Li; Min Zhang; Yunjiang Yu; Guocheng Hu (Journal of Environmental Sciences, 2024)

An isolated salt-tolerant Tetragenococcus halophilus 2MH-3 improved the volatile flavor of low-salt fermented fish sauce by regulating the microbial community - Jiarun Han; Shi Hu; Xin Zhao; Jialan Jiang; Qi Wang; Jinfeng Wu; Xilian Zhao; Ping Li; Qing Gu (Food Research International, 2024)

Atomic modulation of FeN4 sites on hollow carbon nanospheres by neighboring Mn atoms for ultra-stable Zn-air batteries - Zhaowei Ji; Chenglong Qiu; Ping Li; Yifan Li; Jing Shi; Jingyi Wu; Yue Zhu; Wei Hu; Zhi Li; Huanlei Wang (Chemical Engineering Journal, 2024)

Design of graphitic multichannel monolith electrode with in-situ transformed Ni-N-C sites for continuous electrolysis of CO2 - Xu Hu; Hong-Liang Xu; Ling-Yu Dong; Wen-Cui Li; Guang-Ping Hao; An-Hui Lu (Chemical Engineering Journal, 2024)

1-Dimensional metal Nitride-Supported platinum nanoclusters for Low-Temperature hydrogen production from formic acid - Liang Qiu; Bowen Sheng; Haotian Ye; Ping Wang; Jinglin Li; Ying Li; Yixin Li; Tianqi Yu; Muhammad Salman Nasir; Xinqiang Wang; Hu Pan; Zhen Huang; et al. (Chemical Engineering Journal, 2024)

Divergent chemical compositions of soil organic matter size fractions under long-term amendments across a climate gradient - Fanbo Song; Ning Hu; Yilai Lou; Huimin Zhang; Ping Zhu; Dongchu Li; Hongjun Gao; Shuiqing Zhang; Yidong Wang (Soil and Tillage Research, 2024)

RAD-seq data for Engelhardia roxburghiana provide insights into the palaeogeography of Hainan Island and its relationship to mainland China since the late Eocene - Pei-Han Huang; Tian-Rui Wang; Min Li; Zi-Jia Lu; Ren-Ping Su; Ou-Yan Fang; Lang Li; Shi-Shun Zhou; Yun-Hong Tan; Hong-Hu Meng; Yi-Gang Song; Jie Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Novel highly utilized PdNi bimetallic-loaded N-doped carbon catalysts prepared from MOF for Suzuki coupling reaction and hydro reduction of nitroaromatics - Yanjie Jiang; Siyu Han; Gongshu Wang; Zhangpei Chen; Ping Li; Jianshe Hu (Journal of Environmental Chemical Engineering, 2024)

Conjugates of glycosylated antarctic krill proteins and curcumin: Maintaining the storage quality of salmon fillets coupling with photodynamic inactivation - Qiaohui Zeng; Di Hu; Yufeng Li; Ping Qi; Lu Chen; Ronghan Wang; Yong Zhao; Jing Jing Wang (Food Hydrocolloids, 2024)

Highly stable Ag@Au nanowires micromesh as transparent conductive network for stretchable electrochromic modulator - Ping Zhang; Qing Sui; Zhiqiang Liu; Chengyv Hu; Chunjing Li; Xiaodan Guo; Jinhui Wang; Guofa Cai (Chemical Engineering Journal, 2024)

Large-area and high-efficiency carbon nanotube/silicon heterojunction solar cells enabled by self-similar fiber electrodes and solid-state gel electrolytes - Xian-Gang Hu; Bingsheng Li; Yi-Ming Zhao; An-Ping Wu; Zhenhua Lin; Peng-Xiang Hou; Chang Liu; Yue Hao; Jingjing Chang (Chemical Engineering Journal, 2024)

Characteristics and assembly mechanisms of bacterial and fungal communities in soils from Chinese forests across different climatic zones - Ming Sheng; Wei Hu; Cong-Qiang Liu; Mutong Niu; Rui Jin; Junjun Deng; Libin Wu; Ping Li; Zhifeng Yan; Yong-Guan Zhu; Pingqing Fu (CATENA, 2024)

The Role of Nicotine Metabolic Rate on Nicotine Dependence and Rewarding: Nicotine Metabolism in Chinese Male Smokers and Male Mice - Mingda Liu; Hongjuan Wang; Yaning Fu; Xiangyu Li; Ping Wu; Guanglin Liu; Ruiyan Wang; Yuan Zhang; Huan Chen; Hongwei Hou; Qingyuan Hu (Molecular Neurobiology, 2024)

Microbial Community Structure and Metabolism of Xinjiang Fine-Wool Sheep based on High-Throughput Sequencing Technology - Rui Yao; Fulin Li; Xuyang Dong; Yueren Xu; Ruirui Hu; Limin Wang; Kuojun Cai; Xiaogang Liu; Wei Ni; Ping Zhou; Shengwei Hu (Current Microbiology, 2024)

Levels, sources, and health risk assessment of phthalate acid esters in indoor dust of various microenvironments in university - Jun Pan; Xin Li; Ping Ding; Haojie Luo; Sha Cai; Qing Ge; Liuyi Zhang; Guocheng Hu (Chemosphere, 2024)

Environmental microbes alleviate antibiotic disturbance on plant endophytes in aquatic microcosms: Prospects for conferring fitness benefits - Yi Hu; Fan-Li Meng; Jia-Heng Zhao; Guo-Ping Sheng (Water Research, 2024)

A nanoparticle vaccine based on the VP121–26 and VP2 structural proteins of Senecavirus A induces robust protective immune responses - Nan Cao; Yamei Li; Huawei Zhang; Xiangzu Liu; Shudan Liu; Mingxing Lu; Zihui Hu; Linxing Tian; Xiangmin Li; Ping Qian (Veterinary Microbiology, 2024)

A citrullinated antigenic vaccine in treatment of autoimmune arthritis - Xu Jin; Tianya Dong; Qian Wang; Yang Xie; Xiangyu Fang; Chaonan Wei; Shuyan Liu; Xi Zheng; Ping Wang; Danxue Zhu; Lulu Cao; Suwei Dong; et al. (Science Bulletin, 2024)

Multi-omics insights into the function and evolution of sodium benzoate biodegradation pathway in Benzoatithermus flavus gen. nov., sp. nov. from hot spring - Chao-Jian Hu; Yi-Qing Lv; Wen-Dong Xian; Jian-Yu Jiao; Zheng-Han Lian; Sha Tan; Meng-Meng Li; Zhen-Hao Luo; Ze-Tao Liu; Ai-Ping Lv; Lan Liu; Mukhtiar Ali; et al. (Journal of Hazardous Materials, 2024)

Multi-objective optimization of clean utilization for zinc leaching residues by rotary kiln using neural network coupled modeling - Chen-Mu Zhang; Zhi Zan; Yao Shi; Hui-Quan Li; Lang-Ming Liu; Wei-Ping Liu; Wen-Jun Lin; Jing-Jing Shi; Ying-yan Hu; Xue Guan; Kuang-Yi Chen; Xiao Liu; et al. (Journal of Cleaner Production, 2024)

Sustainable flood control strategies under extreme rainfall: Allocation of flood drainage rights in the middle and lower reaches of the yellow river based on a new decision-making framework - Xin Huang; Juqin Shen; Shuqin Li; Chen Chi; Ping Guo; Pei Hu (Journal of Environmental Management, 2024)

Aged polystyrene microplastics exposure affects apoptosis via inducing mitochondrial dysfunction and oxidative stress in early life of zebrafish - Ping Ding; Chongdan Xiang; Qian Yao; Xintong Li; Jiayi Zhang; Renli Yin; Lijuan Zhang; Adela Jing Li; Guocheng Hu (Journal of Environmental Management, 2024)

Preparation, typical structural characteristics and relieving effects on osteoarthritis of squid cartilage type II collagen peptides - Qianqian Zhao; Zhaoxia Li; Zeyu Liu; Xue Zhao; Yan Fan; Ping Dong; Hu Hou (Food Research International, 2024)

Rapid evaluation of the quality of Smilax glabra Roxb. using QADS based on FT-NIR combined with multiple intelligent algorithms - Geng-zhi Zhan; Xin-yue Guo; Zi-chao Qiu; Lu-yao Cai; Qian Hu; Ye Gao; Shu-wan Tang; Cun-yu Li; Yun-feng Zheng; Guo-ping Peng (Food Chemistry, 2024)

Lipid matrix-specific pretreatment method for enhancing the extractability and allergenicity maintenance of bovine milk allergens in ELISA detection - Wei Hu; Ziyi Xiong; Xuanyi Meng; Yong Wu; Ping Tong; Jinyan Gao; Xin Li; Hongbing Chen (Food Chemistry, 2024)

The impact of dissipative algorithms on assessment of high-speed train running safety on railway bridges - Han Zhao; Biao Wei; Zhanjun Shao; Xiaonan Xie; Peng Zhang; Huifang Hu; Yingying Zeng; Lizhong Jiang; Changqing Li; Ping Xiang (Engineering Structures, 2024)

Platelet membrane coated Cu9S8-SNAP for NIR-II photoacoustic imaging guided NO repairing acute kidney injury - Xiaojuan Hu; Danping Wu; Shijie Yao; Gongning Chen; Ping Li; Yang Chen; Wancheng Gong; Weijiao Fan; Xiaoyi Chen; Xiaozhou Mou; Yu Cai; Xianghong Yang (Chemical Engineering Journal, 2024)

Copper-ion-complexed palygorskite as a novel nanozyme with enhanced peroxidase-like activity for sensitive colorimetric sensing - Ping Chen; Hui Zhong; Xiao-rong Li; Tingting Zhang; Xiang Wang; Fang Hu; Yubo Yan; Jiaxing Xu; Meisheng Li (Applied Clay Science, 2024)

Rapid and sensitive detection of SARS-CoV-2 based on a phage-displayed scFv antibody fusion with alkaline phosphatase and NanoLuc luciferase - Yuxue Yan; Guofu Shang; Jiling Xie; Yingying Li; Shaomei Chen; Yanqin Yu; Ping Yue; Xiaoyan Peng; Min Ai; Zuquan Hu (Analytica Chimica Acta, 2024)

Electrical structure identification of deep shale gas reservoir in complex structural area using wide field electromagnetic method - Zhi-Wen Gu; Yue-Gang Li; Chang-Heng Yu; Zhong-Ping Zou; Ai-Guo Hu; Xue-Bo Yin; Qinag Wang; Heng Ye; Zhang-Kun Tan (Applied Geophysics, 2024)

Inventorization and ecological risk assessment of tetrabromobisphenol A and hexabromocyclododecane in sediments from Guangdong coastal area of South China Sea - Xiaoxia Chen; Xin Li; Yuqing Fan; Guocheng Hu; Hang Xie; Xiaoyan Chen; Ping Ding; Yao Dang; Xiyuan Hu; Qinghua Chen (Science of The Total Environment, 2024)

Salinity decreases methane concentrations in Chinese lakes - Hu Liu; Shangbin Xiao; Weiguo Liu; Huanye Wang; Zhonghui Liu; Xiangzhong Li; Ping Zhang; Jia Liu (Science of The Total Environment, 2024)

Phase I clinical trial of intracerebral injection of lentiviral-ABCD1 for the treatment of cerebral adrenoleukodystrophy - Qiu-Hong Wang; Jing Wang; Zhi-Pei Ling; Zhi-Qiang Cui; Jie Gong; Rui Zhang; Shi-Jun Li; Yang-Yang Wang; Rui Yang; De-Hui Huang; Wen He; Jing Gao; et al. (Science Bulletin, 2024)

Boosting the catalytic efficiency of sulfonated crosslinked-polyaniline organocatalyst for producing 5-hydroxymethylfurfural from fructose - Zhidan Xue; Ping Hu; Hui Li; Di Wu; Yimeng Guo; Hang Lv; Changwei Hu; Liangfang Zhu (Fuel, 2024)

Near-infrared-LED photostimulated luminescent nanoprobes based on lanthanide-doped SrS nanocrystals - Wei Lian; Qianqi Yang; Yuhan Liu; Datao Tu; Liangzhi Cai; Xiaoying Shang; Bowen Li; Ping Hu; Wei Zheng; Zhuo Chen; Xueyuan Chen (Chemical Engineering Journal, 2024)

Hydrogel membrane composite reduces fouling and retains ammonium efficiently - Ralph Rolly Gonzales; Jing Li; Pengfei Zhang; Ping Xu; Zhan Li; Mengyang Hu; Zhaohuan Mai; Kecheng Guan; Hideto Matsuyama (Environmental Chemistry Letters, 2024)
The recovery of pure water and valuable substances from wastewater is a major challenge in the context of the circular economy, requiring advanced separation methods. However, actual membrane separation techniques such as forward osmosis are limited by membrane fouling and selectivity. Here, we synthesized composite membranes by crosslinking polyvinyl alcohol hydrogel, using both glutaraldehyde and borax as crosslinking agents, on top of cellulose ester membranes. We tested these composite membranes on model and real wastewater. Results show that the composite membranes retain ammonium effectively, maintain surface electroneutrality, and exhibit remarkable resistance to fouling by organic and biological contaminants. This is explained by the high hydrophilicity of the membrane surface after application of a hydrogel layer.

Wearable solid-phase microextraction sampling for enhanced detection of volatile analytes in human ears - Wenzheng Mo; Lei Li; Bi-Cheng Yang; Xiangjie Wang; Baixue Wang; Jianfeng Zhang; Qiaoyun Huang; Zhong-Ping Yao; Dong Zhang; Bin Hu (Analytica Chimica Acta, 2024)

Current progress in umami peptides from blue foods: Preparation, screening, evaluation, synergistic effects, and taste mechanism - Li Hao; Yan Fan; Qiaoji Tian; Chaozhong Fan; Yanying Zhang; Ping Dong; Yanchao Wang; Hu Hou (Trends in Food Science & Technology, 2024)

Different reference genomes determine different results: Comparing SNP calling in RAD-seq of Engelhardia roxburghiana using different reference genomes - Pei-Han Huang; Tian-Rui Wang; Min Li; Ou-Yan Fang; Ren-Ping Su; Hong-Hu Meng; Yi-Gang Song; Jie Li (Plant Science, 2024)

Inhibition of flowering by gibberellins in the woody plant Jatropha curcas is restored by overexpression of JcFT - Ping Huang; Jie Yang; Jiapeng Ke; Li Cai; Yingxiong Hu; Jun Ni; Chaoqiong Li; Zeng-Fu Xu; Mingyong Tang (Plant Science, 2024)

VGluT2 neuron subtypes in the paraventricular thalamic nucleus regulate depression in paraquat-induced Parkinson’s disease - Yu Zhang; Yihua Jiang; Zhen Yu; Yinhan Li; Xinpei Lin; Yali Weng; Zhenkun Guo; Hong Hu; Wenya Shao; Guangxia Yu; Fuli Zheng; Ping Cai; et al. (Journal of Hazardous Materials, 2024)

Microglial exosomes in paraquat-induced Parkinson's disease: Neuroprotection and biomarker clues - Jingwen Wu; Wenya Shao; Xu Liu; Fuli Zheng; Yaping Wang; Ping Cai; Zhenkun Guo; Hong Hu; Guangxia Yu; Jianhui Guo; Linlin Yao; Siying Wu; et al. (Environmental Pollution, 2024)

Ternary-coordination-regulated polyamide nanofiltration membranes for Li+/Mg2+ separation - Shang Fang; Kecheng Guan; Siyu Zhou; Qiangqiang Song; Yongxuan Shi; Wenming Fu; Zhan Li; Ping Xu; Mengyang Hu; Zhaohuan Mai; Pengfei Zhang; Hideto Matsuyama (Desalination, 2024)

Autonomous, temperature-enhanced oxidase-mimic multimodal antimicrobial film for prolonged preservation of perishable products - Liang Zhang; Wen He; Yiya Ping; Wenze Wang; Puyuan Hu; Bingzhi Li; Wenxin Zhu; Jing Sun; Yanwei Ji; Jianlong Wang (Chemical Engineering Journal, 2024)

Residues of chlorpyrifos in the environment induce resistance in Aedes albopictus by affecting its olfactory system and neurotoxicity - Yanrong Chen; Chen Zhang; Wen Li; Ruoyun Lan; Rufei Chen; Jingchao Hu; Chenyu Yang; Ping Wang; Bin Tang; Shigui Wang (Science of The Total Environment, 2024)

P53 upregulation by USP7-engaging molecular glues - Zhaoyang Li; Ziying Wang; Chao Zhong; Hang Zhang; Rui Liu; Ping An; Zhiqiang Ma; Junmei Lu; Chengfang Pan; Zhaolin Zhang; Zhiyuan Cao; Jianyi Hu; et al. (Science Bulletin, 2024)

microRNA-3037 targeting CYP6CY2 confers imidacloprid resistance to Sitobion miscanthi (Takahashi) - Bai-Zhong Zhang; Yu-Tai Jiang; Ling-Ling Cui; Gui-Lei Hu; Xin-An Li; Pei Zhang; Xiang Ji; Ping-Chuan Ma; Fan-Bin Kong; Run-Qiang Liu (Pesticide Biochemistry and Physiology, 2024)

Isolation of 24-homoscalarane sesterterpenoids from a sponge of the genus Lendenfeldia - Li-Guo Zheng; You-Yan Chen; Chia-Ching Liaw; Yu-Chi Lin; Su-Ying Chien; Yi-Hao Lo; Yu-Chi Tsai; Hao-Chun Hu; You-Ying Chen; Tsong-Long Hwang; Tzu-Ming Ou; Ping-Jyun Sung (Phytochemistry Letters, 2024)

Developing novel ensemble models for predicting soil hydraulic properties in China’s arid region - Liantao Niu; Xiaoxu Jia; Xiangdong Li; Chunlei Zhao; Lidong Ren; Wei Hu; Ping Zhu; Danfeng Li; Baoqing Zhang; Ming'an Shao (Journal of Hydrology, 2024)

Plio-Pleistocene drainage reorganization in the middle Yellow River of China, revealed by provenance and paleocurrent analysis of fluvial sediments - Menghao Li; Zhenbo Hu; Ping Wang; Baotian Pan; David Bridgland; Qinhong Mo; Xiaohua Li; Zijuan Dong; Meiling Zhong; Renzhe Pan; Ningyi Li (Geomorphology, 2024)

Ferulic acid alleviates avermectin induced renal injury in carp by inhibiting inflammation, oxidative stress and apoptosis - Qiulu Li; Kaixin Ping; Yannan Xiang; Ying Sun; Zunhan Hu; Shujuan Liu; Xinying Guan; Mian Fu (Fish & Shellfish Immunology, 2024)

Polypeptide urea increases rice yield and nitrogen use efficiency through root growth improvement - Shuang Liao; Fei Deng; Wei Zhou; Li Wang; Wu Li; Hui Hu; Shi-lin Pu; Shu-xian Li; Yong Chen; You-feng Tao; Chi Zhang; Qiu-ping Li; et al. (Field Crops Research, 2024)

Photoaged polystyrene microplastics result in neurotoxicity associated with neurotransmission and neurodevelopment in zebrafish larvae (Danio rerio) - Xintong Li; Tong Zheng; Jiayi Zhang; Haibo Chen; Chongdan Xiang; Yanan Sun; Yao Dang; Ping Ding; Guocheng Hu; Yunjiang Yu (Environmental Research, 2024)

Halogenated aromatic pollutants in routine animal-derived food of south China: Occurrence, sources, and dietary intake risks - Li-Na Zhang; Ping-An Peng; Hui-Ru Li; Ming-Yang Liu; Jian-Fang Hu (Environmental Pollution, 2024)

High-precision microcline 40Ar/39Ar dating by combined techniques - Xiu-Juan Bai; Yi-Long Li; Rong-Guo Hu; Xiao Liu; Bin Tang; Xiang-Ping Gu; Hua-Ning Qiu (Chemical Geology, 2024)

Soil warming alters tree water use and canopy stomatal conductance in a mixed subtropical forest - Weiting Hu; Christoph Bachofen; Yanqiong Li; Liwei Zhu; Ping Zhao; Charlotte Grossiord (Agricultural and Forest Meteorology, 2024)

Performance on adsorption of toluene by ionic liquid-modified AC in high-humidity exhaust gas - Ji-feng Guo; Zhao-li Ping; Nan Liu; Xin Zhang; Jia-lin Lv; Yan-yan Yao; Jia-jun Hu; Wen-juan Wang; Ji-xiang Li (Environmental Science and Pollution Research, 2024)

Changes in coal waste DOM chemodiversity and Fe/Al oxides during weathering drive the fraction conversion of heavy metals - Pinpeng Tuo; Zongpeng Zhang; Ping Du; Lijuan Hu; Renyou Li; Jie Ren (Science of The Total Environment, 2024)

The effect of nitrogen input on N2O emission depends on precipitation in a temperate desert steppe - Ping Yue; Kaihui Li; Ya Hu; Jingjuan Qiao; Shaokun Wang; Xujun Ma; Tom Misselbrook; Xiaoan Zuo (Science of The Total Environment, 2024)

Glacier dam evolution and knickpoint migration in the Yarlung Tsangpo Gorge, eastern Himalayas, since the last glacial period - Ping Wang; Huiying Wang; Gang Hu; Tao Liu; Cuiping Li; Jintang Qin; Yukui Ge (Quaternary Science Reviews, 2024)

Binding properties of chemosensory protein 4 in Riptortus pedestris to aggregation pheromones - Jin-Bu Li; Qiang Liu; Sai Ma; Yue-Ying Wang; Xing-Zhou Liu; Chao-Wei Wang; Da-Jiang Wang; Zhuang-Zhuang Hu; Jia-Wen Gan; Xiu-Yun Zhu; Bao-Ping Li; Mao-Zhu Yin; et al. (Pesticide Biochemistry and Physiology, 2024)

Water distribution in pore systems and its influences on gas-bearing property of deep shale: A case study of the Longmaxi Formation in the Luzhou area, southern Sichuan Basin - Yue Feng; Xianming Xiao; Ping Gao; Dongfeng Hu; Ruobing Liu; Gang Li; Chengang Lu; Qin Zhou (Marine and Petroleum Geology, 2024)

Three-dimensional multi-channel structure NiCo alloy used for boosting efficient overall water splitting - Fan Yang; Zelin Li; Fei Zhu; Xiaolong Chen; Songwei Ge; Fei Yin; Fairy Fan Yang; Rui Yang; Yanjing Liu; Lili Gao; Qiang Wang; Rui Feng; et al. (Fuel, 2024)

Combined neurotoxicity of aged microplastics and thiamethoxam in the early developmental stages of zebrafish (Danio rerio) - Yanan Sun; Ping Ding; Jiayi Zhang; Kexin Sun; Xintong Li; Qing Ge; Yao Dang; Yunjiang Yu; Guocheng Hu (Environmental Pollution, 2024)

LncRNA NR_030777 promotes mitophagy by targeting CDK1-related mitochondrial fission and ATG12 to attenuate paraquat-induced Parkinson's disease - Nengzhou Chen; Hong Hu; Jianping Tang; Fuli Zheng; Zhenkun Guo; Xinpei Lin; Michael Aschner; Wenya Shao; Guangxia Yu; Ping Cai; Wei-Chun Chou; Siying Wu; et al. (Environmental Pollution, 2024)

Complete genome analysis of a novel narnavirus in sweet viburnum (Viburnum odoratissimum) - Yangwei Gao; Zhongtian Xu; Ping Li; Xiaodi Hu; Jian-Ping Chen; Chuan-Xi Zhang; Yiyuan Li (Archives of Virology, 2024)

Characterization of gonadal development phases and maturation mechanisms in male Pacific whiteleg shrimp (Litopenaeus vannamei) - Tong Chang; Ping Wang; Fenglu Han; Xiaolong Liang; Xianming Xiao; Hu Chen; Chang Xu; Erchao Li (Aquaculture, 2024)

Environmental performance of unfired bricks produced from co-disposal of mine tailings and municipal solid waste incineration fly ash based on comprehensive leaching tests - Ping Wang; Jiangshan Li; Yuanan Hu; Hefa Cheng (Environmental Pollution, 2024)

Intensifying the simultaneous removal of nitrogen and phosphorus of an integrated aerobic granular sludge-membrane bioreactor by Acinetobacter junii - Weifeng Liang; Biao Yang; Liying Bin; Yadong Hu; Depeng Fan; Weirui Chen; Ping Li; Bing Tang (Bioresource Technology, 2024)

Effect of Regional Brain Activity Following Repeat Transcranial Magnetic Stimulation in SCA3: A Secondary Analysis of a Randomized Clinical Trial - Xia Liu; Lin Zhang; Hao-Lin Xu; Xia-Hua Liu; Arif Sikandar; Meng-Cheng Li; Xiao-Yue Xia; Zi-Qiang Huang; Na-Ping Chen; Yu-Qing Tu; Jian-Ping Hu; Shi-Rui Gan; et al. (The Cerebellum, 2024)

A human-specific insertion promotes cell proliferation and migration by enhancing TBC1D8B expression - Hui Zhao; Lin-Lin Liu; Jian Sun; Lian Jin; Hai-Bing Xie; Jian-Bo Li; Hui Xu; Dong-Dong Wu; Xiao-Lin Zhuang; Min-Sheng Peng; Ya-Jun Guo; Wei-Zhu Qian; et al. (Science China Life Sciences, 2024)

Iron oxide–apatite deposits form from hydrosaline liquids exsolved from subvolcanic intrusions - Xin-Fu Zhao; Li-Ping Zeng; Wang Liao; Yi-Zhe Fan; Albert H. Hofstra; Poul Emsbo; Hao Hu; Guang Wen; Jian-Wei Li (Mineralium Deposita, 2024)

LiCOI1 mediates the biosynthesis of monoterpenes induced by methyl jasmonate in Lilium ‘Siberia’ - Zhuo Leng; Ying-Ying Li; Yu-Chen Fu; Jing Wu; Ping-Sheng Leng; Zeng-Hui Hu (Horticulture, Environment, and Biotechnology, 2024)

Persistence of fertilization effects on soil organic carbon in degraded alpine wetlands in the Yellow River source region - Peng Duan; Rongyi Wei; Fangping Wang; Yongxiao Li; Ci Song; Bixia Hu; Ping Yang; Huakun Zhou; Buqing Yao; Zhizhong Zhao (Journal of Mountain Science, 2024)

Spatiotemporal evolution and influencing factors of surface urban heat island footprint across different-sized cities - Hongchao Xu; Chunlin Li; Yuanman Hu; Hao Wang; Ding Wen; Zhenxing Li; Xiaoying Ping; Qiuyue Wang; Qi Li (Urban Climate, 2024)

Microbial colony sequencing combined with metabolomics revealed the effects of chronic hexavalent chromium and nickel combined exposure on intestinal inflammation in mice - Yueming Gu; Shuangyan Zheng; Cheng Huang; Xianhong Cao; Ping Liu; Yu Zhuang; Guyue Li; Guoliang Hu; Xiaona Gao; Xiaoquan Guo (Science of The Total Environment, 2024)

Plant functional traits mediate the response magnitude of plant-litter-soil microbial C: N: P stoichiometry to nitrogen addition in a desert steppe - Zhaobin Song; Xiaoan Zuo; Xueyong Zhao; Jingjuan Qiao; Hu Ya; Xiangyun Li; Ping Yue; Min Chen; Shaokun Wang; Eduardo Medina-Roldán (Science of The Total Environment, 2024)

Determining buffering capacity of polydimethylsiloxane-based passive dosing for hydrophobic organic compounds in large-volume bioassays - Hao Hu; Ping Ma; Huizhen Li; Jing You (Science of The Total Environment, 2024)

Indole alkaloids isolated from the Nicotiana tabacum-derived Aspergillus fumigatus 0338 as potential inhibitors for tobacco powdery mildew and their mode of actions - Yue-Yu Ma; Gui Pu; Hua-Yin Liu; Sui Yao; Guang-Hui Kong; Yu-Ping Wu; Yin-Ke Li; Wei-Guang Wang; Min Zhou; Qiu-Fen Hu; Feng-Xian Yang (Pesticide Biochemistry and Physiology, 2024)

Behavioral and molecular response of the insect parasitic nematode Steinernema carpocapsae to plant volatiles - Peng-hua Bai; Jin-Ping Yu; Rui-rui Hu; Qian-wen Fu; Hai-chao Wu; Xing-yue Li; Guo-hao Zu; Bao-sheng Liu; Yu Zhang (Journal of Invertebrate Pathology, 2024)

Effects of Fractionation Methods on Soil Aggregate Microbial Community Composition: Settling vs. Wet Sieving - Xin Gao; Rui Wang; Yaxian Hu; Weijia Li; Lanlan Du; Shengli Guo; Shengjun Wu; Ping Huang (Journal of Soil Science and Plant Nutrition, 2024)

CsBZR1 Family Transcription Factors in Wild and Cultural Tea Plants and Their Response to Hormone and Abiotic Stress - Jing-Wen Li; Ping Zhou; Ni Yang; Zhi-Hang Hu; Yi Chen; Wei Luo; Jie-Yu Kong; Zhi-Yuan Qin; Xing-Hui Li; Xuan Chen; Jing Zhuang (Journal of Plant Growth Regulation, 2024)

Heat shock induces HuR-dependent MKP-1 posttranslational regulation through the p38 MAPK signaling cascade - Xiao-juan Ma; Zhan Sun; Yi-ping Wang; Xue-ping Yao; Ting-ting Luo; Ya-li Bao; Dina Ainiwaer; Tian Zhang; Hengyi Zhu; Yan Zhang; Fei-ming Hu; Wen-yan Yu (Tissue and Cell, 2024)

The IL-31/TRPV1 pathway mediates allergic asthma exacerbated by DINP dermal exposure in OVA-sensitized Balb/c mice - Qi Peng; Yang Wu; Yan Li; Chan Lu; Runming Yao; Siyuan Hu; Ning Ma; Shaohui Chen; Xu Yang; Ping Ma (Science of The Total Environment, 2024)

Photoaging enhances combined toxicity of microplastics and tetrabromobisphenol A by inducing intestinal damage and oxidative stress in Caenorhabditis elegans - Haibo Chen; Xiaoxia Chen; Ping Ding; Yulun Gu; Yongqi Jiang; Xintong Li; Guocheng Hu; Liangzhong Li; Chen Wang; Jun Yu; Hui Li (Science of The Total Environment, 2024)

Growing-season drought and nitrogen addition interactively impair grassland ecosystem stability by reducing species diversity, asynchrony, and stability - Peng Lv; Shanshan Sun; Yuqiang Li; Shenglong Zhao; Jing Zhang; Ya Hu; Ping Yue; Xiaoan Zuo (Science of The Total Environment, 2024)

Fluorogenic RNA aptamer output sensors via transcription activated by recombinase polymerase amplification for nucleic acid testing - Jiajie Liang; Xin Liu; Wei Xiao; Peijun Teng; Ping Guan; Wanli Liang; Liangshan Hu; Guanbo He; Haorong He; Gan Li; Siyi Zou; Cheng Lu; et al. (Chemical Engineering Journal, 2024)

Plant composition change mediates climate drought, nitrogen addition, and grazing effects on soil net nitrogen mineralization in a semi-arid grassland in North China - Peng Lv; Shanshan Sun; Yuqiang Li; Shenglong Zhao; Jing Zhang; Ya Hu; Ping Yue; Xiaoan Zuo (Science of The Total Environment, 2024)

Harnessing the composition of dissolved organic matter in lagoon sediment in association with rare earth elements using fluorescence and UV–visible absorption spectroscopy - Philomina Onyedikachi Peter; Binessi Edouard Ifon; François Nkinahamira; Kayode Hassan Lasisi; Jiangwei Li; Anyi Hu; Chang-Ping Yu (Science of The Total Environment, 2024)

Drought intensity and post-drought precipitation determine vegetation recovery in a desert steppe in Inner Mongolia, China - Xiangyun Li; Zhaobin Song; Ya Hu; Jingjuan Qiao; Yuheng Chen; Shaokun Wang; Ping Yue; Min Chen; Yuguang Ke; Chong Xu; Qiang Yu; Xiaoan Zuo (Science of The Total Environment, 2024)

Multiomics analyses of two Leonurus species illuminate leonurine biosynthesis and its evolution - Peng Li; Meng-Xiao Yan; Pan Liu; Dan-Jie Yang; Ze-Kun He; Yun Gao; Yan Jiang; Yu Kong; Xin Zhong; Sheng Wu; Jun Yang; Hong-Xia Wang; et al. (Molecular Plant, 2024)

Highly efficient activation of periodate by a manganese-modified biochar to rapidly degrade methylene blue - Jiamin Gong; Honghui Jiang; Xiang Li; Hao Cheng; Ziqi Wang; Jingju Cai; Meifang Li; Ping Wang; Hui Wang; Xi Hu; Xinjiang Hu (Environmental Research, 2024)

Accumulation of livestock manure–derived heavy metals in the Hexi Corridor oasis agricultural alkaline soil and bioavailability to Chinese cabbage (Brassica pekinensis L.) after 4-year continuous application - Tian-Xia Guan; Zhao-Ping Lu; Ming Yue; Bao-Guo Li; Ai-Gen Fu; Xu-Dong Zhang; Zhong-Hu Li (Environmental Pollution, 2024)

Multidentate anchoring strategy for synergistically modulating crystallization and stability towards efficient perovskite solar cells - Ping Hu; Wenbo Zhou; Junliang Chen; Xin Xie; Jingwei Zhu; Yuxin Zheng; Yafeng Li; Junming Li; Mingdeng Wei (Chemical Engineering Journal, 2024)

The designation of intrinsic flame-retarding vinyl ester resins with high mechanical property, optical transparency and degradability - Ying-Ming Li; Shuang-Lin Hu; Hang-Ping Fang; Yao Deng; Chang-De Yang; De-Yi Wang (Chemical Engineering Journal, 2024)

Identification of hub genes that variate the qCSS12-mediated cold tolerance between indica and japonica rice using WGCNA - Ping Gan; Xianglan Luo; Hanxing Wei; Yunfei Hu; Rongbai Li; Jijing Luo (Plant Cell Reports, 2024)

Dynamic assessment of dust hazard risk in the reconstruction of old industrial buildings: coupling effects of dust distribution and personnel trajectories - Wei Tian; Aoxiang Hu; Keyun Li; Ping Guo; Qing Chai; Ruihao Ma (Environmental Science and Pollution Research, 2023)

Effects of single and combined contamination of total petroleum hydrocarbons and heavy metals on soil microecosystems: Insights into bacterial diversity, assembly, and ecological function - Du Zhang; Qi Hu; Bing Wang; Junwen Wang; Can Li; Ping You; Rui Zhou; Weimin Zeng; Xueduan Liu; Qian Li (Chemosphere, 2023)

Interactions between CuO NPs and PS: The release of copper ions and oxidative damage - Yan Cao; Senlin Tian; Yingxue Geng; Linfeng Zhang; Qun Zhao; Jie Chen; Yingjie Li; Xuewei Hu; Jianhong Huang; Ping Ning (Science of The Total Environment, 2023)

Enhanced resuscitation of anammox granular sludge by adding folate: A perspective from the growth factor - Chao Pan; Leiyan Guo; Yang Yu; Wenji Li; Dongdong Xu; Wenda Chen; Lin Zhu; Baolan Hu; Ping Zheng; Meng Zhang (Chemical Engineering Journal, 2023)

Anti-freezing hydrogel thermocells with confined microcrystallization for enhanced low-grade heat harvest - Ping-Fan Li; Ting-Yuan Hu; Tao Luo; Zhuang Liu; Xiao-Jie Ju; Rui Xie; Da-Wei Pan; Wei Wang; Liang-Yin Chu (Chemical Engineering Journal, 2023)

Gas barrier coating based on cellulose nanocrystals and its preservation effects on mango - Mingxia Li; Zhenxu Shi; Shulin He; Qiang Hu; Ping Cai; Lin Gan; Jin Huang; Yongqiang Zhang (Carbohydrate Polymers, 2023)

Association between thermal stress and cardiovascular mortality in the subtropics - Maidina Jingesi; Shuhua Lan; Jing Hu; Mengyi Dai; Suli Huang; Siyi Chen; Ning Liu; Ziquan Lv; Jiajia Ji; Xiaoheng Li; Peng Wang; Jinquan Cheng; et al. (International Journal of Biometeorology, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

Relationship of individual and mixed urinary metals exposure with liver function in the China National Human Biomonitoring (CNHBM) of Zhejiang Province - Ping Cheng; Yi Tao; Jinfeng Hu; Hongxin Wang; Ruifang Zhao; Shenghua Mei; Yin Yang; Fugen Ye; Zhijian Chen; Hao Ding; Mingluan Xing; Peiwei Xu; et al. (Chemosphere, 2023)

Baicalin mitigates nephropathogenic infectious bronchitis virus infection-induced spleen injury via modulation of mitophagy and macrophage polarization in Hy-Line chick - Guanming Tian; Cheng Huang; Zhengqing Li; Zhihua Lu; Chenlu Feng; Yu Zhuang; Guyue Li; Ping Liu; Guoliang Hu; Xiaona Gao; Xiaoquan Guo (Veterinary Microbiology, 2023)

Recent advances in tea seeds (Camellia Sinensis (L.) O. Kuntze): Active ingredients, health effects, and potential applications - Su Zhou; Zhiying Li; Haizhao Song; Hao Hu; Shicheng Ma; Yike Tao; Zhilong Hao; Xinyu Feng; Yani Pan; Shuying Gong; Fangyuan Fan; Ping Chen; et al. (Trends in Food Science & Technology, 2023)

Extraction and characterization of anti-virus anthraquinones from Nicotiana tabacum-derived Aspergillus oryzae YNCA1220 - Feng-Xian Yang; Yue-Yu Ma; Yu-Ping Wu; Gao-Kun Zhao; Yong-Ping Li; Zhen-Jie Li; Xue-Mei Li; Yin-Ke Li; Wei-Guang Wang; Min Zhou; Guang-Hui Kong; Qiu-Fen Hu (Pesticide Biochemistry and Physiology, 2023)

Abamectin induced brain and liver toxicity in carp: The healing potential of silybin and potential molecular mechanisms - Xinyu Wu; Yue Xin; Yeyun Ma; Kaixin Ping; Qiulu Li; Ying Sun; Zunhan Hu; Jingquan Dong (Fish & Shellfish Immunology, 2023)

Genetic variations of CYP3A4 on the metabolism of itraconazole in vitro - Sai-li Xie; Xiayan Zhu; Nanyong Gao; Qianmeng Lin; Chaojie Chen; Yun-jun Yang; Jian-ping Cai; Guo-xin Hu; Ren-ai Xu (Food and Chemical Toxicology, 2023)

Aging effects on residential biomass burning emissions under quasi-real atmospheric conditions - Siyuan Li; Dantong Liu; Yangzhou Wu; Kang Hu; Xiaotong Jiang; Ping Tian; Jiujiang Sheng; Baiwan Pan; Delong Zhao (Environmental Pollution, 2023)

Improvement of anti-wetting and anti-scaling properties in membrane distillation process by a facile fluorine coating method - Zhan Li; Pengfei Zhang; Yu-Hsuan Chiao; Kecheng Guan; Ralph Rolly Gonzales; Ping Xu; Zhaohuan Mai; Guorong Xu; Mengyang Hu; Tooru Kitagawa; Tomohisa Yoshioka; Hideto Matsuyama (Desalination, 2023)

Uniform lithium deposition regulated by lithiophilic Mo3N2/MoN heterojunction nanobelts interlayer for stable lithium metal batteries - Xiaojuan Zhang; Liang Zhou; Kunpeng Hu; Dandan Gao; Shuo Tang; Li He; Yuanfu Chen; Ping Zhang; Zhigang Zhang (Chemical Engineering Journal, 2023)

Alteromonas Aquimaris sp. nov., Isolated from Surface Seawater - Qin Wang; Xin-Yuan Hu; Li-Ping Sun; Hui-Jing Niu; Cai-Xia Pei; Yi Li; Cheng-Qiang Xia (Current Microbiology, 2023)

Sedimentary Environment Interpretation and Organic Matter Enrichment of the Lower Cambrian Shuijingtuo Shale in the Yichang Slope, South China: Insight from Sedimentary Geochemical Proxies with Major/Trace Elements - Sile Wei; Mingyi Hu; Sheng He; Wei Yang; Qing He; Quansheng Cai; Ping Li (Journal of Marine Science and Engineering, 2023)
The vertical geochemical variations in total organic carbon (TOC) content and major and trace elements of the Lower Cambrian Shuijingtuo Formation from the Yichang Slope in the Upper Yangtze were investigated to assess the environmental conditions (redox conditions, water mass restriction, terrigenous input, relative sea-level terrestrial, and paleoproductivity) and to determine the primary controlling factors for organic matter enrichment. The Shuijingtuo Shale is divided into three intervals. The lithofacies of interval I are mainly black siliceous shale with high TOC content, and interval II is mainly black siliceous shale with moderate TOC content. Interval III consists of black, clay-rich siliceous shale and dark-gray calcareous shale and is characterized by a low TOC content. The effects of diagenesis and hydrothermal activity on the elements were evaluated prior to analyzing the environmental condition. There are good positive correlations between TOC and U/Al or Mo/Al ratios, suggesting that major/trace elements still retain the geochemical signature of the sedimentary environment. Meanwhile, the geochemical proxies consisting of Al, Fe, Mn, and Ti indicate that the study area did not experience hydrothermal deposits. The redox proxies (U/Th, Corg:Ptot, and MoEF–UEF) indicate that the interval I samples were formed under a strong reducing condition. The diagram of TOC vs. Mo indicates that the water mass was moderately restricted during the deposition of interval I shales. Proxies of terrigenous input and relative sea-level (Zr/Al and Zr/Rb) suggest that the organic-rich shales at the bottom were deposited under a relatively high sea-level and experienced minimal input of terrigenous debris from the source area. Additionally, the paleoproductivity indicated by Sibio and (Ni + Cu + Zn)/Al was high for interval I samples. During the interval II period, the relative sea-level began to decline, the seawater still remained in reducing conditions, and there was no change in the productivity, but the input of terrigenous debris increased significantly. In the interval III depositional period, the relative sea-level continued to decrease, the seawater shifted to a dysoxic condition, and the paleoproductivity was also at a lower level. The evolution of the sedimentary environment indicates that the high TOC content in the interval I samples is mainly attributed to the strong reducing condition, the preservation condition and debris dilution together control the organic matter content within the interval II samples, and the low TOC content within the interval III samples is constrained by a combination of the poor preservation conditions and lower paleoproductivity.

Spatial and molecular variations in forest topsoil dissolved organic matter as revealed by FT-ICR mass spectrometry - Ming Sheng; Shuang Chen; Cong-Qiang Liu; Qinglong Fu; Donghuan Zhang; Wei Hu; Junjun Deng; Libin Wu; Ping Li; Zhifeng Yan; Yong-Guan Zhu; Pingqing Fu (Science of The Total Environment, 2023)

Clerodane diterpenoids from the Uygur medicine Salvia deserta with immunosuppressive activity - Xue Ren; Xin Yuan; Shan-Shan Jiao; Xiao-Ping He; Hong Hu; Juan-Juan Kang; Shi-Hong Luo; Yan Liu; Kai Guo; Sheng-Hong Li (Phytochemistry, 2023)

Evaluating drought monitoring utility of the top-down and bottom-up satellite precipitation products over mainland China from a three-dimensional perspective - Yuefen Zhang; Chuanhao Wu; Pat J.-F. Yeh; Jianzhu Li; Jiayun Li; Bill X. Hu; Ping Feng (Journal of Hydrology, 2023)

Association between urinary neonicotinoid insecticide levels and dyslipidemia risk: A cross-sectional study in Chinese community-dwelling elderly - Jian Sun; Pei He; Rui Wang; Zhong-Yuan Zhang; Yu-Qing Dai; Xiao-Yu Li; Si-Yu Duan; Cai-Ping Liu; Hao Hu; Guang-Jun Wang; Yan-Ping Zhang; Fei Xu; et al. (Journal of Hazardous Materials, 2023)

Impact of bentonite on greenhouse gas emissions during pig manure composting and its subsequent application - Jia-Ping Wu; Meng-Ling Li; Yan Wang; Shan Lin; Rong-Gui Hu; Rong-Biao Xiang (Journal of Environmental Management, 2023)

Persulfate activation with nitrogen and sulfur co-doped porous biochar to remove thiamethoxam: A combination of radicals and nonradicals - Ziqi Wang; Xiangyu Meng; Yewen Yang; Honghui Jiang; Xinyuan Tan; Jingju Cai; Meifang Li; Ke Ouyang; Tingting Li; Ping Wang; Hui Wang; Xinjiang Hu (Journal of Environmental Chemical Engineering, 2023)

Fermentation of Rosa roxburghii Tratt by Limosilactobacillus fermentum NCU001464: Physicochemical characteristics and biological activity - Hai-Li Zhou; Fei Peng; Jia-Xin Lin; Li-Ping Hu; Mingyong Xie; Tao Xiong (Food Bioscience, 2023)

Corrigendum to ‘Maltol attenuates polystyrene nanoplastic-induced enterotoxicity by promoting AMPK/mTOR/TFEB-mediated autophagy and modulating gut microbiota’ [Environmental Pollution, Maltol attenuates polystyrene nanoplastic-induced enterotoxicity by promoting AMPK/mTOR/TFEB-mediated autophagy and modulating gut microbiota, Volume 322 (2023), 121202] - Ming-hui Jin; Jun-nan Hu; Ming Zhang; Zhaojie Meng; Guo-ping Shi; Zi Wang; Wei Li (Environmental Pollution, 2023)

Near-infrared-triggered chirality-dependent photodynamic therapy based on hybrid upconversion nanoparticle hydrogels - Tianyong Guan; Yan Liu; Jiayao Li; Mingmao Chen; Xiaoying Shang; Ping Hu; Renfu Li; Hang Gao; Datao Tu; Wei Zheng; Xueyuan Chen (Chemical Engineering Journal, 2023)

Ecological distribution of anaerobic granular sludge towards efficient anaerobic reactor - Wenda Chen; Huiming Tang; Dongdong Xu; Wenji Li; Chao Pan; Leiyan Guo; Da Kang; Baolan Hu; Ping Zheng; Meng Zhang (Bioresource Technology, 2023)

Multi-trait functional diversity predicts ecosystem multifunctionality under nitrogen addition in a desert steppe - Ya Hu; Aixia Guo; Xiangyun Li; Ping Yue; Shenglong Zhao; Peng Lv; Xiaoan Zuo (Plant and Soil, 2023)

Trichoscopy for early diagnosis and follow-up of pet-related neonatal tinea capitis - Hui-Lin Zhi; Xiu-Jiao Xia; Hong Shen; Wen-Wen Lv; Yan Zhong; Bo Sang; Qiu-Ping Li; Ze-Hu Liu (Mycopathologia, 2023)

Association of urinary bisphenols with thyroid function in the general population: a cross-sectional study of an industrial park in China - Yang Hu; Shiming Lai; Ying Li; Xiaodong Wu; Mingluan Xing; Xueqing Li; Dandan Xu; Yuan Chen; Jie Xiang; Ping Cheng; Xiaofeng Wang; Zhijian Chen; et al. (Environmental Science and Pollution Research, 2023)

Ambient black carbon variations and emission characteristics of typical Chinese vessels in the Yangtze River Delta, China - Puzhen Zhang; Chen Guo; Yongjie Wei; Zhanshan Wang; Zhigang Li; Yan Qian; Xiaoqian Li; Xiaojing Zhu; Ping Xu; Jun Shen; Wenchao Xue; Jun Hu (Environmental Science and Pollution Research, 2023)

Functional evaluation of CYP2C19 and CYP3A4 gene polymorphism on ibuprofen metabolism - Ling-Jing Yuan; Xiang-Yu Li; Jin-Huan Ni; Jing Wang; Xiao-Yu Xu; Jian-Chao Luo; Qi Zhou; Guo-Xin Hu; Jian-Ping Cai; Jian-Chang Qian (Toxicology and Applied Pharmacology, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Dammarane-type saponins from Gynostemma pentaphyllum and their anti-aging activities via up-regulating mitochondria related proteins - Hai-Zhen Liang; Peng-Xin Lu; Li-Li Chu; Gang Li; Chuan-Biao Li; Xiao-Juan Chen; Jie Zhang; Juan Song; Tao Zhang; Ying Luo; Ying Hu; Bai-Ping Ma (Phytochemistry, 2023)

Early Paleozoic subduction imprints of the Proto-Tethys Ocean: Evidence from the Appinite–Diorite–Granodiorite complex in East Kunlun, Northern Tibet - Yang-Ming Hu; Xiao-Wei Li; Xuan-Xue Mo; Lin Li; Kai Wang; Bing-Zhang Wang; Xiao-Ping Gong; Guo-Chen Dong; Yan-Bin Liu (Lithos, 2023)

Effect of safflower oil and magnetic field-modified soy 11S globulin on rheological and emulsifying properties of oil-in-water emulsions - Zhuang-Li Kang; Jing-jie Xie; Zhong-liang Hu; Yan-ping Li; Han-Jun Ma (Food Hydrocolloids, 2023)

Towards intensified preservation technology of anammox granular sludge: Insights into the role of energy support - Chao Pan; Wenji Li; Dongdong Xu; Wenda Chen; Leiyan Guo; Da Kang; Baolan Hu; Ping Zheng; Meng Zhang (Chemical Engineering Journal, 2023)

Genome-Wide Identification of MabHLH Transcription Factors Family Response to Magnesium Deficiency Stress in Banana (Musa paradisiaca AA) - Ping Li; Xinping Li; Shihan Zhou; Haiyan Hu (Tropical Plant Biology, 2023)

Antimony(III) removal by biogenic manganese oxides formed by Pseudomonas aeruginosa PA-1: kinetics and mechanisms - Qing Li; Yun He; Aijiang Yang; Xia Hu; Fang Liu; Jincheng Mu; Shixue Mei; Lin-Ping Yang (Environmental Science and Pollution Research, 2023)

Schizophrenia in the genetic era: a review from development history, clinical features and genomic research approaches to insights of susceptibility genes - Ye Lv; Lin Wen; Wen-Juan Hu; Chong Deng; Hui-Wen Ren; Ya-Nan Bao; Bo-Wei Su; Ping Gao; Zi-Yue Man; Yi-Yang Luo; Cheng-Jie Li; Zhi-Xin Xiang; et al. (Metabolic Brain Disease, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Face mask derived micro(nano)plastics and organic compounds potentially induce threat to aquatic ecosystem security revealed by toxicogenomics-based assay - Yan-Jun Liu; He-Yun Yang; Yan-Yun Hu; Zheng-Hao Li; Hao Yin; Yun-Tian He; Keng-Qiang Zhong; Li Yuan; Xing Zheng; Guo-Ping Sheng (Water Research, 2023)

Mechanism of aconitine mediated neuronal apoptosis induced by mitochondrial calcium overload caused by MCU - Chen Jiang; Jun Shen; Chun Wang; Yongjie Huang; Linbo Wang; Yiran Yang; Wen Hu; Ping Li; Haiying Wu (Toxicology Letters, 2023)

Quantitative evaluation for the sources and aging processes of organic aerosols in urban Guangzhou: Insights from a comprehensive method of dual‑carbon isotopes and macro tracers - Fan Jiang; Junwen Liu; Zhineng Cheng; Ping Ding; Sanyuan Zhu; Xin Yuan; Wei Chen; Zhisheng Zhang; Zheng Zong; Chongguo Tian; Weiwei Hu; Junyu Zheng; et al. (Science of The Total Environment, 2023)

Enzymatic activity of 38 CYP2C9 genotypes on ibuprofen - Ling-jing Yuan; Xiang-yu Li; Feng Ye; Xin-yue Li; Qing-qing Li; Yun-shan Zhong; Shi-yu Wang; Ya-hui Wang; Guo-xin Hu; Jian-ping Cai; Jun-wei Li (Food and Chemical Toxicology, 2023)

AIWW: a new nutrition-screening tool for the oncologic population - Yi-Zhong Ge; Zhen-Ming Fu; Qi Zhang; Meng-Meng Song; Guo-Tian Ruan; Xi Zhang; Xiao-Wei Zhang; Xiang-Rui Li; Kang-Ping Zhang; Meng Tang; Xiao-Yue Liu; Ming Yang; et al. (Science China Life Sciences, 2023)

TFEB: a double-edged sword for tumor metastasis - Jun-Hu Hu; Shou-Ye Li; Li-Hua Yu; Zhen-Rong Guan; Ya-Ping Jiang; Die Hu; Hao-Jie Wang; Li-Ping Zhao; Zhao-Huang Zhou; Ya-Xin Yan; Tian Xie; Zhi-Hui Huang; et al. (Journal of Molecular Medicine, 2023)

Effects of drug-drug interactions and CYP3A4 variants on alectinib metabolism - Ya-nan Liu; Jie Chen; Jing Wang; Qingqing Li; Guo-xin Hu; Jian-ping Cai; Guanyang Lin; Ren-ai Xu (Archives of Toxicology, 2023)

Determinants affecting the blood mercury levels of preschool children in Shanghai, China: A cross-sectional study - Xi Xu; Yu-Qing Wang; Chen-Yin Dong; Chun-Ping Hu; Li-Na Zhang; Zhen-Yan Gao; Min-Ming Li; Su-Su Wang; Chong-Huai Yan (Environmental Science and Pollution Research, 2023)

Photoaged microplastics induce neurotoxicity via oxidative stress and abnormal neurotransmission in zebrafish larvae (Danio rerio) - Ping Ding; Chongdan Xiang; Xintong Li; Haibo Chen; Xiaoxia Shi; Xin Li; Chushan Huang; Yunjiang Yu; Jianying Qi; Adela Jing Li; Lijuan Zhang; Guocheng Hu (Science of The Total Environment, 2023)

Sinomenine ameliorates rheumatoid arthritis by modulating tryptophan metabolism and activating aryl hydrocarbon receptor via gut microbiota regulation - Zheng-Meng Jiang; Su-Ling Zeng; Tian-Qing Huang; Yang Lin; Fang-Fang Wang; Xing-Jiao Gao; Jing Li; Ping Li; E-Hu Liu (Science Bulletin, 2023)

Probing the formation of soluble humins in catalytic dehydration of fructose to 5-hydroxymethylfurfural over HZSM-5 catalyst - Linzhen Li; Yexin Hu; Hui Li; Ping Hu; Zhidan Xue; Di Wu; Changwei Hu; Liangfang Zhu (Fuel, 2023)

Different dietary fibers unequally remodel gut microbiota and charge up anti-obesity effects - Jia-Jia Wen; Ming-Zhi Li; Jie-Lun Hu; Jiang Wang; Zhi-Qiang Wang; Chun-Hua Chen; Jing-Rui Yang; Xiao-Jun Huang; Ming-Yong Xie; Shao-Ping Nie (Food Hydrocolloids, 2023)

Influence of crack characteristics on the morphological development of Benggang and hydrological processes - Wei-ping Liu; Shu-han Wang; Si-wen Tian; Guo-quan Ouyang; Li-na Hu; Zhi-jun Yuan (Journal of Mountain Science, 2023)

Fluorescence Properties and Chemical Composition of Fine Particles in the Background Atmosphere of North China - Ping Li; Siyao Yue; Xiaoyang Yang; Di Liu; Qiang Zhang; Wei Hu; Shengjie Hou; Wanyu Zhao; Hong Ren; Gang Li; Yuanguan Gao; Junjun Deng; et al. (Advances in Atmospheric Sciences, 2023)

Daphnia magna uptake and excretion of luminescence‐labelled polystyrene nanoparticle as visualized by high sensitivity real-time optical imaging - Yu-Hang Zhang; Rong-Yao Gao; Ze-Jun Wang; Qian-Qian Shao; Ya-Wen Hu; Hua-Bing Jia; Xiao-Jing Liu; Feng-Qin Dong; Li-Min Fu; Jian-Ping Zhang (Chemosphere, 2023)

Real-time perception of rock–machine interaction information in TBM tunnelling using muck image analysis - Wei-Qiang Xie; Xiao-Ping Zhang; Xiao-Li Liu; Chen-Yu Xu; Xin-Fang Li; Dan-Qing Song; Qing Ma; Nan Hu (Tunnelling and Underground Space Technology, 2023)

Secoiridoids from the traditional Chinese medicine Swertia pseudochinensis - Jie Liu; Qin Yan; Li-Xia Wang; Xiao-Ping He; Hong Hu; Yan-Chun Liu; Dan Li; Yan Liu; Kai Guo; Sheng-Hong Li (Phytochemistry, 2023)

Three new isoquinoline alkaloids from the cigar tobacco-derived endophytic fungus Aspergillus felis - Yue-Yu Ma; Gui Pu; Xue-Ju Cha; Rui-Feng Xiong; Guang-Hai Zhang; Heng Yao; Mei-Fen Bao; Guang-Hui Kong; Yin-Ke Li; Qiu-Fen Hu; Yu-Ping Wu (Phytochemistry Letters, 2023)

Bioactive triterpenoids from the traditional Chinese medicine Swertia mileensis - Xin Yuan; Qin Yan; Hong Hu; Xiao-Ping He; Li-Xia Wang; Yan-Chun Liu; Yan Liu; Kai Guo; Sheng-Hong Li (Phytochemistry Letters, 2023)

Tetracycline degradation by persulfate activated with nitrogen magnetic graphene oxide confined Fe/Co dual single-atom catalyst: Performance and degradation mechanism - Chenxi Huang; Meifang Li; Ping Wang; Shiyu Song; Beixia Chai; Meijuan Zhang; Xinjiang Hu; Jingju Cai; Shaohua Wu; Qingyun He (Journal of Environmental Chemical Engineering, 2023)

PSS modified by 3-aminopropyltrimethoxysilane linking large-area GNPs/PSS to silicone rubber with stable interface combination for high sensitivity flexible resistive sensor - Han Feng; Ping Liu; Xu Guo; Junliang Li; Yifan Sun; Shunge Wu; Ruohai Hu; Zhi Liu; Helei Tian; Yuanming Ma; Caixia Liu; Houzhu Huang; et al. (Chemical Engineering Journal, 2023)

Orientated inhibition of humin formation in efficient production of levulinic acid from cellulose with high substrate loading: Synergistic role of additives - Ping Hu; Yexin Hu; Hui Li; Linzhen Li; Zhidan Xue; Di Wu; Juan Zhao; Changwei Hu; Liangfang Zhu (Carbohydrate Polymers, 2023)

Efficient production of cordycepin by engineered Yarrowia lipolytica from agro-industrial residues - Xi-Yu Duan; Hu-Hu Liu; Li-Ping Song; Chong Wang; Hui Yang; Xiang-Yang Lu; Xiao-Jun Ji; Yun Tian (Bioresource Technology, 2023)

High nitrogen addition induces functional trait divergence of plant community in a temperate desert steppe - Jingjuan Qiao; Xiaoan Zuo; Ping Yue; Shaokun Wang; Ya Hu; Xinxin Guo; Xiangyun Li; Peng Lv; Aixia Guo; Shanshan Sun (Plant and Soil, 2023)

Hippocampus: Molecular, Cellular, and Circuit Features in Anxiety - Hu-Jiang Shi; Shuang Wang; Xin-Ping Wang; Rui-Xin Zhang; Li-Juan Zhu (Neuroscience Bulletin, 2023)

Doublecortin-Expressing Neurons in Human Cerebral Cortex Layer II and Amygdala from Infancy to 100 Years Old - Ya-Nan Li; Dan-Dan Hu; Xiao-Lu Cai; Yan Wang; Chen Yang; Juan Jiang; Qi-Lei Zhang; Tian Tu; Xiao-Sheng Wang; Hui Wang; Ewen Tu; Xiao-Ping Wang; et al. (Molecular Neurobiology, 2023)

Multiple Episodes of Zircon Growth during Anatectic Metamorphism of Metasedimentary Rocks in Collisional Orogens: Constraints from Felsic Granulites in the Bohemian Massif - Guang Yang; Ren-Xu Chen; Yong-Fei Zheng; Qiong-Xia Xia; Yong-Jie Yu; Kun Li; Zhaochu Hu; Bing Gong; Xiang-Ping Zha (Journal of Earth Science, 2023)

Blood selenium level can alleviate the nephrotoxicity of lead and cadmium in the general population of the United States: a retrospective cross section analysis of population‐based nationally representative data - Yumeng Shi; Huan Hu; Zuxiang Wu; Zhiqiang Chen; Ping Li (Environmental Science and Pollution Research, 2023)

UV-aged microplastics induces neurotoxicity by affecting the neurotransmission in larval zebrafish - Chongdan Xiang; Haibo Chen; Xiaolin Liu; Yao Dang; Xin Li; Yunjiang Yu; Bei Li; Xintong Li; Yanan Sun; Ping Ding; Guocheng Hu (Chemosphere, 2023)

Transcatheter closure of perimembranous ventricular septal defect using a novel fully bioabsorbable occluder: multicenter randomized controlled trial - Shouzheng Wang; Zefu Li; Yunbing Wang; Tianli Zhao; Xuming Mo; Taibing Fan; Jianhua Li; Tao You; Rundi Deng; Wenbin Ouyang; Weiwei Wang; Chuangnian Zhang; et al. (Science Bulletin, 2023)

Novel bacteriophage-mediated β-lactamase-encoding genes and their risk assessment in environmental communities - Xinxin Li; Yibao Chen; Dayue Hu; Shuang Wang; Xiangmin Li; Huanchun Chen; Ping Qian (Process Safety and Environmental Protection, 2023)

Restoration of sedimentary environment and geochemical features of deep marine Longmaxi shale and its significance for shale gas: A case study of the Dingshan area in the Sichuan Basin, South China - Yue Feng; Xianming Xiao; Ping Gao; Enze Wang; Dongfeng Hu; Ruobing Liu; Gang Li; Chengang Lu (Marine and Petroleum Geology, 2023)

Molecular imprinted electrochemical sensor for ovalbumin detection based on boronate affinity and signal amplification approach - Hao Fu; Zhenyu Bai; Ping Li; Xiaoyang Feng; Xueping Hu; Xingliang Song; Lingxin Chen (Food Chemistry, 2023)

Intelligent shielding material based on VO2 with tunable near-field and far-field electromagnetic response - Si-Yuan Liao; Xiao-Yun Wang; Hai-Peng Huang; Yu-Ying Shi; Qiao-Feng Wang; You-Gen Hu; Peng-Li Zhu; Rong Sun; Ching-Ping Wong; Yan-Jun Wan (Chemical Engineering Journal, 2023)

Rational design of an in-build quasi-solid-state electrolyte for high-performance lithium-ion batteries with the silicon-based anode - Enyou Zhao; Shiqiang Luo; Anyi Hu; Zhu Liao; Chenxi Huang; Orita Akihiro; Ping Jiang; Li Yang (Chemical Engineering Journal, 2023)

Identification of Heterophilic Epitopes of H1N1 Influenza Virus Hemagglutinin - Jing-ying Sun; Chun-yan Guo; Guo-rong Wang; Li-ting Yan; Qing Feng; Yan Li; Xue-ping Huo; Xin Xie; Jun Hu; Li-jun Sun (Current Microbiology, 2023)

Adaptive Graph-Learning Convolutional Network for Multi-Node Offshore Wind Speed Forecasting - Jingjing Liu; Xinli Yang; Denghui Zhang; Ping Xu; Zhuolin Li; Fengjun Hu (Journal of Marine Science and Engineering, 2023)
Multi-node wind speed forecasting is greatly important for offshore wind power. It is a challenging task due to unknown complex spatial dependencies. Recently, graph neural networks (GNN) have been applied to wind forecasting because of their capability in modeling dependencies. However, existing methods usually require a pre-defined graph structure, which is not optimal for the downstream task and limits the application scope of GNN. In this paper, we propose adaptive graph-learning convolutional networks (AGLCN) that can automatically infer hidden associations among multi-nodes through a graph-learning module. It simultaneously integrates the temporal and graph convolutional modules to capture temporal and spatial features in the data. Experiments are conducted on real-world multi-node wind speed data from the China Sea. The results show that our model achieves state-of-the-art results in all multi-scale wind speed predictions. Moreover, the learned graph can reveal spatial correlations from a data-driven perspective.

Histone methyltransferase SETDB1 promotes osteogenic differentiation in osteoporosis by activating OTX2-mediated BMP-Smad and Wnt/β-catenin pathways - Lianying Hu; Zhen Cheng; Lunan Wu; Liangliang Luo; Ping Pan; Shujin Li; Qiyu Jia; Ning Yang; Bin Xu (Human Cell, 2023)

Comparison of two commercial methods with a UHPLC–MS/MS method for the determination of multiple mycotoxins in cereals - Ying-yue Zhang; Mei-juan Zhao; Chun-yao Liu; Kai Ma; Tian-yu Liu; Fei Chen; Li-na Wu; De-jun Hu; Guang-ping Lv (Food Chemistry, 2023)

Maltol attenuates polystyrene nanoplastic-induced enterotoxicity by promoting AMPK/mTOR/TFEB-mediated autophagy and modulating gut microbiota - Ming-hui Jin; Jun-nan Hu; Ming Zhang; Zhaojie Meng; Guo-ping Shi; Zi Wang; Wei Li (Environmental Pollution, 2023)

Global/local buckling analysis of thin-walled I-section beams via hierarchical one-dimensional finite elements - Yichen Yang; Yanchuan Hui; Ping Li; Jie Yang; Qun Huang; Gaetano Giunta; Salim Belouettar; Heng Hu (Engineering Structures, 2023)

Bioaugmentation with Tetrasphaera to improve biological phosphorus removal from anaerobic digestate of swine wastewater - Jiaxin Wang; Chiqian Zhang; Ping Li; Hui Xu; Weiwu Wang; Weizhao Yin; Jinhua Wu; Zhiqiang Hu (Bioresource Technology, 2023)

An in-situ strategy to construct uracil-conjugated covalent organic frameworks with tunable fluorescence/recognition characteristics for sensitive and selective Mercury(II) detection - Xi-Rui Deng; A-Wei Hu; Sheng-Qian Hu; Wen-Li Yang; Chen Sun; Sai-Jin Xiao; Gui-Ping Yang; Qiong-Qing Zheng; Ru-Ping Liang; Li Zhang; Jian-Ding Qiu (Analytica Chimica Acta, 2023)

Tailoring enzymatic loading capacity on CdS nanorods@ZnIn2S4 nanosheets 1D/2D heterojunctions: Toward ultrasensitive photoelectrochemical bioassay of tobramycin - Rui Hu; Ben-Fang Xu; Yadong Xue; Zhi-Zhi Xu; Ai-Jun Wang; Li-Ping Mei; Pei Song; Jiu-Ju Feng (Chemosphere, 2023)

Genome-wide transcriptome analysis uncovers gene networks regulating fruit quality and volatile compounds in mango cultivar 'Tainong' during postharvest - Li Li; Ping Yi; Jian Sun; Jie Tang; Guoming Liu; Jinfeng Bi; Jianwen Teng; Meijiao Hu; Fang Yuan; Xuemei He; Jinfeng Sheng; Ming Xin; et al. (Food Research International, 2023)

Tea polyphenol and epigallocatechin gallate ameliorate hyperlipidemia via regulating liver metabolism and remodeling gut microbiota - Jia-Jia Wen; Ming-Zhi Li; Chun-Hua Chen; Tao Hong; Jing-Rui Yang; Xiao-Jun Huang; Fang Geng; Jie-Lun Hu; Shao-Ping Nie (Food Chemistry, 2023)

Molecular characterization of a teleost-specific toll-like receptor 22 (tlr22) gene from yellow catfish (Pelteobagrus fulvidraco) and its transcriptional change in response to poly I:C and Aeromonas hydrophila stimuli - Xiu-Ying Wei; Jun Wang; Sheng-Tao Guo; Yun-Yun Lv; Yan-Ping Li; Chuan-Jie Qin; Yuan-Chao Zou; Qing-Chao Shi; Peng Hu; Xiao-Qin Xiong; Yang He; Rui Li; et al. (Fish & Shellfish Immunology, 2023)

Solidification and stabilization of Pb–Zn mine tailing with municipal solid waste incineration fly ash and ground granulated blast-furnace slag for unfired brick fabrication - Ping Wang; Jiangshan Li; Yuanan Hu; Hefa Cheng (Environmental Pollution, 2023)

Detecting ionizing radiation dose using composite hydrogel-based sensors - Li Jiang; Chengfang Zhang; Xinyue Xu; Rui Hu; Ping Zhang; Rensheng Wang; Xinjian Chen; Liang Hu (Chemical Engineering Journal, 2023)

Effects of altered precipitation patterns on soil nitrogen transformation in different landscape types during the growing season in northern China - Peng Lv; Shanshan Sun; Xueyong Zhao; Yuqiang Li; Shenglong Zhao; Jing Zhang; Ya Hu; Aixia Guo; Ping Yue; Xiaoan Zuo (CATENA, 2023)

New remains of Ailuropoda melanoleuca baconi from Yanjinggou, China: Throwing light on the evolution of giant pandas during the Pleistocene - Haiqian Hu; Haowen Tong; Qingfeng Shao; Guangbiao Wei; Haidong Yu; Jingsong Shi; Xunqian Wang; Can Xiong; Yu Lin; Ning Li; Zhaoying Wei; Ping Wang; et al. (Journal of Mammalian Evolution, 2023)

Gas in place and its controlling factors of deep shale of the Wufeng-Longmaxi Formations in the Dingshan area, Sichuan Basin - Ping Gao; Xianming Xiao; Dongfeng Hu; Ruobing Liu; Fei Li; Qin Zhou; Yidong Cai; Tao Yuan; Guangming Meng (Frontiers of Earth Science, 2023)

Effects of Internal Waves on Acoustic Temporal Coherence in the South China Sea - Fei Gao; Ping Hu; Fanghua Xu; Zhenglin Li; Jixing Qin (Journal of Marine Science and Engineering, 2023)
An acoustic experiment to measure the sound field during internal wave activity was conducted in the South China Sea. During the experiment, a train of strong internal solitary waves (ISWs) moved from the acoustic source to the receiver array along the acoustic path, and the propagation direction of the ISWs train was almost parallel to the acoustic path. Here, a study of the characteristics and physical mechanisms of the acoustic temporal coherence in this scenario is reported. The temporal coherence was analyzed by using the simulation results and experimental data. The results show that the temporal correlation coefficients oscillate quasi-periodically with both time and time delay, and the predominant oscillation periods are the same as the periods of the ISWs. The predominant fluctuation frequencies of the sound field correspond to some specific modes and lead to the periodicity of the temporal correlation coefficients. In the shallow layer, the spectrum structures of the temporal correlation coefficients are simpler because of the fewer effective modes.

Contrasting relationships between plant-soil microbial diversity are driven by geographic and experimental precipitation changes - Xiaoan Zuo; Shanshan Sun; Shaokun Wang; Ping Yue; Ya Hu; Shengnlong Zhao; Xinxin Guo; Xiangyun Li; Min Chen; Xujun Ma; Hao Qu; Weigang Hu; et al. (Science of The Total Environment, 2023)

Source characterization of volatile organic compounds in urban Beijing and its links to secondary organic aerosol formation - Quan Liu; Jiujiang Sheng; Yangzhou Wu; Zhiqiang Ma; Junying Sun; Ping Tian; Delong Zhao; Xia Li; Kang Hu; Siyuan Li; Xiaojing Shen; Yangmei Zhang; et al. (Science of The Total Environment, 2023)

Impacts of PFOAC8, GenXC6, and their mixtures on zebrafish developmental toxicity and gene expression provide insight about tumor-related disease - Huinian Liu; Yu Chen; Wenli Hu; Yuan Luo; Ping Zhu; Shiqi You; Yunxuan Li; Zhaobiao Jiang; Xiushan Wu; Xin Li (Science of The Total Environment, 2023)

ARSCP: An antimicrobial residue surveillance cloud platform for animal-derived foods - Jun-Jun Yu; Ya-Lin Hu; Cheng-Zheng Liu; Shuai-Bin Wu; Zi-Jian Zheng; Ze-Hua Cui; Li Chen; Tian Wei; Shi-Kai Sun; Jun Ning; Xiang Wen; Qiu-Yue Diao; et al. (Science of The Total Environment, 2023)

Synthesis of cationic polymer decorated with halogen for highly efficient trapping 99TcO4-/ReO4- - You-Gan Wang; Qing-Hua Hu; Juan Huang; Wei Jiang; Li Zhang; Ru-Ping Liang; Jian-Ding Qiu (Journal of Hazardous Materials, 2023)

Metabolomics and proteomics reveal the toxicological mechanisms of florfenicol stress on wheat (Triticum aestivum L.) seedlings - Hanmei Chen; Jiaojun Jin; Shuhao Hu; Luoqin Shen; Ping Zhang; Zhiheng Li; Zhiguo Fang; Huijun Liu (Journal of Hazardous Materials, 2023)

Effect of phenol formaldehyde-associated microplastics on soil microbial community, assembly, and functioning - Hu Li; Qiu-Ping Luo; Sha Zhao; Yan-Yan Zhou; Fu-Yi Huang; Xiao-Ru Yang; Jian-Qiang Su (Journal of Hazardous Materials, 2023)

Preparation of XCu@TiO2 adsorbent for high-efficient PH3 removal in anaerobic environment and evaluation of desulfurization activity of deactivated adsorbent - Lijuan Jia; Xuejin Yang; Kaiqiang Hu; Jiayu Feng; Fang Wang; Kai Li; Xin Sun; Fei Wang; Ping Ning (Chemical Engineering Journal, 2023)

Holdup of sub-granules towards enhanced production of anammox sludge in a dual circulation sludge bed reactor - Dongdong Xu; Wenda Chen; Chao Pan; Wenji Li; Leiyan Guo; Da Kang; Ping Zheng; Baolan Hu; Meng Zhang (Chemical Engineering Journal, 2023)

Efficient fabrication of desert beetle-inspired micro/nano-structures on polypropylene/graphene surface with hybrid wettability, chemical tolerance, and passive anti-icing for quantitative fog harvesting - Wei-long Zhou; Ting Wu; Yu Du; Xiao-hu Zhang; Xin-chang Chen; Jin-bo Li; Heng Xie; Jin-ping Qu (Chemical Engineering Journal, 2023)

The detection of major clades and new species of Mallocybe (Inocybaceae, Agaricales) from China with elongate cheilocystidia - Jian-Hua Hu; Wen-Jie Yu; Lun-Sha Deng; Yu-Guang Fan; Tolgor Bau; Li-Ping Tang; Wen-Fei Lin; Chun-Ying Deng (Mycological Progress, 2023)

Chinese consensus guidelines for therapeutic drug monitoring of polymyxin B, endorsed by the Infection and Chemotherapy Committee of the Shanghai Medical Association and the Therapeutic Drug Monitoring Committee of the Chinese Pharmacological Society - Xiaofen Liu; Chenrong Huang; Phillip J. Bergen; Jian Li; Jingjing Zhang; Yijian Chen; Yongchuan Chen; Beining Guo; Fupin Hu; Jinfang Hu; Linlin Hu; Xin Li; et al. (Journal of Zhejiang University-SCIENCE B, 2023)

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

Polybrominated dibenzo-p-dioxins/furans and their chlorinated analogues in sediments from a historical hotspot for both brominated flame retardants and organochlorine pesticides - Mingyang Liu; Huiru Li; Aimin Song; Ping'an Peng; Hehuan Liu; Jianfang Hu; Guoying Sheng; Guangguo Ying (Environmental Pollution, 2023)

Regulating electronic structure by Mn doping for nickel cobalt hydroxide nanosheets/carbon nanotube to promote oxygen evolution reaction and oxidation of urea and hydrazine - Kaili Wu; Chenyang Cao; Keren Li; Chaojie Lyu; Jiarun Cheng; Hongyu Li; Pengfei Hu; Jiwen Wu; Woon-Ming Lau; Xixi Zhu; Ping Qian; Jinlong Zheng (Chemical Engineering Journal, 2023)

Corrigendum to “CD44-targeted hyaluronic acid-curcumin prodrug protects renal tubular epithelial cell survival from oxidative stress damage” [Carbohydrate Polymers 193 (2018) 268–280] - Jing-Bo Hu; Shu-Juan Li; Xu-Qi Kang; Jing Qi; Jia-Hui Wu; Xiao-Juan Wang; Xiao-Ling Xu; Xiao-Ying Ying; Sai-Ping Jiang; Jian You; Yong-Zhong Du (Carbohydrate Polymers, 2023)

An antibody cocktail with broadened mutational resistance and effective protection against SARS-CoV-2 - Chunyun Sun; Hang Chi; Fei Yuan; Jing Li; Ji Yang; Aihua Zheng; Fei Wang; Lingling Sun; Yanjing Zhang; Ping Hu; Lihua Jiao; Yongqiang Deng; et al. (Science China Life Sciences, 2023)

Abietane diterpenoids with neuroprotective activities from Phlegmariurus carinatus - Yang Liu; Qiang Wang; Dong-Kun Zheng; De Zhang; Zhen Xie; Jia-Wei Hu; Xin-Hua Xie; Jing Li; Shu-Ping Jiang (Natural Product Research, 2022)

Environmental impact of typical zinc smelting that implements solid waste collaborative utilization in China - Wei-Ning Liu; Yao Shi; Chen-Mu Zhang; Lang-Ming Liu; Hui-Quan Li; Bin Lu; Yuan-Bo Xie; Cai-Bei Zhuang; Tian-You Sun; Wei-Ping Liu; Xue Guan; Ying-Yan Hu (The International Journal of Life Cycle Assessment, 2022)

The landscape of aging - Yusheng Cai; Wei Song; Jiaming Li; Ying Jing; Chuqian Liang; Liyuan Zhang; Xia Zhang; Wenhui Zhang; Beibei Liu; Yongpan An; Jingyi Li; Baixue Tang; et al. (Science China Life Sciences, 2022)

Copper Toxicity Differentially Regulates the Seedling Growth, Copper Distribution, and Photosynthetic Performance of Citrus sinensis and Citrus grandis - Xin-yu Li; Mei-lan Lin; Ping-ping Hu; Ning-wei Lai; Zeng-rong Huang; Li-song Chen (Journal of Plant Growth Regulation, 2022)

An alkali-resistant metal–organic framework as halogen bond donor for efficient and selective removing of ReO4−/TcO4− - Qing-Hua Hu; Yu-Zhen Shi; Xin Gao; Li Zhang; Ru-Ping Liang; Jian-Ding Qiu (Environmental Science and Pollution Research, 2022)

Damage and Failure Characteristics and Constitutive Model of Copper-Bearing Skarns Disturbed by Hierarchical Dynamic Loading After Loading And Unloading - Chun Wang; Jia Li; Lu- ping Cheng; Xin-ru Li; Pan-long Zhang; Man-gu Hu (Rock Mechanics and Rock Engineering, 2022)

A1 Adenosine Receptor Activation Inhibits P2X3 Receptor–Mediated ATP Currents in Rat Dorsal Root Ganglion Neurons - Jia-Wei Hao; Wen-Long Qiao; Qing Li; Shuang Wei; Xue-Mei Li; Ting-Ting Liu; Chun-Yu Qiu; Wang-Ping Hu (Molecular Neurobiology, 2022)

Caffeine alleviates acute liver injury by inducing the expression of NEDD4L and deceasing GRP78 level via ubiquitination - Xing-Wang Hu; Xiang-Min Li; Ai-Min Wang; Yong-Ming Fu; Fang-Jie Zhang; Feng Zeng; Li-Ping Cao; Hui Long; Ying-Hui Xiong; Ji Xu; Jia Li (Inflammation Research, 2022)

Metabolomic analysis reveals the impact of ketoprofen on carbon and nitrogen metabolism in rice (Oryza sativa L.) seedling leaves - Huan Wang; Zhiheng Li; Hanmei Chen; Jiaojun Jin; Ping Zhang; Luoqin Shen; Shuhao Hu; Huijun Liu (Environmental Science and Pollution Research, 2022)

Enhanced M-CSF/CSF1R Signaling Closely Associates with PrPSc Accumulation in the Scrapie-Infected Cell Line and the Brains of Scrapie-Infected Experimental Rodents - Ying Xia; Cao Chen; Jia Chen; Chao Hu; Wei Yang; Lin Wang; Lian Liu; Li-Ping Gao; Yue-Zhang Wu; Dong-Dong Chen; Qi Shi; Zhi-Bao Chen; et al. (Molecular Neurobiology, 2022)

Exploring the R-ISS stage-specific regular networks in the progression of multiple myeloma at single-cell resolution - Ling Zhong; Xiao Yang; Yu Zhou; Jialing Xiao; Huan Li; Jiang Tao; Qian Xi; Chen Chu; Chenglong Li; Xi Yang; Chen Yang; Yi Zhang; et al. (Science China Life Sciences, 2022)

Feasibility Studies of Nebulized SARS-CoV-2 Neutralizing Antibody in Mice and Cynomolgus Monkeys - Jilei Jia; Zhaojuan Yin; Xiao Zhang; Huimin Li; Dan Meng; Qianqian Liu; Hongfang Wang; Meng Han; Shixiang Suo; Yan Liu; Ping Hu; Chunyun Sun; et al. (Pharmaceutical Research, 2022)
Purpose Neutralizing antibodies, administrated through intravenous infusion, have shown to be highly efficacious in treating mild and moderate COVID-19 caused by SARS-CoV-2 infection in the lung. However, antibodies do not transport across the plasma-lung barrier efficiently, and up to 100 mg/kg dose was used in human causing significant supply and cost burdens. This study was to explore the feasibility of nebulized antibodies inhalation delivery as an alternative route. Methods HB27, a potent RBD-specific humanized monoclonal antibody (Zhu et al. in National Sci Rev. 8:nwaa297, 2020), showed excellent protection against SARS-CoV-2 in animal model and good safety profile in clinical studies. The pharmacokinetics and preliminary safety of HB27 administrated through the respiratory tract were studied in mice and cynomolgus monkeys here. Results At a single 5 mg/kg dose, the peak HB27 concentration in mice pulmonary epithelial lining fluid (ELF) reached 857.8 μg/mL, 670-fold higher than the PRNT 90 value of 1.28 μg/mL, and maintained above PRNT 90 over 240 h. In contrast, when administrated by intravenous injection at a 5 mg/kg dose, the antibody concentrations in mice ELF were below PRNT 90 value throughout, and were about 50-fold lower than that in the serum. In cynomolgus monkeys administrated with a single dose through inhalation, the antibody concentration in ELF remained high within 3 days. No drug-related safety concerns were observed in the studies. Conclusions The study demonstrated that nebulized neutralizing antibody delivery though inhalation could be a more efficient and efficacious alternative approach for treating COVID-19 and other respiratory infectious diseases, and warrants further evaluation in clinical studies.

Dissecting the role of cell signaling versus CD8+ T cell modulation in propranolol antitumor activity - Wei Li; Jielin Wan; Cuiyu Chen; Chengfang Zhou; Ping Liao; Qian Hu; Jiali Hu; Yang Wang; Yu Zhang; Cong Peng; Yuanfei Huang; Weihua Huang; et al. (Journal of Molecular Medicine, 2022)

Impacts of Mercury Exposure Levels and Sources on the Demethylation of Methylmercury Through Human Gut Microbiota - Xian-Feng Yang; Shao-Chen Yang; Fu-Li Wen; Lin Feng; Bo Meng; Hai-Yan Hu; Bao-Lin Wang; Jun Li; Alexandre J. Poulain; Ping Li (Bulletin of Environmental Contamination and Toxicology, 2022)

ML323, a USP1 inhibitor triggers cell cycle arrest, apoptosis and autophagy in esophageal squamous cell carcinoma cells - Yaxin Sun; Beibei Sha; Wenjing Huang; Miaomiao Li; Shan Zhao; Yuan Zhang; Jie Yan; Zheng Li; Jingwen Tang; Peiyan Duan; Jianxiang Shi; Pei Li; et al. (Apoptosis, 2022)

Bedside Diagnosis for Disseminated Deep Dermatophytosis: a Case Series Study - Xiu-Jiao Xia; Hong Shen; Hui-Lin Zhi; Yan Zhong; Bo Sang; Wen-Wen Lv; Qiu-Ping Li; Ze-Hu Liu (Mycopathologia, 2022)

Astragalus Polysaccharides Reduce High-glucose-induced Rat Aortic Endothelial Cell Senescence and Inflammasome Activation by Modulating the Mitochondrial Na+/Ca2+ Exchanger - Xin-Yu Miao; Xiao-Xiao Zhu; Zhao-Yan Gu; Bo Fu; Shao-Yuan Cui; Yuan Zu; Ling-Jun Rong; Fan Hu; Xiang-Mei Chen; Yan-Ping Gong; Chun-Lin Li (Cell Biochemistry and Biophysics, 2022)

Mycorrhizal fungi alleviate acidification‐induced phosphorus limitation: Evidence from a decade‐long field experiment of simulated acid deposition in a tropical forest in south China - Yuanliu Hu; Ji Chen; Dafeng Hui; Ying‐Ping Wang; Jianling Li; Jingwen Chen; Guoyin Chen; Yiren Zhu; Leiyi Zhang; Deqiang Zhang; Qi Deng (Global Change Biology, 2022)
South China has been experiencing very high rate of acid deposition and severe soil acidification in recent decades, which has been proposed to exacerbate the regional ecosystem phosphorus (P) limitation. We conducted a 10‐year field experiment of simulated acid deposition to examine how acidification impacts seasonal changes of different soil P fractions in a tropical forest with highly acidic soils in south China. As expected, acid addition significantly increased occluded P pool but reduced the other more labile P pools in the dry season. In the wet season, however, acid addition did not change microbial P, soluble P and labile organic P pools. Acid addition significantly increased exchangeable Al 3+ and Fe 3+ and the activation of Fe oxides in both seasons. Different from the decline of microbial abundance in the dry season, acid addition increased ectomycorrhizal fungi and its ratio to arbuscular mycorrhiza fungi in the wet season, which significantly stimulated phosphomonoesterase activities and likely promoted the dissolution of occluded P. Our results suggest that, even in already highly acidic soils, the acidification‐induced P limitation could be alleviated by stimulating ectomycorrhizal fungi and phosphomonoesterase activities. The differential responses and microbial controls of seasonal soil P transformation revealed here should be implemented into ecosystem biogeochemical model for predicting plant productivity under future acid deposition scenarios.

Residential proximity to major roadway and progression in physical disability in older adults in China - Jing Hu; Wenqian Chen; Lei Li; Yu Zhang; Hongwei Jiang; Wenhua Liu; Ping Yin (Environmental Science and Pollution Research, 2022)

Chemical constituents of Viscum coloratum (Kom.) Nakai and their cytotoxic activities - Ying-Ying Chen; Jiang-Ping Hou; Ling Huang; Afsar Khan; Fei-Fei Xing; Xiao-Han Zhang; De-Feng Han; Shi-Li Yan; Gui-Dong Cao; Qi-Yang Jiao; Dejie Liu; Xuwei Zhu; et al. (Natural Product Research, 2022)

Dissection of the practical soybean breeding pipeline by developing ZDX1, a high-throughput functional array - Rujian Sun; Bincheng Sun; Yu Tian; Shanshan Su; Yong Zhang; Wanhai Zhang; Jingshun Wang; Ping Yu; Bingfu Guo; Huihui Li; Yanfei Li; Huawei Gao; et al. (Theoretical and Applied Genetics, 2022)
Key message We developed the ZDX1 high-throughput functional soybean array for high accuracy evaluation and selection of both parents and progeny, which can greatly accelerate soybean breeding. Abstract Microarray technology facilitates rapid, accurate, and economical genotyping. Here, using resequencing data from 2214 representative soybean accessions, we developed the high-throughput functional array ZDX1, containing 158,959 SNPs, covering 90.92% of soybean genes and sites related to important traits. By application of the array, a total of 817 accessions were genotyped, including three subpopulations of candidate parental lines, parental lines and their progeny from practical breeding. The fixed SNPs were identified in progeny, indicating artificial selection during the breeding process. By identifying functional sites of target traits, novel soybean cyst nematode-resistant progeny and maturity-related novel sources were identified by allele combinations, demonstrating that functional sites provide an efficient method for the rapid screening of desirable traits or gene sources. Notably, we found that the breeding index (BI) was a good indicator for progeny selection. Superior progeny were derived from the combination of distantly related parents, with at least one parent having a higher BI. Furthermore, new combinations based on good performance were proposed for further breeding after excluding redundant and closely related parents. Genomic best linear unbiased prediction (GBLUP) analysis was the best analysis method and achieved the highest accuracy in predicting four traits when comparing SNPs in genic regions rather than whole genomic or intergenic SNPs. The prediction accuracy was improved by 32.1% by using progeny to expand the training population. Collectively, a versatile assay demonstrated that the functional ZDX1 array provided efficient information for the design and optimization of a breeding pipeline for accelerated soybean breeding.

Fine mapping of powdery mildew resistance gene MlWE74 derived from wild emmer wheat (Triticum turgidum ssp. dicoccoides) in an NBS-LRR gene cluster - Keyu Zhu; Miaomiao Li; Haibin Wu; Deyun Zhang; Lingli Dong; Qiuhong Wu; Yongxing Chen; Jingzhong Xie; Ping Lu; Guanghao Guo; Huaizhi Zhang; Panpan Zhang; et al. (Theoretical and Applied Genetics, 2022)

Association of temperature variability with the risk of initial outpatient visits for allergic rhinitis: a time-series study in Changchun - Man Xu; Pan Ke; Ruoling Chen; Ping Hu; Bing Liu; Jian Hou; Li Ke (Environmental Science and Pollution Research, 2022)

New sesquiterpeniod esters form Blumea balsamifera (L.) DC. and their anti-influenza virus activity - Yan Xiong; Ping Yi; Yuhuan Li; Rongmei Gao; Junlei Chen; Zhanxing Hu; Huayong Lou; Caixia Du; Jiayu Zhang; Yu Zhang; Chunmao Yuan; Liejun Huang; et al. (Natural Product Research, 2022)

Association of long-term exposure to ambient air pollution with the number of tuberculosis cases notified: a time-series study in Hong Kong - Man Xu; Ping Hu; Ruoling Chen; Bing Liu; Hongying Chen; Jian Hou; Li ke; Jiao Huang; Hairong Ren; Hui Hu (Environmental Science and Pollution Research, 2022)

Biological monitoring and health assessment of 21 metal(loid)s in children and adolescents in Liuzhou City, Southwest China - Yaping Li; Yu Zhang; Meng Yu; Liqin Hu; Ting Zeng; Ling Liu; Limei Wang; Liangqiong Deng; Xiang Li; Ping Liu; Dingyuan Zeng; Surong Mei (Environmental Science and Pollution Research, 2022)

Cumulative damage effect on debris slopes under frequent microseisms - Zhong-ping Yang; Shi-qi Li; Xin Tian; Yuan-xin Hu; Wan-kun Li (Journal of Mountain Science, 2022)

Direct and indirect effects of precipitation change and nutrients addition on desert steppe productivity in Inner Mongolia, northern China - Xinxin Guo; Xiaoan Zuo; Ping Yue; Xiangyun Li; Ya Hu; Min Chen; Qiang Yu (Plant and Soil, 2022)

Association between serum folate levels and blood concentrations of cadmium and lead in US adults - Zuxiang Wu; Huan Hu; Chenxi Wang; Ji Wu; Yurong Xiong; Yang Fu; Xiaoshu Cheng; Hai Su; Ping Li (Environmental Science and Pollution Research, 2022)

Isoquercitrin Upregulates Aldolase C Through Nrf2 to Ameliorate OGD/R-Induced Damage in SH-SY5Y Cells - Shi-Chang Cai; Chuan-An Yi; Xiang-Shang Hu; Gen-Yun Tang; Li-Ming Yi; Xiu-Ping Li (Neurotoxicity Research, 2021)

Influences of environmental factors on the modern 14C reservoir effects in Qinghai-Tibet Plateau lakes - Ding-ding Du; Zhi-wen Li; Hai-ping Hu; Yong-hui Bai; Wen Li; Muhammad Saleem Mughal; Hai-Yan Qian (Journal of Mountain Science, 2021)

Genetic Prion Disease: Insight from the Features and Experience of China National Surveillance for Creutzfeldt-Jakob Disease - Qi Shi; Cao Chen; Kang Xiao; Wei Zhou; Li-Ping Gao; Dong-Dong Chen; Yue-Zhang Wu; Yuan Wang; Chao Hu; Chen Gao; Xiao-Ping Dong (Neuroscience Bulletin, 2021)

Geo-structures and deformation-failure characteristics of rockslide areas near the Baige landslide scar in the Jinsha River tectonic suture zone - Shi-lin Zhang; Yue-ping Yin; Xie-wen Hu; Wen-pei Wang; Zong-liang Li; Xin-ming Wu; Gang Luo; Sai-nan Zhu (Landslides, 2021)

Detoxification of aflatoxin B 1 in broiler chickens by a triple-action feed additive - Hongwei Guo; Juan Chang; Ping Wang; Qingqiang Yin; Chaoqi Liu; Silu Li; Qun Zhu; Mingfan Yang; Xiaofei Hu (Food Additives & Contaminants: Part A, 2021)

Characterization and genome sequence of the genetically unique Escherichia bacteriophage vB_EcoM_IME392 - Yunjia Hu; Shanwei Tong; Ping Li; Xiaoping An; Lihua Song; Huahao Fan; Yigang Tong (Archives of Virology, 2021)

First report of Bacillus altitudinis causing seed rot of pomegranate in China - Qili Liu; Dongxiao Li; Haiyan Hu; Qianqian Huang; Yongheng Zhang; Feng Zhou; Puwen Song; Yuanyuan Guan; Ruifang Bu; Ping Hu; Jianjun Hao; Chengwei Li (Australasian Plant Pathology, 2021)

Steroidal glycosides from the underground parts of Hosta ventricosa and their anti-inflammatory activities in mice - Hong-Biao Chu; Nan-Nan Li; Zong-Ping Zhang; Xiao-Yue Hu; Cai-Yun Yu; Lei Hua (Natural Product Research, 2021)

Metabolomics Analysis Reveals the Role of Cyanidin Metabolism in Plumbago auriculata Flower Color - Yurong Li; Wenji Li; Di Hu; Ting Lei; Ping Shen; Jiani Li; Suping Gao (Journal of Plant Biology, 2021)

PsGRGH, a TOS1 family-like gene, is involved in the vegetative growth, environmental stress response, and pathogenicity of Phytophthora sojae - Dong Liu; Kunyuan Li; Jiulong Hu; Ping Li; Xiao Liu; Zhimou Gao (European Journal of Plant Pathology, 2021)

Exposed to Mercury-Induced Oxidative Stress, Changes of Intestinal Microflora, and Association between them in Mice - Yulan Zhao; Changming Zhou; Xiaoquan Guo; Guoliang Hu; Guyue Li; Yu Zhuang; Huabin Cao; Lin Li; Chonghong Xing; Caiying Zhang; Fan Yang; Ping Liu (Biological Trace Element Research, 2021)

Lithological and environmental controls on large tafoni along conglomerate cliffs in subtropic humid Danxiashan UNESCO Global Geopark - Xin Chen; Liu-qin Chen; Yan-hong Zhang; Ding-ding Du; Hai-ping Hu; Dong-xing Liu; Wen-zhuo Li (Journal of Mountain Science, 2021)

Emergent chikungunya fever and vertical transmission in Yunnan Province, China, 2019 - XiaoXiong Yin; Ting-Song Hu; HaiLin Zhang; YongHua Liu; ZhiJian Zhou; LeBin Liu; Ping Li; YiYin Wang; ZhaoLan Yang; Jing Yu; SiYu Chen; Fu-Qiang Zhang (Archives of Virology, 2021)

Effect of fermentation bed on bacterial growth in the fermentation mattress material and cecum of ducks - Jian- mei Wang; Xin- meng Gan; Fa-jun Pu; Wan- xia Wang; Min Ma; Ling-li Sun; Ji-wei Hu; Bo Hu; Rong-ping Zhang; Li-li Bai; Liang Li; He-he Liu (Archives of Microbiology, 2021)

Subcellular Localization of the D27 Protein in Sugarcane (Saccharum spp. Hybrids) Using an Optimized Protoplast Isolation, Purification, and Transient Gene Expression Protocol - Zhuan-di Wu; Xin Hu; Feng-gang Zan; Yong-bao Pan; David M. Burner; Zheng-ying Luo; Jia-yong Liu; Li-ping Zhao; Li Yao; Yong Zhao; Xin-long Liu; Hong-ming Xia; et al. (Sugar Tech, 2021)

Sesquiterpenoids from the roots and rhizomes of Valeriana amurensis and their effects on NGF-induced neurite outgrowth in PC12 cells - Fa-Wu Dong; Fang Li; Jia-Jia Ren; Cheng-Mei Zhao; Hong-Li Diao; Bao-Jing Li; Yan-Ping Li; Jiang-Miao Hu; Hong-Ping He (Natural Product Research, 2021)

Antifungal Effects of Fusion Puroindoline B on the Surface and Intracellular Environment of Aspergillus flavus - Ping-Ping Tian; Yang-Yong Lv; Ang Lv; Wen-Jing Yuan; Shuai-Bing Zhang; Na Li; Yuan-Sen Hu (Probiotics and Antimicrobial Proteins, 2021)

Altered BMP-Smad4 signaling causes complete cleft palate by disturbing osteogenesis in palatal mesenchyme - Nan Li; Jing Liu; Han Liu; Shangqi Wang; Ping Hu; Hailing Zhou; Jing Xiao; Chao Liu (Journal of Molecular Histology, 2021)

Correction to: Involvement of proBDNF in Monocytes/Macrophages with Gastrointestinal Disorders in Depressive Mice - Yun-Qing Yu; Yan-Ling Zhang; Zhe Wang; Yu Liu; Hui Li; Chang-Qi Li; Xin-Fu Zhou; Zhao-Lan Hu; Ru-Ping Dai (Neurotoxicity Research, 2020)

Involvement of proBDNF in Monocytes/Macrophages with Gastrointestinal Disorders in Depressive Mice - Yun-Qing Yu; Yan-Ling Zhang; Zhe Wang; Yu Liu; Hui Li; Xin-Fu Zhou; Zhao-Lan Hu; Ru-Ping Dai (Neurotoxicity Research, 2020)

Adult Stress Promotes Purinergic Signaling to Induce Visceral Pain in Rats with Neonatal Maternal Deprivation - Shufen Hu; Qian Sun; Wan-Jie Du; Jian Song; Xin Li; Ping-An Zhang; Ji-Tian Xu; Guang-Yin Xu (Neuroscience Bulletin, 2020)
Chronic visceral pain is one of the primary symptoms of patients with irritable bowel syndrome (IBS), which affects up to 15% of the population world-wide. The detailed mechanisms of visceral pain remain largely unclear. Our previous studies have shown that neonatal maternal deprivation (NMD) followed by adult multiple stress (AMS) advances the occurrence of visceral pain, likely due to enhanced norepinephrine (NE)-β 2 adrenergic signaling. This study was designed to explore the roles of P2X3 receptors (P2X3Rs) in the chronic visceral pain induced by combined stress. Here, we showed that P2X3Rs were co-expressed in β 2 adrenergic receptor (β 2 -AR)-positive dorsal root ganglion neurons and that NE significantly enhanced ATP-induced Ca 2+ signals. NMD and AMS not only significantly increased the protein expression of P2X3Rs, but also greatly enhanced the ATP-evoked current density, number of action potentials, and intracellular Ca 2+ concentration of colon-related DRG neurons. Intrathecal injection of the P2X3R inhibitor A317491 greatly attenuated the visceral pain and the ATP-induced Ca 2+ signals in NMD and AMS rats. Furthermore, the β 2 -AR antagonist butoxamine significantly reversed the expression of P2X3Rs, the ATP-induced current density, and the number of action potentials of DRG neurons. Overall, our data demonstrate that NMD followed by AMS leads to P2X3R activation, which is most likely mediated by upregulation of β 2 adrenergic signaling in primary sensory neurons, thus contributing to visceral hypersensitivity.

Functional expression and characterization of an endo-1,4-β-mannosidase from Triticum aestivum in Pichia pastoris - Shuai-Bing Zhang; Wei-Ji Zhang; Na Li; Huan-Chen Zhai; Yang-Yong Lv; Yuan-Sen Hu; Jing-Ping Cai (Biologia, 2020)

Erratum to: An Examination of the Predictability of Tropical Cyclone Genesis in High-Resolution Coupled Models with Dynamically Downscaled Coupled Data Assimilation Initialization - Mingkui Li; Shaoqing Zhang; Lixin Wu; Xiaopei Lin; Ping Chang; Gohkan Danabasoglu; Zhiqiang Wei; Xiaolin Yu; Huiqin Hu; Xiaohui Ma; Weiwei Ma; Haoran Zhao; et al. (Advances in Atmospheric Sciences, 2020)

Vicissitudes experienced by the oldest urban center in Bangladesh in relation to the migration of the Brahmaputra River - Gang Hu; Ping Wang; Sufi Mostafizur Rahman; Dehong Li; Muhammad Mahbubul Alam; Jiafu Zhang; Zhengyao Jin; Anchuan Fan; Jie Chen; Aimin Zhang; Wenqing Yang (Journal of Quaternary Science, 2020)
Bangladesh is one of the most densely populated countries in the world. There are 57 trans‐frontier rivers in the country, the widest being the Brahmaputra River. The river's channels have frequently changed course, but the relationship between such river migrations and human settlement patterns has remained unstudied. In this paper, optically stimulated luminescence and radiocarbon dating techniques were applied to sedimentary and organic materials in the oldest urban center (Wari‐Bateshwar) in Bangladesh. The results showed that the landscape around the urban center was dominated by floodplain and peatland facies between 7.9–7.6 and 4.7–1.6 ka, respectively. Humans occupied this area at ~3.2 ka, and manufactured delicate semi‐precious gemstone beads between ~2.4 and 1.8 ka. The urban center might be the same as an important city of the Gangaridai described in historical records. Due to fluvial migration at ~1.8 ka, the area surrounding the urban center was covered by fluvial sand. Humans might have been forced to abandon the urban center, leading to the bead processing technology in Bangladesh being lost forever.

Nutrient Resorption from Leaves of Wetland Plants in a Constructed Wetland Depends on Green Leaf Nutrient Content and Life Form - Xu Pan; Yunmei Ping; Lijuan Cui; Xiaodong Zhang; Wei Li; Yukun Hu; Johannes H. C. Cornelissen (Wetlands, 2020)

De novo transcriptome of the whole-body of the gastropod mollusk Philomycus bilineatus, a pest with medical potential in China - Zhongjie Li; Yaping Yuan; Miaomiao Meng; Ping Hu; Yong Wang (Journal of Applied Genetics, 2020)

Characterization of Pneumocystis jirovecii pneumonia at three tertiary comprehensive hospitals in southern China - Yan-Hui Chen; Xue-Yao Fang; Yue-Ting Li; Yan-Ling Liu; Ya-Ping Hang; Yan-Ping Xiao; Xing-Wei Cao; Qiao-Shi Zhong; Long-Hua Hu (Brazilian Journal of Microbiology, 2020)

An Examination of the Predictability of Tropical Cyclone Genesis in High-Resolution Coupled Models with Dynamically Downscaled Coupled Data Assimilation Initialization - Mingkui Li; Shaoqing Zhang; Lixin Wu; Xiaopei Lin; Ping Chang; Gohkan Danabasoglu; Zhiqiang Wei; Xiaolin Yu; Huiqin Hu; Xiaohui Ma; Weiwei Ma; Haoran Zhao; et al. (Advances in Atmospheric Sciences, 2020)

Corticosterone Induced the Increase of proBDNF in Primary Hippocampal Neurons Via Endoplasmic Reticulum Stress - Yu Liu; Guang-Jing Zou; Bo-Xuan Tu; Zhao-Lan Hu; Cong Luo; Yan-Hui Cui; Yang Xu; Fang Li; Ru-Ping Dai; Fang-Fang Bi; Chang-Qi Li (Neurotoxicity Research, 2020)

Contamination characteristics of heavy metals in particle size fractions from street dust from an industrial city, Central China - Ping Zhong; Jia-Quan Zhang; Da-Mao Xu; Qian Tian; Tian-Peng Hu; Xiang-Yi Gong; Chang-Lin Zhan; Shan Liu; Xin-Li Xing; Shi-Hua Qi (Air Quality, Atmosphere & Health, 2020)

Dynamic Risk Assessment Method of Collapse in Mountain Tunnels and Application - Sheng Wang; Li-ping Li; Shaoshuai Shi; Shuai Cheng; Huijiang Hu; Tao Wen (Geotechnical and Geological Engineering, 2020)

Biological Aerosol Particles in Polluted Regions - Wei Hu; Zihan Wang; Shu Huang; Lujie Ren; Siyao Yue; Ping Li; Qiaorong Xie; Wanyu Zhao; Lianfang Wei; Hong Ren; Libin Wu; Junjun Deng; et al. (Current Pollution Reports, 2020)

Transcriptome profiling of Plumbago auriculata Lam. in response to cold stress - Wenji Li; Suping Gao; Qiao Li; Ping Shen; Yurong Li; Di Hu; Ting Lei; Xi Chen; Jiani Li (Acta Physiologiae Plantarum, 2020)

NK cell reconstitution following unmanipulated HLA-mismatched/haploidentical transplantation compared with matched sibling transplantation - Li-Juan Hu; Xun-Hong Cao; Xing-Xing Yu; Xue-Fei Liu; Xiao-Su Zhao; Ying-Jun Chang; Xiao-Hui Zhang; Lan-Ping Xu; Yu Wang; Kai-Yan Liu; Xiao-Jun Huang; Xiang-Yu Zhao (Science China Life Sciences, 2020)

Molecular characterization of the Krüppel-homolog 1 and its role in ovarian development in Sogatella furcifera (Hemiptera: Delphacidae) - Kui Hu; Ping Tian; Lu Yang; Yan Tang; Lin Qiu; Hualiang He; Wenbing Ding; Youzhi Li (Molecular Biology Reports, 2020)

Alternative complement pathway is activated in the brains of scrapie-infected rodents - Cao Chen; Yan Lv; Chao Hu; Xiao-Feng Xu; Ren-Qing Zhang; Kang Xiao; Yue Ma; Li-Ping Gao; Jian-Le Li; Qiang Shi; Jing Wang; Qi Shi; et al. (Medical Microbiology and Immunology, 2020)

Heme oxygenase-1 regulates autophagy through carbon–oxygen to alleviate deoxynivalenol-induced hepatic damage - Zhao Peng; Yuxiao Liao; Xiaoqian Wang; Liangkai Chen; Liangliang Wang; Chenyuan Qin; Zhenting Wang; Mengyao Cai; Jiawei Hu; Dan Li; Ping Yao; Andreas K. Nüssler; et al. (Archives of Toxicology, 2020)

Nocardia panacis sp. nov., a novel actinomycete with antiphytopathogen activity isolated from the rhizosphere of Panax notoginseng - Jia-Yun Hu; Lei Li; Guang Peng; Yi-Qing Li; Li-Hua Xu; Hui-Lin Guan; Li-Xing Zhao; Cui-Ping Miao (Antonie van Leeuwenhoek, 2020)

The false smut pathogen Ustilaginoidea virens requires rice stamens for false smut ball formation - Jing Fan; Jie Liu; Zhi‐You Gong; Pei‐Zhou Xu; Xiao‐Hong Hu; Jin‐Long Wu; Guo‐Bang Li; Juan Yang; Yu‐Qiu Wang; Yu‐Feng Zhou; Shuang‐Cheng Li; Li Wang; et al. (Environmental Microbiology, 2020)
Summary Rice false smut has emerged as a serious grain disease in rice production worldwide. The disease is characterized by the transformation of individual rice florets into false smut balls, which is caused by the fungal pathogen Ustilaginoidea virens . To date, little is known about the host factors required for false smut ball formation by U . virens . In this study, we identified histological determinants for the formation of false smut balls by inoculating U . virens into rice floral mutants defective with respect to individual floral parts. The results showed that U . virens could form mature false smut balls in rice floral mutants with defective pistils, but failed to develop false smut balls in the superwoman mutant lacking stamens, identifying that U . virens requires rice stamens to complete its infection cycle. Comparative transcriptome analysis indicated a list of candidate host genes that may facilitate nutrient acquisition by U . virens from the rice stamens, such as SWEET11 , SWEET14 and SUT5 , and genes involved in the biosynthesis of trehalose and raffinose family sugars. These data pinpoint rice stamens as the key target organ of U . virens infection and provide a valuable starting point for dissecting the molecular mechanism of false smut ball formation.

The complete chloroplast genome of the daimyo oak, Quercus dentata Thunb. - Hua-Lei Hu; Jing-Yu Zhang; Yu-Ping Li; Lu Xie; Dong-Bin Chen; Qun Li; Yan-Qun Liu; Shu-Rong Hui; Li Qin (Conservation Genetics Resources, 2019)

The Verticillium dahliae Sho1‐MAPK pathway regulates melanin biosynthesis and is required for cotton infection - Jun‐Jiao Li; Lei Zhou; Chun‐Mei Yin; Dan‐Dan Zhang; Steven J. Klosterman; Bao‐Li Wang; Jian Song; Dan Wang; Xiao‐Ping Hu; Krishna V. Subbarao; Jie‐Yin Chen; Xiao‐Feng Dai (Environmental Microbiology, 2019)
Summary Verticillium dahliae is a soil‐borne fungus that causes vascular wilt on numerous plants worldwide. The fungus survives in the soil for up to 14 years by producing melanized microsclerotia. The protective function of melanin in abiotic stresses is well documented. Here, we found that the V . dahliae tetraspan transmembrane protein VdSho1, a homolog of the Saccharomyces cerevisiae Sho1, acts as an osmosensor, and is required for plant penetration and melanin biosynthesis. The deletion mutant Δ Sho1 was incubated on a cellophane membrane substrate that mimics the plant epidermis, revealing that the penetration of Δ Sho1 strain was reduced compared to the wild‐type strain. Furthermore, VdSho1 regulates melanin biosynthesis by a signalling mechanism requiring a kinase‐kinase signalling module of Vst50‐Vst11‐Vst7. Strains, Δ Vst50 , Δ Vst7 and Δ Vst11 also displayed defective penetration and melanin production like the Δ Sho1 strain. Defects in penetration and melanin production in Δ Sho1 were restored by overexpression of Vst50 , suggesting that Vst50 lies downstream of VdSho1 in the regulatory pathway governing penetration and melanin biosynthesis. Data analyses revealed that the transmembrane portion of VdSho1 was essential for both membrane penetration and melanin production. This study demonstrates that Vst50‐Vst11‐Vst7 module regulates VdSho1‐mediated plant penetration and melanin production in V . dahliae , contributing to virulence.

Wind and sand control by an oasis protective system: a case from the southeastern edge of the Tengger Desert, China - Yun-hu Xie; Xiao-hong Dang; Zhong-ju Meng; Hong-tao Jiang; Xiao-jia Li; Rui-ping Zhou; Dan-dan Zhou; Xiao-xi Liu; Jing Ding; Xue-qin Wu; Yu-hao Wang; Chun-xing Hai; et al. (Journal of Mountain Science, 2019)

A new abietane diterpenoid glycoside from ajuga ovalifolia var. calantha - Fan Yang; Hong-Ping Chen; Xiao-Fei Shen; Hu-Lan Chen; Yin Chen; Li-Xia Wang; Hai Zhang; Wen-Ji Zhao; Mei Zhang; Yu-Zhu Tan (Natural Product Research, 2019)

Upregulation of proBDNF in the Mesenteric Lymph Nodes in Septic Mice - Zhe Wang; Jia-Li Wu; Feng Zhong; Yu Liu; Yun-Qing Yu; Jing-Jing Sun; Shuang Wang; Hui Li; Xin-Fu Zhou; Zhao-Lan Hu; Ru-Ping Dai (Neurotoxicity Research, 2019)

Deubiquitylatinase inhibitor b-AP15 induces c-Myc-Noxa-mediated apoptosis in esophageal squamous cell carcinoma - Beibei Sha; Xiaoyu Chen; Han Wu; Miaomiao Li; Jianxiang Shi; Longhao Wang; Xingge Liu; Ping Chen; Tao Hu; Pei Li (Apoptosis, 2019)

The effect of host plant on the development and larval midgut protease activity of Plutella xylostella (Lepidoptera: Plutellidae) - Aiping Zhao; Xiangqun Yuan; Di Hu; Chunmeng Leng; Yin Li; Ping Wang; Yiping Li (Phytoparasitica, 2019)

Favus of Scrotum Due to Trichophyton rubrum in Immunocompetent Patients: A Clinical, Mycological and Ultrastructural Study - Ze-Hu Liu; Xiu-Jiao Xia; Yong Zhang; Yan Zhong; Bo Sang; Qiu-Ping Li; Mei Wang; Wen-Wen Lv; Hui-Lin Zhi; Xiang-Dong Wang; Cui-Ping Guan; Hong Shen (Mycopathologia, 2019)

Study on Stability of Goaf Pillars in Daqiao Phosphate Mine: Theoretical Calculation and Field Investigation - Feifei Wang; Ping Zou; Zhonghua Meng; Aibing Li; Zhengyu Liu; Wanjie Hu; Zeng Ma (Geotechnical and Geological Engineering, 2019)

Potential effects of exploiting the Yunfu pyrite mine (southern China) on soil: evidence from analyzing trace elements in surface soil - Zhi-hua Tang; Ting-ping Ouyang; Ming-kun Li; Ning-sheng Huang; Yao-qiu Kuang; Qiao Hu; Zhao-yu Zhu (Environmental Monitoring and Assessment, 2019)

The Molecular Mechanisms of Protective Role of Se on the G0/G1 Phase Arrest Caused by AFB1 in Broiler’s Thymocytes - Ke Guan; Hang Li; Zhicai Zuo; Fengyuan Wang; Ping Hu; Xi Peng; Jing Fang; Hengmin Cui; Gang Shu; Ping Ouyang (Biological Trace Element Research, 2019)

The Tibetan Plateau Surface-Atmosphere Coupling System and Its Weather and Climate Effects: The Third Tibetan Plateau Atmospheric Science Experiment - Ping Zhao; Yueqing Li; Xueliang Guo; Xiangde Xu; Yimin Liu; Shihao Tang; Wenming Xiao; Chunxiang Shi; Yaoming Ma; Xing Yu; Huizhi Liu; La Jia; et al. (Journal of Meteorological Research, 2019)

Effect of Chronic Exposure to Methomyl on Tissue Damage and Apoptosis in Testis of Tilapia (Oreochromis niloticus) and Recovery Pattern - Shun Long Meng; Tao Liu; Xi Chen; Li Ping Qiu; Geng Dong Hu; Chao Song; LiMin Fan; Yao Zheng; Jia Zhang Chen; Pao Xu (Bulletin of Environmental Contamination and Toxicology, 2019)

Silencing of an aquaporin gene diminishes bacterial blight disease in rice - Liyuan Zhang; Yiqun Hu; Ping Li; Xiaobing Wang; Hansong Dong (Australasian Plant Pathology, 2019)

Neonatal Maternal Deprivation Followed by Adult Stress Enhances Adrenergic Signaling to Advance Visceral Hypersensitivity - Wan-Jie Du; Shufen Hu; Xin Li; Ping-An Zhang; Xinghong Jiang; Shan-Ping Yu; Guang-Yin Xu (Neuroscience Bulletin, 2019)

Magnetic chitosan/sodium alginate gel bead as a novel composite adsorbent for Cu(II) removal from aqueous solution - Hu-Chun Tao; Shuo Li; Li-Juan Zhang; Yi-Zhen Chen; Li-Ping Deng (Environmental Geochemistry and Health, 2019)

Challenges in predicting and simulating summer rainfall in the eastern China - Ping Liang; Zeng-Zhen Hu; Yunyun Liu; Xing Yuan; Xiaofan Li; Xingwen Jiang (Climate Dynamics, 2019)

Luminescence chronology of the Palaeolithic–Neolithic transition in the Yujiagou site at the Nihewan Basin, northern China - Xue Rui; Yu‐Jie Guo; Jia‐Fu Zhang; Yue Hu; Hui‐Jie Mei; You‐Ping Wang; Fei Xie; Bo Li (Journal of Quaternary Science, 2019)
The relationship between the Palaeolithic–Neolithic cultural transition and environmental changes is important for understanding human history. However, the timing and nature of human behaviour at the transition, and their relationship to local environmental conditions, remain poorly understood. The Yujiagou archaeological site in the Nihewan Basin, northern China, provides valuable chronological and archaeological information about cultural changes in northern China due to its continuous archaeological sequence of cultural layers from the Palaeolithic to Neolithic. In this study, we apply post‐infrared infrared stimulated luminescence (pIRIR) dating on individual feldspar grains to date the Yujiagou deposits. We provide a revised chronology for the archaeological sequence at the site. We combine these results with multi‐proxy climatic indicators to gain insights into palaeoenvironmental changes in the region. The results show that the age of the artefact‐bearing deposits ranges from 13.5 to 9.7 ka. Polished stones and pottery begin to occur in the archaeological layer around 13 ka, corresponding to a transitional period when the local climate changed from cold to warm. This site provides evidence for understanding the process that led to the regional transition from hunter‐gathering to farming.

RETRACTED ARTICLE: Fluoxetine is Neuroprotective in Early Brain Injury via its Anti-inflammatory and Anti-apoptotic Effects in a Rat Experimental Subarachnoid Hemorrhage Model - Hui-Min Hu; Bin Li; Xiao-Dong Wang; Yun-Shan Guo; Hua Hui; Hai-Ping Zhang; Biao Wang; Da-Geng Huang; Ding-Jun Hao (Neuroscience Bulletin, 2018)

Transcriptome profiling of rubber tree (Hevea brasiliensis) discovers candidate regulators of the cold stress response - Xiao-Xiao Gong; Bing-Yu Yan; Jin Hu; Cui-Ping Yang; Yi-Jian Li; Jin-Ping Liu; Wen-Bin Liao (Genes & Genomics, 2018)

The Protective Role of Selenium in AFB1-Induced Tissue Damage and Cell Cycle Arrest in Chicken’s Bursa of Fabricius - Ping Hu; Zhicai Zuo; Fengyuan Wang; Xi Peng; Ke Guan; Hang Li; Jing Fang; Hengmin Cui; Gang Su; Ping Ouyang; Yi Zhou (Biological Trace Element Research, 2018)

Update on the clinical application of deep brain stimulation in sleep dysfunction of Parkinson’s disease - Shuang Zou; Yu-Long Lan; Ya-Ping Hu; Xiao-Xue Yin; Wen-Long Liu; Tao Li; Zhanhua Liang (Acta Neurologica Belgica, 2018)

Soil infiltration processes of different underlying surfaces in the permafrost region on the Tibetan Plateau - Guo-jie Hu; Li-ming Tian; Lin Zhao; Xiao-dong Wu; Ren Li; Tong-hua Wu; Xiao-fan Zhu; Er-ji Du; Zhi-wei Wang; Jun-ming Hao; Wang-ping Li; Song-he Wang (Hydrological Sciences Journal, 2018)

Climatology of tracked persistent maxima of 500-hPa geopotential height - Ping Liu; Yuejian Zhu; Qin Zhang; Jon Gottschalck; Minghua Zhang; Christopher Melhauser; Wei Li; Hong Guan; Xiaqiong Zhou; Dingchen Hou; Malaquias Peña; Guoxiong Wu; et al. (Climate Dynamics, 2018)

Joint structural and physiological control on the interannual variation in productivity in a temperate grassland: A data‐model comparison - Zhongmin Hu; Hao Shi; Kaili Cheng; Ying‐Ping Wang; Shilong Piao; Yue Li; Li Zhang; Jianyang Xia; Lei Zhou; Wenping Yuan; Steve Running; Longhui Li; et al. (Global Change Biology, 2018)
Given the important contributions of semiarid region to global land carbon cycle, accurate modeling of the interannual variability (IAV) of terrestrial gross primary productivity (GPP) is important but remains challenging. By decomposing GPP into leaf area index (LAI) and photosynthesis per leaf area (i.e., GPP_leaf), we investigated the IAV of GPP and the mechanisms responsible in a temperate grassland of northwestern China. We further assessed six ecosystem models for their capabilities in reproducing the observed IAV of GPP in a temperate grassland from 2004 to 2011 in China. We observed that the responses to LAI and GPP_leaf to soil water significantly contributed to IAV of GPP at the grassland ecosystem. Two of six models with prescribed LAI simulated of the observed IAV of GPP quite well, but still underestimated the variance of GPP_leaf, therefore the variance of GPP. In comparison, simulated pattern by the other four models with prognostic LAI differed significantly from the observed IAV of GPP. Only some models with prognostic LAI can capture the observed sharp decline of GPP in drought years. Further analysis indicated that accurately representing the responses of GPP_leaf and leaf stomatal conductance to soil moisture are critical for the models to reproduce the observed IAV of GPP_leaf. Our framework also identified that the contributions of LAI and GPP_leaf to the observed IAV of GPP were relatively independent. We conclude that our framework of decomposing GPP into LAI and GPP_leaf has a significant potential for facilitating future model intercomparison, benchmarking and optimization should be adopted for future data‐model comparisons.

Analysis of DNA Methylation of Gracilariopsis lemaneiformis Under Temperature Stress Using the Methylation Sensitive Amplification Polymorphism (MSAP) Technique - Chong Peng; Zhenghong Sui; Wei Zhou; Yiyi Hu; Ping Mi; Minjie Jiang; Xiaodong Li; Xudong Ruan (Journal of Ocean University of China, 2018)

Transcriptome analysis of Hevea brasiliensis in response to exogenous methyl jasmonate provides novel insights into regulation of jasmonate-elicited rubber biosynthesis - Jin-Ping Liu; Jin Hu; Yan-Hui Liu; Cui-Ping Yang; Yu-Fen Zhuang; Xiu-Li Guo; Yi-Jian Li; Liangsheng Zhang (Physiology and Molecular Biology of Plants, 2018)

Geochemistry of uranium in Chinese coals and the emission inventory of coal-fired power plants in China - Jian Chen; Ping Chen; Duoxi Yao; Wenhui Huang; Shuheng Tang; Kejian Wang; Wenzhong Liu; Youbiao Hu; Qingguang Li; Ruwei Wang (International Geology Review, 2018)

Tau-Induced Ca2+/Calmodulin-Dependent Protein Kinase-IV Activation Aggravates Nuclear Tau Hyperphosphorylation - Yu-Ping Wei; Jin-Wang Ye; Xiong Wang; Li-Ping Zhu; Qing-Hua Hu; Qun Wang; Dan Ke; Qing Tian; Jian-Zhi Wang (Neuroscience Bulletin, 2018)

Physical and chemical characteristics of PM2.5 and its toxicity to human bronchial cells BEAS-2B in the winter and summer - Hui-hui Zhang; Zheng Li; Yu Liu; Ping Xinag; Xin-yi Cui; Hui Ye; Bao-lan Hu; Li-ping Lou (Journal of Zhejiang University-SCIENCE B, 2018)

Genome-wide genetic variation and comparison of fruit-associated traits between kumquat (Citrus japonica) and Clementine mandarin (Citrus clementina) - Tian-Jia Liu; Yong-Ping Li; Jing-Jing Zhou; Chun-Gen Hu; Jin-Zhi Zhang (Plant Molecular Biology, 2018)

A study of variation characteristics of Gobi broadband emissivity based on field observational experiments in northwestern China - Zhi-yuan Zheng; Zhi-gang Wei; Zhi-ping Wen; Wen-jie Dong; Zhen-chao Li; Xiao-hang Wen; Xian Zhu; Chen Chen; Shan-shan Hu (Theoretical and Applied Climatology, 2018)

Phenolic constituents from Rheum nobile and their antioxidant activity - Ye Fei; Juan Wang; Bing Peng; Jiangnan Peng; Jing-Hong Hu; Zu-Ping Zeng; Jing Chen; Qi-En Li; Zeng-Ping Gao; Xing-Li Yan (Natural Product Research, 2017)

RETRACTED ARTICLE: Downregulation of the Long Non-Coding RNA Meg3 Promotes Angiogenesis After Ischemic Brain Injury by Activating Notch Signaling - Juan Liu; Qing Li; Kun-shan Zhang; Bin Hu; Xin Niu; Shu-min Zhou; Si-guang Li; Yu-ping Luo; Yang Wang; Zhi-feng Deng (Molecular Neurobiology, 2017)
Angiogenesis after ischemic brain injury contributes to the restoration of blood supply in the ischemic zone. Strategies to improve angiogenesis may facilitate the function recovery after stroke. Recent researches have demonstrated that dysfunction of long non-coding RNAs are associated with angiogenesis. We have previously reported that long non-coding RNAs (lncRNAs) are aberrantly expressed in ischemic stroke. However, little is known about long non-coding RNAs and theirs role in angiogenesis after stroke. In this study, we identified a rat lncRNAs, Meg3, and found that Meg3 was significantly decreased after ischemic stroke. Overexpression of Meg3 suppressed functional recovery and decreased capillary density after ischemic stroke. Downregulation of Meg3 ameliorated brain lesion and increased angiogenesis after ischemic stroke. Silencing of Meg3 resulted in a proangiogenic effect evidenced by increased endothelial cell migration, proliferation, sprouting, and tube formation. Mechanistically, we showed that Meg3 negatively regulated notch pathway both in vivo and in vitro. Inhibition of notch signaling in endothelial cells reversed the proangiogenic effect induced by Meg3 downregulation. This study revealed the function of Meg3 in ischemic stroke and elucidated its mechanism in angiogenesis after ischemic stroke.

Strong impact of anthropogenic contamination on the co‐occurrence patterns of a riverine microbial community - Anyi Hu; Feng Ju; Liyuan Hou; Jiangwei Li; Xiaoyong Yang; Hongjie Wang; Sikandar I. Mulla; Qian Sun; Helmut Bürgmann; Chang‐Ping Yu (Environmental Microbiology, 2017)
Summary Although the health of rivers is threatened by multiple anthropogenic stressors with increasing frequency, it remains an open question how riverine microbial communities respond to emerging micropollutants. Here, by using 16S rDNA amplicon sequencing of 60 water samples collected during different hydrological seasons, we investigated the spatio‐temporal variation and the co‐occurrence patterns of microbial communities in the anthropogenically impacted Jiulong River in China. The results indicated that the riverine microbial co‐occurrence network had a nonrandom, modular structure, which was mainly shaped by the taxonomic relatedness of co‐occurring species. Fecal indicator bacteria may survive for prolonged periods of time in river water, but they formed an independent module which had fewer interactions with typical freshwater bacteria. Multivariate analysis demonstrated that nutrients and micropollutants [i.e., pharmaceuticals and personal care products (PPCPs)] exerted combined effects in shaping α‐ and β‐diversity of riverine microbial communities. Remarkably, we showed that a hitherto unrecognized disruptive effect of PPCPs on the abundance variations of central species and module communities was stronger than the influence of physicochemical factors, suggesting the key role played by micropollutants for the microbial co‐occurrence relationships in lotic ecosystems. Overall, our findings provide novel insights into community assembly in aquatic environments experiencing anthropogenic stresses.

A new compound, methylbergenin along with eight known compounds with cytotoxicity and anti-inflammatory activity from Ardisia japonica - Ke-Yun Yu; Wei Wu; Shang-Zhen Li; Li-Li Dou; Le-Le Liu; Ping Li; E-Hu Liu (Natural Product Research, 2017)

Role of early environmental enrichment on the social dominance tube test at adulthood in the rat - Wen-Yu Cao; Zhao-Lan Hu; Yang Xu; Wen-Juan Zhang; Fu-Lian Huang; Xiao-Qing Qiao; Yan-Hui Cui; Wei Wan; Xue-qin Wang; Dan Liu; Ru-Ping Dai; Fang Li; et al. (Psychopharmacology, 2017)

Changes in Histopathology, Enzyme Activities, and the Expression of Relevant Genes in Zebrafish (Danio rerio) Following Long-Term Exposure to Environmental Levels of Thallium - Li-Ping Hou; Yang Yang; Hu Shu; Guang-Guo Ying; Jian-Liang Zhao; Yi-Bing Chen; Yong-Heng Chen; Gui-Zhen Fang; Xin Li; Ji-Sheng Liu (Bulletin of Environmental Contamination and Toxicology, 2017)

Rockfall Hazard Assessment on Wangxia Rock Mass in Wushan (Chongqing, China) - Shang-qu Sun; Li-ping Li; Shu-cai Li; Qian-qing Zhang; Cong Hu (Geotechnical and Geological Engineering, 2017)

Structural features and proto-type basin reconstructions of the Bay of Bengal Basin: A remnant ocean basin model - Peng Zhang; Lianfu Mei; Ping Xiong; Xiaolin Hu; Renyuan Li; Huaning Qiu (Journal of Earth Science, 2017)

Occurrence and genetic diversity analysis of apple stem pitting virus isolated from apples in China - Guo-Jun Hu; Ya-Feng Dong; Zun-Ping Zhang; Xu-Dong Fan; Fang Ren; Zhengnan Li (Archives of Virology, 2017)

Two ultraviolet radiation datasets that cover China - Hui Liu; Bo Hu; Yuesi Wang; Guangren Liu; Liqin Tang; Dongsheng Ji; Yongfei Bai; Weikai Bao; Xin Chen; Yunming Chen; Weixin Ding; Xiaozeng Han; et al. (Advances in Atmospheric Sciences, 2017)

LecRK-VII.1, a Lectin Receptor-Like Kinase, Mediates the Regulation of Salt Stress and Jasmonic Acid Response in Arabidopsis - Cheng Zhang; Jinyan Li; Xinhong Guo; Baode Zhu; Wenjun Xiao; Ping Wang; Miao Jiang; Shuai Hu; Xiutao Lu; Zhuang He; Ping Chen (Journal of Plant Growth Regulation, 2017)

Nuclear magnetic resonance T2 spectrum: multifractal characteristics and pore structure evaluation - Jian-Ping Yan; Xu He; Bin Geng; Qin-Hong Hu; Chun-Zhen Feng; Xiao-Pan Kou; Xing-Wen Li (Applied Geophysics, 2017)

Early-Life Social Isolation-Induced Depressive-Like Behavior in Rats Results in Microglial Activation and Neuronal Histone Methylation that Are Mitigated by Minocycline - Hong-Tao Wang; Fu-Lian Huang; Zhao-Lan Hu; Wen-Juan Zhang; Xiao-Qing Qiao; Yan-Qing Huang; Ru-Ping Dai; Fang Li; Chang-Qi Li (Neurotoxicity Research, 2017)

Astragaloside IV, a Natural PPARγ Agonist, Reduces Aβ Production in Alzheimer’s Disease Through Inhibition of BACE1 - Xu Wang; Yue Wang; Jiang-Ping Hu; Song Yu; Bao-Kun Li; Yong Cui; Lu Ren; Li-De Zhang (Molecular Neurobiology, 2017)

Erratum to: CX3CR1 deficiency accelerates the development of retinopathy in a rodent model of type 1 diabetes - Eleni Beli; James M. Dominguez; Ping Hu; Jeffrey S. Thinschmidt; Sergio Caballero; Sergio Li Calzi; Defang Luo; Sumathi Shanmugam; Tatiana E. Salazar; Yaqian Duan; Michael E. Boulton; Susanna Mohr; et al. (Journal of Molecular Medicine, 2017)

Koninginins R-S from the endophytic fungus Trichoderma koningiopsis - Ming Hu; Qi-Ling Li; Ya-Bin Yang; Kai Liu; Cui-Ping Miao; Li-Xing Zhao; Zhong-Tao Ding (Natural Product Research, 2017)

Sap flow-based transpiration in Phyllostachys pubescens: applicability of the TDP methodology, age effect and rhizome role - Zhao Xiu-hua; Zhao Ping; Zhang Zhen-zhen; Zhu Li-wei; Niu Jun-feng; Ni Guang-yan; Hu Yan-ting; Ouyang Lei (Trees, 2017)

miR-200a controls hepatic stellate cell activation and fibrosis via SIRT1/Notch1 signal pathway - Jing-Jing Yang; Hui Tao; Li-Ping Liu; Wei Hu; Zi-Yu Deng; Jun Li (Inflammation Research, 2017)

Genetic characterization of H9N2 avian influenza virus in plateau pikas in the Qinghai Lake region of China - Yan Yan; Jin-Yan Gu; Zhuang-Chuan Yuan; Xin-Yu Chen; Zeng-Kui Li; Jing Lei; Bo-li Hu; Li-Ping Yan; Gang Xing; Min Liao; Ji-Yong Zhou (Archives of Virology, 2017)

Analgesic Effects of Danggui-Shaoyao-San on Various “Phenotypes” of Nociception and Inflammation in a Formalin Pain Model - Jun-Bin Yin; Ke-Cheng Zhou; Huang-Hui Wu; Wei Hu; Tan Ding; Ting Zhang; Li-Ying Wang; Jun-Ping Kou; Alan David Kaye; Wen Wang (Molecular Neurobiology, 2016)

Responses and recovery pattern of sex steroid hormones in testis of Nile tilapia (Oreochromis niloticus) exposed to sublethal concentration of methomyl - Shun Long Meng; Li Ping Qiu; Geng Dong Hu; Li Min Fan; Chao Song; Yao Zheng; Wei Wu; Jian Hong Qu; Dan Dan Li; Jia Zhang Chen; Pao Xu (Ecotoxicology, 2016)

CX3CR1 deficiency accelerates the development of retinopathy in a rodent model of type 1 diabetes - Eleni Beli; James M. Dominguez; Ping Hu; Jeffrey S. Thinschmidt; Sergio Caballero; Sergio Li Calzi; Defang Luo; Sumathi Shanmugam; Tatiana E. Salazar; Yaqian Duan; Michael E. Boulton; Susanna Mohr; et al. (Journal of Molecular Medicine, 2016)

Microsatellite records for volume 8, issue 3 - Yan-Ling Cao; Lívia Izabela Caputo; Hongyi Cheng; Fausto Moreira da Silva Carmo; Leiliane Campos de Carvalho; Gabriel de Menezes Yazbeck; Zélia de Oliveira Teixeira; Jiaxin Fu; José Antonio Guerrero; Guibing Hu; Jun Li; Zhihua Lin; et al. (Conservation Genetics Resources, 2016)

Submerged macrophytes facilitate dominance of omnivorous fish in a subtropical shallow lake: implications for lake restoration - Jinlei Yu; Zhengwen Liu; Hu He; Wei Zhen; Baohua Guan; Feizhou Chen; Kuanyi Li; Ping Zhong; Franco Teixeira-de Mello; Erik Jeppesen (Hydrobiologia, 2016)

Delta-like 1 homolog in Capra hircus: molecular characteristics, expression pattern and phylogeny - Jiangtao Hu; Wei Zhao; Siyuan Zhan; Ping Xiao; Jingxuan Zhou; Linjie Wang; Li Li; Hongping Zhang; Lili Niu; Tao Zhong (Molecular Biology Reports, 2016)

Exogenous Diethyl Aminoethyl Hexanoate, a Plant Growth Regulator, Highly Improved the Salinity Tolerance of Important Medicinal Plant Cassia obtusifolia L. - Chunping Zhang; Ping He; Yicun Li; Yan Li; Huankai Yao; Jingyu Duan; Shijun Hu; Hui Zhou; Shuo Li (Journal of Plant Growth Regulation, 2016)

Chip-based visual detection of microRNA using DNA-functionalized gold nanoparticles - Ping Wang; Jianlong Zhao; Bin Hu; Zule Cheng; Yanan Bai; Qinghui Jin; Huiying Liu; Hongju Mao; Sanqiang Li; Jianlong Zhao (Science China Life Sciences, 2016)

Feeding ecology of the mud shrimp S olenocera melantho in the E ast C hina S ea - Hui Yu Li; Jian Zhong Ling; Li Ping Yan; Jia Hua Cheng; Fen Hu (Marine Ecology, 2016)
The feeding habits of the mud shrimp Solenocera melantho were studied in the East China Sea by analysing 720 stomach contents and comparing diet composition and prey diversity among seasons, sexes and size classes. Feeding activity was linked to season and ovarian condition. The stomach fullness was high during spring and summer and low in fall. Females with advanced ovaries also displayed low stomach fullness, which suggests that feeding activity is affected by the reproductive cycle. The diet of S. melantho consisted of 42 different prey categories, primarily smaller crustaceans, Foraminifera, polychaetes, mollusks and fishes (larvae and eggs). Crustacea,Foraminifera and polychaetes together constituted the dominant prey groups, accounting for 75% of total prey abundance and >50% of total prey occurrence. Diet composition differed among seasons between sexes and size classes. Females and males consumed the same prey items but with different orders of importance. In terms of body size, the small shrimps preferred relatively small food items, such as Foraminifera and algae, whereas larger shrimps preferred polychaetes and crustaceans. Trophic diversity varied among the seasons within both sexes and size classes, with the highest values being observed in fall. Niche overlap was high within both sexes and size classes among seasons (0.6051–0.8740).

Polymorphisms in VEGF-A are associated with COPD risk in the Chinese population from Hainan province - YIPENG DING; HUAN NIU; YIZHOU LI; PING HE; QUANNI LI; YANHONG OUYANG; MIN LI; ZHIGAO HU; YOUQING ZHONG; PEI SUN; TIANBO JIN (Journal of Genetics, 2016)

One new cycloartane triterpene glycoside from Beesia calthaefolia - Jin-Yuan Zhao; Li-Hua Mu; Xian-zhe Dong; Yuan Hu; Ping Liu (Natural Product Research, 2016)

Boosting BCG-primed mice with chimeric DNA vaccine HG856A induces potent multifunctional T cell responses and enhanced protection against Mycobacterium tuberculosis - Ping Ji; Zhi-Dong Hu; Han Kang; Qin Yuan; Hui Ma; Han-li Wen; Juan Wu; Zhong-Ming Li; Douglas B. Lowrie; Xiao-Yong Fan (Immunologic Research, 2016)

Dissimilarity of phytoplankton assemblages in two connected tropical reservoirs: effects of water transportation and environmental filtering - Li-Juan Xiao; Ren Hu; Liang Peng; La-Mei Lei; Yu Feng; Bo-Ping Han (Hydrobiologia, 2016)

Tracking management-related water quality alterations by phytoplankton assemblages in a tropical reservoir - Ren Hu; Qiuhua Li; Bo-Ping Han; Luigi Naselli-Flores; Judit Padisak; Nico Salmaso (Hydrobiologia, 2016)

A Time-Dependent Drought Index for Non-Stationary Precipitation Series - Yixuan Wang; Jianzhu Li; Ping Feng; Rong Hu (Water Resources Management, 2015)

Dynamic Transcriptional Regulation of Fis in Salmonella During the Exponential Phase - Hui Wang; Lei Wang; Ping Li; Yilang Hu; Wei Zhang; Bo Tang (Current Microbiology, 2015)

Soil stability characteristics of mulberry lands at hydro-fluctuation belt in the Three Gorges Reservoir area, China - Ping Jiang; Dongmei Shi; Xueqin Hu; Xianzhi Huang; Yexin Li; Tianlei Guo (Environmental Monitoring and Assessment, 2015)

The miR-573/apoM/Bcl2A1-dependent signal transduction pathway is essential for hepatocyte apoptosis and hepatocarcinogenesis - Yan-Wei Hu; Zhi-Ping Chen; Xiu-Mei Hu; Jia-Yi Zhao; Jin-Lan Huang; Xin Ma; Shu-Fen Li; Yu-Rong Qiu; Xiao-Juan Wu; Yan-Hua Sha; Ji-Juan Gao; Yan-Chao Wang; et al. (Apoptosis, 2015)

Wheat acclimate to water deficit by modifying carbohydrates metabolism, water use efficiency, and growth - MengYun Hu; ZhiGang Shi; Ping Xu; Hui Li; Zhengbin Zhang (Brazilian Journal of Botany, 2015)

Activation of VEGF/Flk-1-ERK Pathway Induced Blood–Brain Barrier Injury After Microwave Exposure - Li-Feng Wang; Xiang Li; Ya-Bing Gao; Shui-Ming Wang; Li Zhao; Ji Dong; Bin-Wei Yao; Xin-Ping Xu; Gong-Min Chang; Hong-Mei Zhou; Xiang-Jun Hu; Rui-Yun Peng (Molecular Neurobiology, 2015)

Protective Effect of Apigenin on Ischemia/Reperfusion Injury of the Isolated Rat Heart - Jing Hu; Zilin Li; Li-ting Xu; Ai-jun Sun; Xiao-yan Fu; Li Zhang; Lin-lin Jing; An-dong Lu; Yi-fei Dong; Zheng-ping Jia (Cardiovascular Toxicology, 2015)

Marker-assisted breeding for transgressive seed protein content in soybean [Glycine max (L.) Merr.] - Ying Hu Zhang; Mei Feng Liu; Jian Bo He; Yu Feng Wang; Guang Nan Xing; Yan Li; Shou Ping Yang; Tuan Jie Zhao; Jun Yi Gai (Theoretical and Applied Genetics, 2015)

Endophytic microbes Bacillus sp. LZR216-regulated root development is dependent on polar auxin transport in Arabidopsis seedlings - Jianfeng Wang; Yongqiang Zhang; Ying Li; Xiaomin Wang; Wenbin Nan; Yanfeng Hu; Hong Zhang; Chengzhou Zhao; Feng Wang; Ping Li; Hongyong Shi; Yurong Bi (Plant Cell Reports, 2015)

Characterization of 26 deletion CNVs reveals the frequent occurrence of micro-mutations within the breakpoint-flanking regions and frequent repair of double-strand breaks by templated insertions derived from remote genomic regions - Ye Wang; Peiqiang Su; Bin Hu; Wenjuan Zhu; Qibin Li; Ping Yuan; Jiangchao Li; Xinyuan Guan; Fucheng Li; Xiangyi Jing; Ru Li; Yongling Zhang; et al. (Human Genetics, 2015)

Hydrogeochemical and isotopic characteristics of groundwater in the salt chemical industrial base of Guyuan City, northwestern China - Ying Li; Fu Sheng Hu; Zhong Qi Xue; Yan Qing Yu; Ping Wu (Arabian Journal of Geosciences, 2015)

Enhanced Phytoextraction of Heavy Metals from Contaminated Soil by Plant Co-cropping Associated with PGPR - Zhi-feng Liu; Hong-guang Ge; Chen Li; Zuo-ping Zhao; Feng-min Song; Shi-bin Hu (Water, Air, & Soil Pollution, 2015)

Genetic manipulation of a high-affinity PHR1 target cis-element to improve phosphorous uptake in Oryza sativa L. - Wenyuan Ruan; Meina Guo; Linlin Cai; Hongtao Hu; Changying Li; Yu Liu; Zhongchang Wu; Chuanzao Mao; Keke Yi; Ping Wu; Xiaorong Mo (Plant Molecular Biology, 2015)

Host-Choice Behavior of Diaphorina citri Kuwayama (Hemiptera: Psyllidae) Under Laboratory Conditions - Chuan-Qing Ruan; David G. Hall; Bo Liu; Yong-Ping Duan; Tao Li; Han-Qing Hu; Guo-Cheng Fan (Journal of Insect Behavior, 2015)

Three-dimensional tensor controlled-source electromagnetic modeling based on the vector finite-element method - Ying-Cai Hu; Tong-Lin Li; Cui-Song Fan; Da-Yong Wang; Jian-Ping Li (Applied Geophysics, 2015)

Annual thawing and freezing indices changes in the China Tianshan Mountains - Feng-qing Jiang; Abudu-waili Jilili; Shao-ping Wang; Ru-ji Hu; Xiao-lan Li (Regional Environmental Change, 2015)

Genetic analysis and chromosome mapping of a thermo-sensitive genic male sterile gene in wheat - Zhen-Gang Ru; Li-Ping Zhang; Tie-Zhu Hu; Hong-Yu Liu; Qing-Kai Yang; Man-Li Weng; Bin Wang; Chang-Ping Zhao (Euphytica, 2015)

Responses of canola (Brassica napus L.) cultivars under contrasting temperature regimes during early seedling growth stage as revealed by multiple physiological criteria - Jing Zhang; Fangwei Jiang; Ping Yang; Jing Li; Guijun Yan; Liyong Hu (Acta Physiologiae Plantarum, 2015)

A novel strategy for rapid quantification of 20( S )-protopanaxatriol and 20( S )-protopanaxadiol saponins in Panax notoginseng P. ginseng and P. quinquefolium - Fa-Xiang Xu; Cen Yuan; Jian-Bo Wan; Ru Yan; Hao Hu; Shao-Ping Li; Qing-Wen Zhang (Natural Product Research, 2015)

Contamination of commercially available seafood by key diarrhetic shellfish poisons along the coast of China - Chao Lin; Zeng-Shan Liu; Cai-Yun Tan; Yi-Ping Guo; Lin Li; Hong-Lin Ren; Yan-Song Li; Pan Hu; Sheng Gong; Yu Zhou; Shi-Ying Lu (Environmental Science and Pollution Research, 2015)

Removal and Recovery of U(VI) from Low Concentration Radioactive Wastewater by Ethylenediamine-Modified Biomass of Aspergillus niger - De Xin Ding; Xin Xin; Le Li; Nan Hu; Guang Yue Li; Yong Dong Wang; Ping Kun Fu (Water, Air, & Soil Pollution, 2014)

Isolation and molecular characterization of an ethylene response factor NtERF1-1 in Nicotiana tabacum cv. Xanthi - Jun-Shan Gao; Li Hu; Peng Xie; Yan Meng; Yong-Ping Cai; Yi Lin (Journal of Biosciences, 2014)

Secretory expression of a bispecific antibody targeting tumor necrosis factor and ED-B fibronectin in Pichia pastoris and its functional analysis - Meng-yuan Liu; Xue-ping Hu; Mian Xie; Si-jing Jiang; Lu-jun Li; Dong-xu Liu; Xiao-song Yang (Biotechnology Letters, 2014)

Isolation and characterization of polymorphic microsatellites in the perennial herb Euphorbia kansui using paired-end Illumina shotgun sequencing - Xiao-Hao Yan; Min-Feng Fang; Zeng-Qiang Qian; Zhan-Lin Liu; Ma-Li Wang; Cai-Ping Tian; Meng-Han Du; Yin-Jun Li; Zhong-Hu Li; Gui-Fang Zhao (Conservation Genetics Resources, 2014)

Potent in vitro synergism of fusidic acid (FA) and berberine chloride (BBR) against clinical isolates of methicillin-resistant Staphylococcus aureus (MRSA) - Rong-mei Liang; Xiao-lan Yong; Yu-qin Duan; Yong-hong Tan; Ping Zeng; Zi-ying Zhou; Yan Jiang; Shi-hua Wang; Yun-ping Jiang; Xiao-chun Huang; Zhao-hui Dong; Ting-ting Hu; et al. (World Journal of Microbiology and Biotechnology, 2014)

The influence of Caragana korshinskii shrub on soil and hydrological properties in a revegetation-stabilized desert ecosystem - Yan-Xia Pan; Xin-Ping Wang; Xin-Rong Li; Ya-Feng Zhang; Rui Hu; Hao Zhang (Hydrological Sciences Journal, 2014)

Hepatocellular Carcinoma in Budd-Chiari Syndrome: Enhancement Patterns at Dynamic Gadolinium-Enhanced T1-Weighted MR Imaging - Chun Yang; Kai Xu; Junnian Zheng; Ping Ma; Chunfeng Hu; Shaodong Li; Yutao Rong; Xin Lu; Qingqiao Zhang; Maoheng Zu; Rong Hua; Ling Zhang (Cell Biochemistry and Biophysics, 2014)

Assessment of dietary phytoestrogen intake via plant-derived foods in China - Xiao Juan Hu; Wan Rui Song; Li Ying Gao; Shao Ping Nie; Gerhard Eisenbrand; Ming Yong Xie (Food Additives & Contaminants: Part A, 2014)

Catechin ameliorates cardiac dysfunction in rats with chronic heart failure by regulating the balance between Th17 and Treg cells - Qi Zhang; Li-qun Hu; Chang-sen Yin; Ping Chen; Hong-qi Li; Xin Sun; Guang Yan (Inflammation Research, 2014)

Aquaporin-4 Mitigates Retrograde Degeneration of Rubrospinal Neurons by Facilitating Edema Clearance and Glial Scar Formation After Spinal Cord Injury in Mice - Qi Wu; Yong-Jie Zhang; Jun-Ying Gao; Xiu-Miao Li; Hui Kong; Yi-Ping Zhang; Ming Xiao; Christopher B. Shields; Gang Hu (Molecular Neurobiology, 2014)

Fluid Flow-Induced Calcium Response in Osteoclasts: Signaling Pathways - Ping Li; Chenglin Liu; Man Hu; Mian Long; Ding Zhang; Bo Huo (Annals of Biomedical Engineering, 2014)

Morin Inhibits Sortase A and Subsequent Biofilm Formation in Streptococcus mutans - Ping Huang; Ping Hu; Su Yun Zhou; Qian Li; Wei Min Chen (Current Microbiology, 2014)

The role of sucrose-metabolizing enzymes in pear fruit that differ in sucrose accumulation - Hu Ping Zhang; Ju You Wu; Gai Hua Qin; Gai Fang Yao; Kai Jie Qi; Li Fen Wang; Shao Ling Zhang (Acta Physiologiae Plantarum, 2014)

Activation of BKCa Channels Mediates Hippocampal Neuronal Death After Reoxygenation and Reperfusion - Ming Chen; Hong-Yu Sun; Ping Hu; Chun-Fei Wang; Bo-Xing Li; Shu-Ji Li; Jian-Jun Li; Hui-Ying Tan; Tian-Ming Gao (Molecular Neurobiology, 2013)

ROCK is Involved in Vimentin Phosphorylation and Rearrangement Induced by Dengue Virus - Shun Lei; Yan-Ping Tian; Wei-Dong Xiao; Shu Li; Xian-Cai Rao; Jun-Lei Zhang; Jie Yang; Xiao-Mei Hu; Wei Chen (Cell Biochemistry and Biophysics, 2013)

The first complete genomic characterization of an Amur virus isolate from China - Yu Zhang; Bo-Hua Liu; Fang Lin; Yong-Guo Zhang; Bing-Yin Si; Xiao-Ping Kang; Yi Hu; Jing Li; Xiao-Yan Wu; Yu-Chang Li; Qing-Yu Zhu; Yin-Hui Yang (Archives of Virology, 2013)

Characterization of embryogenesis and early larval development in the Pacific triton, Charonia tritonis (Gastropoda: Caenogastropoda) - Lü-Ping Zhang; Jian-Jun Xia; Peng-Fei Peng; Hai-Peng Li; Peng Luo; Chao-Qun Hu (Invertebrate Reproduction & Development, 2013)

Discrimination between Demodex folliculorum (Acari: Demodicidae) isolates from China and Spain based on mitochondrial cox1 sequences - Ya-e Zhao; Jun-xian Ma; Li Hu; Li-ping Wu; Manuel De Rojas (Journal of Zhejiang University-SCIENCE B, 2013)

Valproic acid reduces autophagy and promotes functional recovery after spinal cord injury in rats - Hai-Hu Hao; Li Wang; Zhi-Jian Guo; Lang Bai; Rui-Ping Zhang; Wei-Bing Shuang; Yi-Jia Jia; Jie Wang; Xiao-Yu Li; Qiang Liu (Neuroscience Bulletin, 2013)

Factors underlying the association of body mass index with serum ALT in Chinese hypertensive adults without known hepatic diseases - Yan Zhang; Xian-hui Qin; Jian-ping Li; Yi-min Cui; Ze-yuan Liu; Zhi-gang Zhao; Jun-bo Ge; De-ming Guan; Jian Hu; Yan-ni Wang; Fu-min Zhang; Xin Xu; et al. (Journal of Zhejiang University-SCIENCE B, 2013)

Geochemistry and Sr–Nd–Pb–Hf isotopic composition of the Donggou Mo-bearing granite porphyry, Qinling orogenic belt, central China - Li Yang; Fukun Chen; Bing-Xiang Liu; Zhao-Ping Hu; Yue Qi; Jia-De Wu; Jian-Feng He; Wolfgang Siebel (International Geology Review, 2013)

A consensus envelope protein domain III can induce neutralizing antibody responses against serotype 2 of dengue virus in non-human primates - Hsin-Wei Chen; Shih-Jen Liu; Yi-Shiuan Li; Hsueh-Hung Liu; Jy-Ping Tsai; Chen-Yi Chiang; Mei-Yu Chen; Chyi-Sing Hwang; Chin-Cheng Huang; Hui-Mei Hu; Han-Hsuan Chung; Sze-Hsien Wu; et al. (Archives of Virology, 2013)

Transcriptional Regulation of Genes Encoding Key Enzymes of Abscisic Acid Metabolism During Melon (Cucumis melo L.) Fruit Development and Ripening - Yufei Sun; Pei Chen; Chaorui Duan; Pang Tao; Yanping Wang; Kai Ji; Yin Hu; Qian Li; Shengjie Dai; Yan Wu; Hao Luo; Liang Sun; et al. (Journal of Plant Growth Regulation, 2013)

Occurrence, distribution, and sources of six phenolic endocrine disrupting chemicals in the 22 river estuaries around Dianchi Lake in China - Bin Wang; Bin Huang; Wei Jin; Shimin Zhao; Farong Li; Ping Hu; Xuejun Pan (Environmental Science and Pollution Research, 2013)

Dietary consumption and diet diversity and risk of developing bladder cancer: results from the South and East China case–control study - Fatima Isa; Li-Ping Xie; Zhiquan Hu; Zhaohui Zhong; Marjolein Hemelt; Raoul C. Reulen; Y. C. Wong; Po-Chor Tam; Kai Yang; Chao Chai; Xing Zeng; Yilan Deng; et al. (Cancer Causes & Control, 2013)

Finer resolution observation and monitoring of global land cover: first mapping results with Landsat TM and ETM+ data - Peng Gong; Jie Wang; Le Yu; Yongchao Zhao; Yuanyuan Zhao; Lu Liang; Zhenguo Niu; Xiaomeng Huang; Haohuan Fu; Shuang Liu; Congcong Li; Xueyan Li; et al. (International Journal of Remote Sensing, 2013)

Genetic structure and phylogeography of Pyrus pashia L. (Rosaceae) in Yunnan Province, China, revealed by chloroplast DNA analyses - Jing Liu; Ping Sun; Xiaoyan Zheng; Daniel Potter; Kunming Li; Chunyun Hu; Yuanwen Teng (Tree Genetics & Genomes, 2013)

Generalized Subcutaneous Phaeohyphomycosis Caused by Phialophora verrucosa: Report of a Case and Review of Literature - Zhongsheng Tong; Sharon C.-A. Chen; Liuqing Chen; Bilin Dong; Ruoyu Li; Zhimin Hu; Ping Jiang; Dongsheng Li; Yiqun Duan (Mycopathologia, 2013)

Suggestion of GLYAT gene underlying variation of bone size and body lean mass as revealed by a bivariate genome-wide association study - Yan-Fang Guo; Li-Shu Zhang; Yong-Jun Liu; Hong-Gang Hu; Jian Li; Qing Tian; Ping Yu; Feng Zhang; Tie-Lin Yang; Yan Guo; Xiang-Lei Peng; Meng Dai; et al. (Human Genetics, 2013)

The confirmation of three repeated sequence elements in the 3′ untranslated region of Chikungunya virus - Yu Zhang; Bing-Yin Si; Xiao-Ping Kang; Yi Hu; Jing Li; Xiao-Yan Wu; Yu-Chang Li; Yin-Hui Yang; Qing-Yu Zhu (Virus Genes, 2013)

Trends of precipitation extremes during 1960–2008 in Xinjiang, the Northwest China - Feng-qing Jiang; Ru-Ji Hu; Shao-Ping Wang; Yan-Wei Zhang; Li Tong (Theoretical and Applied Climatology, 2013)

Transforming growth factor-β1 induces matrix metalloproteinase-9 expression in rat vascular smooth muscle cells via ROS-dependent ERK–NF-κB pathways - Hao Zhang; Zhi-Wei Wang; Hong-Bing Wu; Zhi Li; Luo-Cheng Li; Xiao-Ping Hu; Zong-Li Ren; Bai-Jun Li; Zhi-Peng Hu (Molecular and Cellular Biochemistry, 2012)

Integrated Analysis on Gravity and Magnetic Fields of the Hailar Basin, NE China: Implications for Basement Structure and Deep Tectonics - Bin Sun; Liangshu Wang; Ping Dong; YongJing Wu; Changbo Li; Bo Hu; Chong Wang (Pure and Applied Geophysics, 2012)

Variations in soil culturable bacteria communities and biochemical characteristics in the Dongkemadi glacier forefield along a chronosequence - Guang-Xiu Liu; Ping Hu; Wei Zhang; Xiukun Wu; Xuan Yang; Tuo Chen; Manxiao Zhang; Shi-Weng Li (Folia Microbiologica, 2012)

Effects of hematin and carbon monoxide on the salinity stress responses of Cassia obtusifolia L. seeds and seedlings - Chunping Zhang; Yicun Li; Fenggang Yuan; Shijun Hu; Ping He (Plant and Soil, 2012)

Correlation between serum CA724 and gastric cancer: multiple analyses based on Chinese population - Xin-Zu Chen; Wei-Ke Zhang; Kun Yang; Lan-Lan Wang; Jin Liu; Li Wang; Jian-Kun Hu; Bo Zhang; Zhi-Xin Chen; Jia-Ping Chen; Zong-Guang Zhou; Xian-Ming Mo (Molecular Biology Reports, 2012)

A Highly Sensitive Fluorescent Probe for HClO and Its Application in Live Cell Imaging - Qing-Ping Zuo; Zuo-Jun Li; Yong-Hua Hu; Bin Li; Li-Hua Huang; Chun-Jiang Wang; Shi-Kun Liu; Hai-Qiang Liao (Journal of Fluorescence, 2012)

Fluid Flow-Induced Calcium Response in Early or Late Differentiated Osteoclasts - Ping Li; Man Hu; Shujin Sun; Yan Zhang; Yuxin Gao; Mian Long; Bo Huo; Ding Zhang (Annals of Biomedical Engineering, 2012)

Endothelin-induced differentiation of Nkx2.5+ cardiac progenitor cells into pacemaking cells - Xi Zhang; Jin-Ping Guo; Ya-Li Chi; Yan-Chun Liu; Chuan-Sen Zhang; Xiang-Qun Yang; Hai-Yan Lin; Er-Peng Jiang; Shao-Hu Xiong; Zhi-Ying Zhang; Bao-Hai Liu (Molecular and Cellular Biochemistry, 2012)

Cytomegalovirus infection and coronary heart disease risk: a meta-analysis - Ya-Nan Ji; Li An; Ping Zhan; Xiao-Hu Chen (Molecular Biology Reports, 2012)

S-nitrosylation of c-Src via NMDAR-nNOS module promotes c-Src activation and NR2A phosphorylation in cerebral ischemia/reperfusion - Li-Juan Tang; Chong Li; Shu-Qun Hu; Yong-Ping Wu; Yan-Yan Zong; Chang-Cheng Sun; Fa Zhang; Guang-Yi Zhang (Molecular and Cellular Biochemistry, 2012)

H. pylori related proinflammatory cytokines contribute to the induction of miR-146a in human gastric epithelial cells - Na Li; Xiang Xu; Bin Xiao; En-Dong Zhu; Bo-sheng Li; Zhen Liu; Bin Tang; Quan-Ming Zou; Hua-Ping Liang; Xu-Hu Mao (Molecular Biology Reports, 2012)

Hydrogen sulfide protects H9c2 cells against doxorubicin-induced cardiotoxicity through inhibition of endoplasmic reticulum stress - Xiu-Yu Wang; Chun-Tao Yang; Dong-Dan Zheng; Li-Qiu Mo; Ai-Ping Lan; Zhan-Li Yang; Fen Hu; Pei-Xi Chen; Xin-Xue Liao; Jian-Qiang Feng (Molecular and Cellular Biochemistry, 2012)

Inhibition of ROS-activated ERK1/2 pathway contributes to the protection of H2S against chemical hypoxia-induced injury in H9c2 cells - Xiao-Bian Dong; Chun-Tao Yang; Dong-Dan Zheng; Li-Qiu Mo; Xiu-Yu Wang; Ai-Ping Lan; Fen Hu; Pei-Xi Chen; Jian-Qiang Feng; Mei-Fen Zhang; Xin-Xue Liao (Molecular and Cellular Biochemistry, 2012)

A meta-analysis of association between acne vulgaris and Demodex infestation - Ya-e Zhao; Li Hu; Li-ping Wu; Jun-xian Ma (Journal of Zhejiang University-SCIENCE B, 2012)

Involvement of KATP/PI3K/AKT/Bcl-2 Pathway in Hydrogen Sulfide-induced Neuroprotection Against the Toxicity of 1-methy-4-phenylpyridinium Ion - Xiao-Qing Tang; Yuan-Yuan Zhuang; Li-Li Fan; Heng-Rong Fang; Cheng-Fang Zhou; Ping Zhang; Bi Hu (Journal of Molecular Neuroscience, 2012)

Effects of insulin-like growth factor-1 on the properties of mesenchymal stem cells in vitro - Yu-li Huang; Ruo-feng Qiu; Wei-yi Mai; Jian Kuang; Xiao-yan Cai; Yu-gang Dong; Yun-zhao Hu; Yuan-bin Song; An-ping Cai; Zhi-gao Jiang (Journal of Zhejiang University-SCIENCE B, 2012)

Facial dermatosis associated with Demodex: a case-control study - Ya-e Zhao; Yan Peng; Xiang-lan Wang; Li-ping Wu; Mei Wang; Hu-ling Yan; Sheng-xiang Xiao (Journal of Zhejiang University-SCIENCE B, 2011)

The effects of simvastatin on angiogenesis: studied by an original model of atherosclerosis and acute myocardial infarction in rabbit - Wei Shen; Hai-Ming Shi; Wei-Hu Fan; Xin-Ping Luo; Bo Jin; Yong Li (Molecular Biology Reports, 2011)

Regulation of melanocyte pivotal transcription factor MITF by some other transcription factors - Ping Wan; Yongqing Hu; Li He (Molecular and Cellular Biochemistry, 2011)

Dominant Contribution of Northern Chinese to the Paternal Genetic Structure of Chaoshanese in South China - Sheng-Ping Hu; Hui Li; Feng-Huan Zhang; Li-Qun Huang; Yan Lu (Biochemical Genetics, 2011)

Ds-echinoside A, a new triterpene glycoside derived from sea cucumber, exhibits antimetastatic activity via the inhibition of NF-κB-dependent MMP-9 and VEGF expressions - Qin Zhao; Zhi-dong Liu; Yong Xue; Jing-feng Wang; Hui Li; Qing-juan Tang; Yu-ming Wang; Ping Dong; Chang-hu Xue (Journal of Zhejiang University-SCIENCE B, 2011)

PzsS3a, a novel endosperm specific promoter from maize (Zea mays L.) induced by ABA - Yu-Feng Hu; Yang-ping Li; Junjie Zhang; Hanmei Liu; Zhiyu Chen; Yubi Huang (Biotechnology Letters, 2011)

Characterization of Exserohilum rostratum, a new causal agent of banana leaf spot disease in China - Shan-Hai Lin; Si-Liang Huang; Qi-Qin Li; Chun-Jin Hu; Gang Fu; Li-Ping Qin; Yue-Feng Ma; Ling Xie; Zhen-Lu Cen; Wei-Hong Yan (Australasian Plant Pathology, 2011)

Gα13 is closely related to hematopoiesis in zebrafish - Ding Ye; Qiwen Yang; Yang Li; Xinyun Huang; Jiarui Hu; Shiguang Qian; Zheng Tan; Ping Song (Molecular Biology Reports, 2011)

Targeting interleukin-21 in rheumatoid arthritis - Feng-Lai Yuan; Wei Hu; Wei-Guo Lu; Xia Li; Jian-Ping Li; Rui-Sheng Xu; Cheng-Wan Li; Fei-Hu Chen; Cheng Jin (Molecular Biology Reports, 2011)

Bacillus zhanjiangensis sp. nov., isolated from an oyster in South China Sea - Yi-Guang Chen; Song-Ping Hu; Shu-Kun Tang; Jian-Wu He; Jian-Qing Xiao; Hong-Yi Zhu; Wen-Jun Li (Antonie van Leeuwenhoek, 2011)

Localized expression pattern of miR-184 in Drosophila - Ping Li; Jianjian Peng; Jiangbo Hu; Zhongxin Xu; Wei Xie; Liudi Yuan (Molecular Biology Reports, 2011)

Molecular cytogenetic identification of a new wheat-Thinopyrum substitution line with stripe rust resistance - Li-Jun Hu; Guang-Rong Li; Zi-Xian Zeng; Zhi-Jian Chang; Cheng Liu; Jian-Ping Zhou; Zu-Jun Yang (Euphytica, 2011)

Alleviation of osteoarthritis by Trichostatin A, a histone deacetylase inhibitor, in experimental osteoarthritis - Wei-Ping Chen; Jia-Peng Bao; Peng-Fei Hu; Jie Feng; Li-Dong Wu (Molecular Biology Reports, 2010)

Globular adiponectin regulates energy homeostasis through AMP-activated protein kinase–acetyl-CoA carboxylase (AMPK/ACC) pathway in the hypothalamus - Jun-Ping Wen; Chun-e Liu; Ya-Ting Hu; Gang Chen; Li-xiang Lin (Molecular and Cellular Biochemistry, 2010)

Inhibition of acid-sensing ion channels in articular chondrocytes by amiloride attenuates articular cartilage destruction in rats with adjuvant arthritis - Feng-Lai Yuan; Fei-Hu Chen; Wei-Guo Lu; Xia Li; Jian-ping Li; Cheng-Wan Li; Rui-Sheng Xu; Fan-Rong Wu; Wei Hu; Teng-Yue Zhang (Inflammation Research, 2010)

Leptin plays a catabolic role on articular cartilage - Jia-peng Bao; Wei-ping Chen; Jie Feng; Peng-fei Hu; Zhong-li Shi; Li-dong Wu (Molecular Biology Reports, 2010)

Do local communities support the conservation of endangered Przewalski’s gazelle? - Junhua Hu; Xiaoge Ping; Jing Cai; Zhongqiu Li; Chunwang Li; Zhigang Jiang (European Journal of Wildlife Research, 2010)

Acid-sensing ion channel 1a mediates acid-induced increases in intracellular calcium in rat articular chondrocytes - Feng-Lai Yuan; Fei-Hu Chen; Wei-Guo Lu; Xia Li; Fan-Rong Wu; Jian-Ping Li; Cheng-Wan Li; Yu Wang; Teng-Yue Zhang; Wei Hu (Molecular and Cellular Biochemistry, 2010)

Neurochip based on light-addressable potentiometric sensor with wavelet transform de-noising - Qing-jun Liu; Wei-wei Ye; Hui Yu; Ning Hu; Li-ping Du; Ping Wang (Journal of Zhejiang University-SCIENCE B, 2010)

Isopentenyl transferase gene (ipt) downstream transcriptionally fused with gene expression improves the growth of transgenic plants - Jian-Chun Guo; Rui-Jun Duan; Xin-Wen Hu; Kai-Mian Li; Shao-Ping Fu (Transgenic Research, 2010)

Potential water sources for Late Quaternary Megalake Jilantai-Hetao, China, inferred from mollusk shell 87Sr/86Sr ratios - Yu-Xin Fan; Fa-Hu Chen; Guo-Xiao Wei; David B. Madsen; Charles G. Oviatt; Hui Zhao; Xi Chun; Li-Ping Yang; Tian-Lai Fan; Guo-Qiang Li (Journal of Paleolimnology, 2010)

Protective effect of selaginellin on glutamate-induced cytotoxicity and apoptosis in differentiated PC12 cells - Chen-Jing Wang; Chang-Ping Hu; Kang-Ping Xu; Qiong Yuan; Fu-Shuang Li; Hui Zou; Gui-Shan Tan; Yuan-Jian Li (Naunyn-Schmiedeberg's Archives of Pharmacology, 2010)

Inhibitory effect of reinioside C on monocyte–endothelial cell adhesion induced by oxidized low-density lipoprotein via inhibiting NADPH oxidase/ROS/NF-κB pathway - Yong-Ping Bai; Chang-ping Hu; Mei-Fang Chen; Kang-Ping Xu; Gui-Shan Tan; Rui-Zhen Shi; Yuan-Jian Li; Guo-Gang Zhang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2009)

cDNA cloning and expression analysis of a putative decarbonylase TaCer1 from wheat (Triticum aestivum L.) - Xiaojun Hu; Zhengbin Zhang; Weiqiang Li; Zhenyan Fu; Shuxin Zhang; Ping Xu (Acta Physiologiae Plantarum, 2009)

Prevalence, genetic diversity, and antimicrobial susceptibility profiles of Staphylococcus aureus isolated from bovine mastitis in Zhejiang Province, China - Jian-ping Li; Hai-jian Zhou; Lin Yuan; Ting He; Song-hua Hu (Journal of Zhejiang University-SCIENCE B, 2009)

Blockade of HERG K+ channel by isoquinoline alkaloid neferine in the stable transfected HEK293 cells - Dong-fang Gu; Xue-lian Li; Zhi-ping Qi; Sha-shan Shi; Mei-qin Hu; Dong-min Liu; Cheng-bai She; Yan-jie Lv; Bao-xin Li; Bao-feng Yang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2009)

Embryo and anther regulation of the mabinlin II sweet protein gene in Capparis masaikai Lévl - Xin-Wen Hu; Si-Xin Liu; Jian-Chun Guo; Ji-Tao Li; Rui-Jun Duan; Shao-Ping Fu (Functional & Integrative Genomics, 2009)

Secretory expression of K88 (F4) fimbrial adhesin FaeG by recombinant Lactococcus lactis for oral vaccination and its protective immune response in mice - Chun Xia Hu; Zi Rong Xu; Wei Fen Li; Dong Niu; Ping Lu; Ling Lin Fu (Biotechnology Letters, 2009)

STR Polymorphisms of the Henan Population and Investigation of the Central Plains Han Origin of Chaoshanese - Li-Na Xu; Sheng-Ping Hu; Guo-Ying Feng (Biochemical Genetics, 2009)

Secretory expression of K88 (F4) fimbrial adhesin FaeG by recombinant Lactococcus lactis for oral vaccination and its protective immune response in mice - Chun Xia Hu; Zi Rong Xu; Wei Fen Li; Niu Dong; Ping Lu; Ling Lin Fu (Biotechnology Letters, 2009)

A new screening method based on yeast-expressed human dipeptidyl peptidase IV and discovery of novel inhibitors - Chen-Xi Hu; Hui Huang; Li Zhang; You Huang; Zhu-Fang Shen; Ke-Di Cheng; Guan-Hua Du; Ping Zhu (Biotechnology Letters, 2009)

Association of polymorphisms at restriction enzyme recognition sites of apolipoprotein B and E gene with dyslipidemia in children undergoing primary nephrotic syndrome - Peng Hu; Yuan Han Qin; Cheng Xue Jing; Feng Ying Lei; Ping Chen; Ming Fang Li (Molecular Biology Reports, 2009)

Induction of cytochrome P450 2B6 activity by the herbal medicine baicalin as measured by bupropion hydroxylation - Lan Fan; Jin-Chao Wang; Feng Jiang; Zhi-Rong Tan; Yao Chen; Qing Li; Wei Zhang; Guo Wang; He-Ping Lei; Dong-Li Hu; Dan Wang; Hong-Hao Zhou (European Journal of Clinical Pharmacology, 2009)

The CYP2C19 ultra-rapid metabolizer genotype influences the pharmacokinetics of voriconazole in healthy male volunteers - Guo Wang; He-Ping Lei; Zhi Li; Zhi-Rong Tan; Dong Guo; Lan Fan; Yao Chen; Dong-Li Hu; Dan Wang; Hong-Hao Zhou (European Journal of Clinical Pharmacology, 2009)

Relationships Among Genetic Makeup, Active Ingredient Content, and Place of Origin of the Medicinal Plant Gastrodia Tuber - Jun Tao; Zhi-yong Luo; Chikira Ismail Msangi; Xiao-shun Shu; Li Wen; Shui-ping Liu; Chang-quan Zhou; Rui-xin Liu; Wei-xin Hu (Biochemical Genetics, 2009)

Isolation and Description of a Stable Carbazole-Degrading Microbial Consortium Consisting of Chryseobacterium sp. NCY and Achromobacter sp. NCW - Weiqiang Guo; Daping Li; Yong Tao; Ping Gao; Jijun Hu (Current Microbiology, 2008)

Solid lipid nanoparticles loading adefovir dipivoxil for antiviral therapy - Zhang Xing-guo; Miao Jing; Li Min-wei; Jiang Sai-ping; Hu Fu-qiang; Du Yong-zhong (Journal of Zhejiang University-SCIENCE B, 2008)

Proteiomic patterns for endometrial cancer using SELDI-TOF-MS - Li-rong Zhu; Wen-ying Zhang; Li Yu; Yan-hua Zheng; Jun Hu; Qin-ping LIAO (Journal of Zhejiang University-SCIENCE B, 2008)

Sensing Escherichia coli O157:H7 via frequency shift through a self-assembled monolayer based QCM immunosensor - Li-jiang Wang; Chun-sheng Wu; Zhao-ying Hu; Yuan-fan Zhang; Rong Li; Ping Wang (Journal of Zhejiang University-SCIENCE B, 2008)

Detection of three pear viruses by multiplex RT-PCR assays with co-amplification of an internal control - Bing-Gang Ma; Jian-Xin Niu; M. Morley-Bunker; Li-Zhong Pan; Hu-Ping Zhang; Lu-Xia Zhang (Australasian Plant Pathology, 2008)

Expression and characteristic of synthetic human epidermal growth factor (hEGF) in transgenic tobacco plants - Jie-Ying Bai; Lin Zeng; Yuan-Lei Hu; Yan-Fang Li; Zhong-Ping Lin; Shi-Chen Shang; Yan-Sheng Shi (Biotechnology Letters, 2007)

Expression analysis of the NDRG2 gene in mouse embryonic and adult tissues - Xiao-Lan Hu; Xin-Ping Liu; Yan-Chun Deng; Shu-Xin Lin; Lin Wu; Jian Zhang; Li-Feng Wang; Xiao-Bin Wang; Xia Li; Lan Shen; Yuan-Qiang Zhang; Li-Bo Yao (Cell and Tissue Research, 2006)

Decreased cardiac sarcoplasmic reticulum Ca2+-ATPase activity contributes to cardiac dysfunction in streptozotocin-induced diabetic rats - Xiao-Yan Zhao; Shen-Jiang Hu; Jiang Li; Yun Mou; Bao-Ping Chen; Qiang Xia (Journal of Physiology and Biochemistry, 2006)

Dynamic analysis and evaluation of Xinjiang forest resources: Based on RS and GIS - Li Hu; Wang Xiaofeng; Chen Shujiang; Hou Ping (Journal of Geographical Sciences, 2005)

Expression of a begomoviral DNAβ gene in transgenic Nicotiana plants induced abnormal cell division - Xiao-feng Cui; Yun-qin Li; Dong-wei Hu; Xue-ping Zhou (Journal of Zhejiang University-SCIENCE B, 2005)

Mapping of quantitative trait loci (QTLs) for rice protein and fat content using doubled haploid lines - Zhong-Li Hu; Ping Li; Ming-Quan Zhou; Zhi-Hong Zhang; Ling-Xia Wang; Li-Huang Zhu; Ying-Guo Zhu (Euphytica, 2004)

Identification of quantitative trait loci (QTLs) for the characters of vascular bundles in peduncle related to indica-japonica differentiation in rice (Oryza sativa L.) - Zhi-Hong Zhang; Ping Li; Ling-Xia Wang; Chang-Jun Tan; Zhong-Li Hu; Ying-Guo Zhu; Li-Huang Zhu (Euphytica, 2002)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Effect of total alkaloid ofPeganum harmala L. in the treatment of experimental haemosporidian infections in cattle - Bingtang Fan; Jilan Liang; Jucheng Men; Fang Gao; Guangling Li; Sixi Zhao; Tingjun Hu; Ping Dang; Ling Zhang (Tropical Animal Health and Production, 1997)